Reconciling explicit and homogenized modeling strategies for compression behavior of cracked soils - Zhao-Lin Cai; Yu-Jun Cui; Chao-Sheng Tang; Qing Cheng; Zhi-Xiong Zeng; Xin-Lun Ji (Computers and Geotechnics, 2027)

Application of molasses improves strawberry marketability by enhancing fruit flavor and aroma - Yuanxiu Lin; Yu Long; Zimeng Cui; Siqi Dai; Yunting Zhang; Mengyao Li; Qing Chen; Yong Zhang; Haoru Tang; Yifei Zhou; Ya Luo (Postharvest Biology and Technology, 2026)

Integrating genomic evolution and reported outbreak occurrence in foot-and-mouth disease in Asia: Cross-border lineage connectivity and exploratory prediction of reported outbreak occurrence - Xiaoyu Ge; Yize Li; Jiaxuan Li; Yanping Jiang; Wen Cui; Xiaona Wang; Lijie Tang (Preventive Veterinary Medicine, 2026)

Tracing sediment provenance in the eastern Beibu Gulf, South China Sea using detrital zircon U-Pb ages and clay minerals - Yuxin Qin; Xianlong Zhu; Xiaoyan Tang; Heqi Cui; Kaixi Jiang; Ce Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Eastward radiation of C4 crops from the Hongshan culture core region initiated around 6 ka - Licheng Guo; Qiaowen Zhang; Shiling Yang; Shangfa Xiong; Zihua Tang; Zhe Liu; Jingyi Cui; Linlin Cui (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

MMDiff: Multi-modal remote sensing image generation via cross-modality spatial feature transfer - Haojun Tang; Wenda Zhao; Hengshuai Cui; Haipeng Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

A comparative study on radio frequency inactivation kinetics of Bacillus cereus vegetative cells and A. flavus spores in sunflower seeds: nonlinear modeling and its impact on storage stability - Xuan Ou; Sen Zeng; Jiamin Song; Songlei Wang; Yunyang Wang; Baozhong Cui; Guangxian Wang; Ping Zhang; Qiuyu Deng; Yinghua Tang; Yanan Sun (Food Research International, 2026)

Knowledge-guided graph neural network: A code-embedded stress-field learning framework for predicting the fatigue life of corroded welded joints - Kun Tang; Chuang Cui; Xiong Tian; Yan Ma; Qinghua Zhang; Yi Bao (Engineering Structures, 2026)

Disguise strategy-adjusted controlled cleavage of DNA hydrogel for precision theranostics in colorectal cancer - Bo Han; Haitao Cui; Wenhui Chen; Zixiao Ma; Dandan Liang; Dongyang Wang; Jinghui Zhang; Juan Song; Sheng Tang (Chemical Engineering Journal, 2026)

Biomass-derived self-supporting thick porous carbon electrodes via KOH-assisted hydrothermal treatment and hot pressing reconstruction for high-performance supercapacitors - Yexuan Tang; Caiwei Wang; Yangzi Luo; Yan He; Xuemin Cui (Chemical Engineering Journal, 2026)

Dual-tailoring of microenvironment and electronic structure in tandem catalysts for highly selective CO2-to-ethanol electroreduction - Shuo Cui; Cheng Yang; Tingting Tang; Xinjie Liu; Xinlong Huang; Junyang Li; Wei Cui; Zengxi Li; Hong Zhao (Chemical Engineering Journal, 2026)

Valorization of microalgal lipids for the production of high-value bio-based epoxidized monomers - Jiarong Tian; Siyuan Zhang; Yue Liu; Wei Rao; Kuichuan Sheng; Jun Wang; Yu Tang; Shaoqing Cui (Biomass and Bioenergy, 2026)

Enterococcus in herbal fermentation: a genus-specific perspective on enzymatic capability, biotransformation outcomes and safety - Jiafei Tang; Shuo Zhang; Gui Xu; Mengxiao Cui; Xiutong Ge; Hui Gao; Fan Zhang (Archives of Microbiology, 2026)

Underwater reverberation suppression based on multi-view online subspace tracking in moving target scenarios - Jiajie Liu; Qunfei Zhang; Chencong Tang; Boheng Wang; Xiaodong Cui (Ocean Engineering, 2026)

Enhanced bio-electrochemical decolorization of azo dye by an rGO/ polyaniline-modified biocathode: Performance improvement and cathodic microbiome reshaping - Tao Hou; Hong-Li Lu; Naif Abdullah Al-Dhabi; Ai-Hong Chen; Wang-Wang Tang; Meng-Yuan Li; Dan Cui (Journal of Environmental Chemical Engineering, 2026)

Hydrothermal synthesis of carbon-zeolite composites from coal gasification coarse slag and fine slag: Insight into residual carbon - Jungang Tang; Kaizhi Yang; Mingmin Bao; Li Cui; Jianming Gao; Fangqin Cheng; Kezhou Yan (Journal of Environmental Chemical Engineering, 2026)

Spatial regulation of Fe species in Fe-Zn@HY catalysts via sequential ion exchange for enhanced heterogeneous Fenton degradation of phenol - Gengchen Han; Rongji Cui; Junnan Liu; Weiliang Han; Zhicheng Tang (Journal of Environmental Chemical Engineering, 2026)

Standardization of urban heat island effects and how different building types reflect solar radiation to form thermal inertia - Kui Yang; Jinting Zhang; Dongge Cui; Qi Tang; Yaoxuan Zhang (Energy and Buildings, 2026)

A new unified phase field hybrid fracture model considering the nonlinear coupling of Mode I/II and III fracture for rock-like geomaterials - Yajun Cao; Shaoxun Song; XiaoYan Cui; Jianwei Tang; Yulong Zhang (Computers and Geotechnics, 2026)

Bacterial cellulose–Morchella sextelata mycelium composite disks as scalable, bioactive scaffolds: A promising platform for cultured meat - Yunan Tang; Yue Li; Shucheng Liu; Shaoqing Cui; Ximing Zhang (Carbohydrate Polymers, 2026)

Chemical constituents from the aerial parts of Rauvolfia yunnanensis Tsiang and their chemotaxonomic significance - Wanqi Yang; Xiaoyan Cui; Renfeng Ye; Min Jiang; Shijing Tang; Wenjing Dong; Guiguang Cheng; Yaping Liu (Biochemical Systematics and Ecology, 2026)

Size-dependent regulation of soil microbial functional-network structure by polystyrene microplastics - Guanlin Li; Junliang Chen; Yi Tang; Xiaoxun Zhao; Sushu Cui; Babar Iqbal; Pengfei Cheng; Tingting Zhao; Daolin Du; Peng Wang (Applied Soil Ecology, 2026)

A synergy strategy of deep eutectic solvents and boric acid modified β-CD polymer for enhancing enantioseparation in HPLC - Xiaoqian Yuan; Ziyi Cheng; Jiajia Fu; Wanting Duan; Yuchen Cui; Ruijun Tang; Xinru Wang; Youxin Li (Analytica Chimica Acta, 2026)

Curcumin maintains pseudorabies virus latent infection by inhibiting the phosphorylation level of EGFR protein - Yuhang Li; Fan Yang; Dingqiu Zou; Pei Liu; Kexin Qi; Jingyi Wang; Chenlu Sun; Yanru Tang; Ruihan Zhang; Junyan Ren; Zijie Cui; Ruoxian Li; et al. (Veterinary Microbiology, 2026)

Seepage characteristics and transformation mechanisms of point–linear–planar infiltration in loess tunnels - Guanhua Cui; Junling Qiu; Jinxing Lai; Kunjie Tang; Jiawei Xu; Hao Sun (Tunnelling and Underground Space Technology, 2026)

Real-world exposure parameters of ten color cosmetic categories in shanghai and health risk assessment of potentially toxic elements in lipsticks - Yuanyuan She; Yang Tang; Jian Chen; Tian Chen; Wenguang Cui; Yijun Chen; Lihong Zhou; Zhu Li (Regulatory Toxicology and Pharmacology, 2026)

γ-aminobutyric acid (GABA) treatment alleviates off-flavor in postharvest waxed citrus fruit by enhancing peel gas permeance - Zhiquan Wang; Junchao Wang; Lu Qin; Zhen Huang; Xinxin Xu; Zhifeng Zhu; Jingjie Tang; Xiaojie Cui; Rangwei Xu; Feng Zhu; Yanping Fu; Xiuxin Deng; et al. (Postharvest Biology and Technology, 2026)

Urbanization is associated with changes in the sensitivity of water quality to drought - Dongxin Tang; Pengcheng Sun; Shengzhi Huang; Xiaoting Wei; Yifei Li; Hao Cui; Dong Liu; Fuqiang Wang; Jingqing Gao (Journal of Hydrology, 2026)

Linking botany and mineral exploration: Alhagi sparsifolia as a potential indicator for Ni-Cu sulfide deposits - Meng-Meng Cui; Ben-Xun Su; Shan-Ke Liu; Hui-Li Yan; Wen-Jun Li; Bing-Yu Gao; Jing Wang; Zhen-Yan He; Shu-Kuan Wu; Ye-Tao Tang (Journal of Asian Earth Sciences, 2026)

Combined application of 1-methylcyclopropene and silicon-window modified atmosphere packaging delays cell wall degradation and softening in cold-stored ‘Saiwaihong’ apples - Cheng Zhao; Jiefen Cui; Hao Wu; Xuanming Tang; Xueping Wang; Mengyu Ma; Ting Liu; Yanfang Pan; Jinkai Zheng (Food Chemistry, 2026)

Physicochemical and structural characterization of self-assembled nanoparticles from whey protein isolate–dextran Maillard conjugates and binding mechanism with capsaicin - Chen Huang; Xinjing Li; Guzalnur Askar; Heping Cui; Jingyang Yu; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Chemistry, 2026)

Phenolic mediated browning of sushi ginger slices during storage and its inhibition by enzyme inactivation and reduced phenolic availability during mild blanching - Jingyang Yu; Jiahui Zhou; Tong Zhou; Yishun Yao; Shuqin Xia; Heping Cui; Jianzeng Liu; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Bioscience, 2026)

Machine learning–fugacity framework reveals the fate and environmental drivers of per- and polyfluoroalkyl substances in a mountainous river - Yanan Li; Wenjing Lv; Jiao Ren; Jianhui Tang; Jiayin Dai; Qiusheng He; Yang Cui; Lijuan Huo; Ke Zhang; Yitao Pan (Environmental Pollution, 2026)

TBBPA-induced insulin reduction in two generations of marine medaka (Oryzias melastigma) with calcium signaling as a key event - Teng Wang; Yi Ge; Jinghe Li; Yanxin Qiao; Yingqi Tang; Xiaoying Cui; Jin Yong Lee; Zhengyan Li (Environmental Pollution, 2026)

Coupled effect of crack inclination and microstructure on the mechanical behavior of soils - Zhao-Lin Cai; Yu-Jun Cui; Chao-Sheng Tang; Qing Cheng; Zhi-Xiong Zeng; Xin-Lun Ji; Tao Wang; Hao Wang; Hai Wang; Jun-Feng Ren (Engineering Geology, 2026)

Rapid and multimodal responsive composite hydrogel actuator with enhanced mechanical performance and reprogrammability for complex application scenarios in soft robotics - Zhilin Zhang; Xingchen Cui; Xing Gao; Xu Zhai; Zijing Huang; Jianwei Sun; Yi Tang; Yan Wang; Yu Fu; Tieqiang Wang (Chemical Engineering Journal, 2026)

Synergistic neurotoxicity of mono-butyl phthalate and bisphenol A at environmentally relevant concentrations: Multi-Omics evidence for ferroptosis via glutathione metabolism disruption in neural stem cells and brain organoids - Yunpeng Li; Fengzhen Cui; Huanwen Tang (Chemico-Biological Interactions, 2026)

FOXO1 Promotes Mitophagy in Granulosa Cells by Targeting the METTL3/SMAD4 axis - Lan Luo; Mi Tang; Yanli Peng; Xi Chen; Yaqi Liu; Jialan Cui (Cell Biochemistry and Biophysics, 2026)

Advances in Remote Sensing-Based Studies on Environmental Characteristics and Formation Mechanisms of Purpleback Flying Squid Fishing Grounds - Wei Fan; Ruizhi Zhou; Xuesen Cui; Yongchuang Shi; Yumei Wu; Fenghua Tang; Guoqing Zhao (Fishes, 2026)
The purpleback flying squid (Sthenoteuthis oualaniensis) is an important commercially exploited cephalopod resource in tropical open oceans. The formation and spatial variability of its fishing grounds are jointly regulated by local marine environmental conditions, ocean dynamic processes, and multiscale climate variability. In recent years, substantial progress has been achieved in understanding the environmental characteristics and formation mechanisms of S. oualaniensis fishing grounds with the development of satellite remote sensing, multisource oceanographic observations, and ecological statistical models. However, due to differences in study regions, data sources, and modeling approaches, considerable discrepancies remain among studies regarding the mechanisms through which environmental factors and climate modes influence the distribution and abundance variations in S. oualaniensis resources. This review systematically summarizes recent advances in the application of remote sensing and multisource marine data in S. oualaniensis fishing ground studies and highlights the ecological significance of major environmental drivers. Current evidence indicates that the formation of S. oualaniensis fishing grounds is not controlled by a single environmental factor but results from the integrated effects of SST, Chl-a, oceanographic dynamic processes (e.g., mesoscale eddies, fronts, and upwelling), and subsurface environmental conditions such as thermocline structure and dissolved oxygen. Suitable thermal conditions and moderate productivity levels provide fundamental environmental prerequisites for resource aggregation, whereas mesoscale physical processes and three-dimensional ecological structures further regulate prey transport, habitat availability, and squid aggregation processes. Moreover, substantial regional differences exist in fishing ground formation mechanisms. In the northwestern Indian Ocean, fishing grounds are primarily controlled by monsoon-driven upwelling and large-scale circulation systems, exhibiting strong continuity and pronounced climate-related variability. In contrast, fishing grounds in the South China Sea are more strongly influenced by Kuroshio intrusion, island–reef topography, and regional circulation processes, resulting in greater spatial heterogeneity. With advances in analytical approaches, fishing ground prediction methods for S. oualaniensis have gradually evolved from empirical statistical analyses toward multifactor statistical modeling and machine-learning-based prediction frameworks. Nevertheless, resolving three-dimensional ecological processes, developing physical–biological coupled models, and improving model interpretability remain key challenges for future research. This review provides theoretical insights for remote sensing-based investigations of S. oualaniensis fishing ground formation mechanisms, resource assessment, and sustainable exploitation.

ElHyX enables multimodal implantable bioelectronics for autonomous disease management - Lei Zhang; Cui Ye; You Yu; Yu Song; Yadong Xu; Wenzheng Heng; Songsong Tang; Minqiang Wang (Science Bulletin, 2026)

Flood driving the migration of the prehistoric settlements in the Chengdu plain, southwest China - Daobin Tang; Peng Cui; Weiming Liu; Jiao Wang; Zewen Yang; Zili Wang; Anna Yang; Xiangjun Liu (Quaternary Science Reviews, 2026)

Dynamic responses of floating offshore wind turbines under freak waves: A review - Yan Li; Haoran Li; Qiang Zhu; Yougang Tang; Bin Wang; Yiting Feng; Ouming Su; Guoyan Li; Yiwen Cui (Ocean Engineering, 2026)

Spatial distribution of per- and polyfluoroalkyl substances in the Yellow River basin: Role of suspended sediment on the PFAS partition and accumulation - Yanan Li; Yawen Li; Yitao Pan; Wenjing Lv; Fengfeng Dong; Qiusheng He; Lijuan Huo; Yang Cui; Ke Zhang; Jiayin Dai; Jianhui Tang (Journal of Hazardous Materials, 2026)

Long-range transported dust enhances ice nucleating particle abundance in the North China Plain - Yue Sun; Yujiao Zhu; Hengde Liu; Lanxiadi Chen; Hongyong Li; Yujian Bi; Di Wu; Xiangkun Yin; Can Cui; Ping Liu; Yu Yang; Jisheng Zhang; et al. (Journal of Environmental Sciences, 2026)

In-situ lignin-integrated nanocellulose multifunctional composite films for fruit preservation applications - Silong Wu; Junwei Tang; Jiaqian Cui; Xijiao Bian; Yifan Zhang; Jungang Jiang; Lei Wang (Food Research International, 2026)

Carvone nanoemulsions stabilized by octenyl succinic anhydride starch and pea protein isolate effectively inhibits Botryosphaeria dothidea in postharvest kiwifruit - Yu Tang; Yawen Li; Haiying Yang; Xuan Cui; Qi Tang; Shenghua Ding; Rongrong Wang (Food Bioscience, 2026)

Legacy and emerging organophosphate compounds in plateau rivers: Insights into environmental fate and risk from target and nontarget analyses - Zhenfei Han; Jinze He; Yisheng Xu; Wei Zheng; Xuexin Yang; Shuling Duan; Song Tang; Xiaoyu Cui; Yindong Tong; Hongyang Cui (Environmental Research, 2026)

Chloride-repelling and interfacial hydroxyl enrichment synergy in Co-Pi@Cr2O3-CoP for high current density alkaline seawater electrolysis - Tingting Tang; Cheng Yang; Xinlong Huang; Shuo Cui; Xinjie Liu; Junyang Li; Wei Cui; Zengxi Li; Hong Zhao (Chemical Engineering Journal, 2026)

Nanoconfinement of phase separation toward high-performance and reversible all-solid-state CuS batteries - Xianwei Wang; Jiawu Cui; Kang Yang; Qi Ling; Zhen Wang; Liang Xie; Chao Wu; Chengwei Wu; Yuping Wu; Chengyong Shu; Shenghua Chen; Wei Tang (Chemical Engineering Journal, 2026)

Improved photovoltaic performance via synergistically combining electric poling and flexoelectricity on lead-free ferroelectric (KNbO3)0.9(BaNi1/2Nb1/2O3-δ)0.1 films - Chuanqing Li; Yu Cai; Feifan Hu; Zhihua Duan; Tao Wang; Xiaomei Qin; Yanxue Tang; Xiangyong Zhao; Aiyun Liu; Feifei Wang; Zhongchen Gao; Fang Wang; et al. (Chemical Engineering Journal, 2026)

Mechanisms underlying the modification of corn starch granules by raw starch-degrading amylase with substrate-targeting specificity - Lingli Zhong; Wenming Chang; Kai Yang; Songchen Jiang; Jin Lin; Yifei Shu; Yukun Zhong; Zehao Tang; Xianfeng Ye; Yanling Ji; Lei Zhang; Yan Huang; et al. (Carbohydrate Polymers, 2026)

Synergistic mineral-microbial regulation dominates mineral-associated organic carbon accrual by carbonate weathering - Chunpei Li; Junfang Cui; Tao Wang; Lu Chen; Mei Lu; Xiaodong Tu; Zhaoyang Shi; Jialiang Tang (CATENA, 2026)

LncRNA MNX1-AS1 drives the progression of non-small cell lung cancer and serves as a ceRNA to target COMMD8 by sponging miR-218-5p - Gao-Feng Liu; Li Zhou; Yu-Bo Zhao; Jia-Hong Tang; Qing-Yuan Li; Xiao-Yong Ding; Xiao-Zhen Zhang; Su-Juan Cui; Yong Zhang; Zhen-Wei Sun (Journal of Molecular Histology, 2026)
The role and mechanistic action of MNX1-AS1 in non-small cell lung cancer (NSCLC) remain unclear. This study aimed to investigate the function of MNX1-AS1 in the progression of NSCLC. A total of 40 paired tumor and adjacent lung tissue samples from patients with NSCLC were collected to investigate the expression of MNX1-AS1. H1299 and HCC827 cells were transfected with sh-MNX1-AS1, shRNA-NC, miR-218-5p mimic, mimic-NC, pcDNA3.1-COMMD8, or empty vector (pcDNA3.1). The expression of MNX1-AS1, miR-218-5p, and COMMD8 was detected using quantitative real-time PCR (qRT-PCR). Cell proliferation was evaluated using CCK-8 assays, while cell migration and invasion were evaluated using Transwell assays. Dual-luciferase reporter and RNA pull-down assays were performed to validate the targeting interactions between MNX1-AS1 and miR-218-5p, as well as between COMMD8 and miR-218-5p. In vivo, a nude mouse model was established: tumor volume and weight were measured after four weeks. Gene expression in tumor tissue was quantified using qRT-PCR, and Ki-67 expression was evaluated using immunohistochemistry. MNX1-AS1 expression was significantly upregulated in NSCLC tissues ( P < 0.05) and was correlated with poor prognosis in NSCLC patients. MNX1-AS1 knockdown markedly suppressed the viability, migration, and invasion of H1299 and HCC827 cells ( P < 0.05). Mechanistically, MNX1-AS1 acted as a molecular sponge for miR-218-5p, thereby relieving miR-218-5p-mediated repression of its direct target COMMD8 ( P < 0.05). Functional rescue experiments revealed that miR-218-5p silencing or COMMD8 overexpression partially reversed the inhibitory effects of MNX1-AS1 knockdown on the cell viability, migration, and invasion of H1299 and HCC827 cells. In vivo, sh-MNX1-AS1 significantly reduced tumor volume and weight ( P < 0.05). Moreover, the expression of MNX1-AS1, COMMD8, and Ki-67 were downregulated, while the expression of miR-218-5p was upregulated in sh-MNX1-AS1 tumor tissues ( P < 0.05). MNX1-AS1 promotes the progression of NSCLC by modulating the miR-218-5p/COMMD8 axis.

Slope stability analysis using semidefinite programming-optimized strength reduction finite element method with parallel search algorithm - Xi Chen; Liusheng Cui; Jianbin Tang (Computational Geosciences, 2026)

Fracture behavior and constitutive modeling of rock-concrete contact surfaces with different roughness under freeze–thaw cycles - Mengyuan Cui; Taoying Liu; Yeshan Sheng; Min Tang; Wenbin Cai; Longjun Dong (Bulletin of Engineering Geology and the Environment, 2026)

Artificial Intelligence and Protein Design: A retrospective study on 20-year emerging trends and core research areas from bibliometric perspectives - Wenjuan Zhao; Xiuwu Pan; Wei Yang; Zichang Liu; Xiyi Wei; Anqi Lin; Bufu Tang; Lin Zhang; Mingjia Xiao; Qing Zeng; Quan Cheng; Weiming Mou; et al. (Probiotics and Antimicrobial Proteins, 2026)

Establishment and Application of a Triple TaqMan qPCR Detection Method for IMNV, DIV1, and CMNV - Yuzhi Wang; Chuang Cui; Xiaoqian Tang; Jing Xing; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Journal of Fish Diseases, 2026)
The escalating incidence of emerging pathogens and their propensity for co‐infection pose a severe threat to the sustainable intensification of Penaeus vannamei aquaculture. To address this challenge, a novel triplex TaqMan quantitative PCR (qPCR) assay was developed for the simultaneous detection of three high‐risk agents: Infectious Myonecrosis Virus (IMNV), Decapod Iridescent Virus 1 (DIV1), and Covert Mortality Nodavirus (CMNV). This study not only establishes a robust multiplex platform but also systematically optimises its performance, achieving superior analytical sensitivity and reproducibility compared to existing single‐target or duplex methods. The assay demonstrated a limit of detection as low as 10 1 copies/μL for all targets, with excellent inter‐ and intra‐assay coefficients of variation (CVs) consistently below 3%. Notably, the method effectively overcomes the technical hurdles associated with detecting both RNA (IMNV, CMNV) and DNA (DIV1) viruses within a single reaction, eliminating cross‐reactivity and ensuring high specificity. Validated against clinical samples, the established protocol exhibits a concordance rate exceeding 95% with current standard methods, while significantly streamlining the diagnostic workflow. This advancement provides a powerful tool for routine biosecurity monitoring, seed stock certification, and the comprehensive management of emerging shrimp diseases.

An ion-mediated synergistic composite suppressant for coal dust control during transportation: Interfacial wetting mechanisms and sustained moisture retention effects - Yanan Yuan; Liang Yuan; Bingyou Jiang; Mingyun Tang; Bo Ren; Ben Ji; Hanyi Lin; Jie Wang; Leyun Cui (Process Safety and Environmental Protection, 2026)

Establishment of A triplex TaqMan qPCR assay for EHP, VpTPD, VpAHPND with optimized efficacy using methyl cellulose - Yuzhi Wang; Chuang Cui; Xiaoqian Tang; Jing Xing; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Journal of Invertebrate Pathology, 2026)

High-intensity intermittent aeration with multi-stage descending rates enhances oxygen uptake to mitigate nitrogen emissions and promote humification in composting - Ruolan Tang; Ruonan Ma; Kaishu Luo; Yifan Zhai; Bin cui; Fanqiao Meng; Guoxue Li; Yue Xie; Jing Yuan (Journal of Cleaner Production, 2026)

Synergistic Mo2C/MoO2 hybridization in sucrose-derived hard carbon spheres for sodium-ion batteries - Hong Cui; Liang Liu; Jiacheng Shen; Ge Lin; Yiting Dai; Yuanzhe Wang; Yue Tang; Jiantie Xu (Chemical Engineering Journal, 2026)

Regulating surface hydroxyl anchoring sites to tailor metal–support interactions in Ni–FAU bifunctional materials for integrated CO₂ capture and methanation - Pengchao Zang; Jiyun Tang; Xiaozhe Wang; Wei Dong; Hao Zhang; Lin Cui; Shouyan Chen; Guojie Qi; Yong Dong (Chemical Engineering Journal, 2026)

Artemisinin derivative SM934 targets α-enolase to inhibit PEP-mediated TAK1 stabilization and inflammation - Jun Pan; Yuwei Zhang; Zhiwei Du; Yuanyuan Huang; Yu Wang; Miya Su; Yuting Cai; Weiya Xu; Lili Chen; Chengdong Huang; Di Cui; Dongsheng Chen; et al. (Science China Life Sciences, 2026)

Effects and Mechanism of Lactobacillus gasseri CCFM1346 Combined with Rutin on Alleviating Hyperuricemia in Mice - Xin Tang; Shuling Zhang; Bingyong Mao; Qiuxiang Zhang; Jianxin Zhao; Wei Chen; Shumao Cui (Probiotics and Antimicrobial Proteins, 2026)

Age-related metabolomic signatures and stroke susceptibility in a population-based cohort - Yanfeng Jiang; Qingxia Huang; Jincheng Li; Qinsheng Chen; Jialin Li; Zhenqiu Liu; Mei Cui; Chen Suo; Kelin Xu; Li Jin; Huiru Tang; Xingdong Chen (GeroScience, 2026)

Targeting the TOPK-STAT3 pathway in keratinocytes and mast cells mediates the therapeutic attenuation of Atopic dermatitis - Xiaohan Du; Xianshuai Shi; Qian He; Zheng Yuan; Longzhen Cui; Beibei Tang; Shuang Zhao; Yafang Li; Lei Ma; Mee-Hyun Lee; Olesya S. Malyarenko; Juanjuan Xiao; et al. (Inflammation Research, 2026)

CART Rule-Guided MaxEnt Model Construction and Its Application in Fishing Ground Prediction of Chub Mackerel in the Northwestern Pacific Ocean - Zuli Wu; Fenghua Tang; Yumei Wu; Shengmao Zhang; Fei Wang; Xuesen Cui (Fishes, 2026)
Chub mackerel (Scomber japonicus) is a commercially important pelagic species in the northwest Pacific Ocean. Accurate identification of its fishing grounds can provide a more robust and targeted scientific basis for fishery management and ecological research. Based on fishing effort and five environmental factors (i.e., sea surface temperature [SST], chlorophyll-a concentration [CHL], SST gradient [GSST], sea surface height [SSH], and current speed), this study developed a Classification and Regression Tree (CART) rule-guided MaxEnt model. Specifically, rules generated by the CART model were first extracted and then incorporated as constrained feature functions into MaxEnt for model training. To select the optimal model scheme, four combinations of rule compositions and feature function outputs were designed, and model performance on the validation dataset was evaluated using ROC curves. Finally, the model was further verified with in situ environmental and fisheries data from April to November 2024. Results showed that the predicted fishing grounds were highly aligned with the actual monthly fishing grounds in 2024, and the predicted migration routes matched the movement trajectory of fishing vessels. The model also exhibited satisfactory performance, achieving an average AUC of 0.722 ± 0.033, a sensitivity of 0.604, a specificity of 0.834, and a negative predictive value (NPV) of 0.978. In conclusion, the CART rule-guided MaxEnt model, integrating the interpretability of CART and the predictive power of MaxEnt, effectively predicts the spatial distribution of chub mackerel fishing grounds in the northwest Pacific Ocean, providing technical support for fishery management and ecological research.

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Worker exposure to bioaerosols from sludge dewatering facilities: risks and mitigations - Bei-bei Cui; Wajid Ali; Wei-di Wan; Yi-ning Hu; Si-yi Liu; Tian-nuo Lai; Yong-tang Yan; Zhen Hu; Ting-xu Jin; Xiang Li; Zaheer Ahmad Nasir; Frederic Coulon; et al. (Water Research, 2026)

Houpu Sanwu decoction alleviates rat intraperitoneal adhesion by regulating macrophage polarization and inhibiting inflammatory responses - Mei Liu; Quanxin Chen; Yan Cui; Tianming Wang; Qun Li; Zhihang Wu; Richeng Li; Yuan Tang; Haibang Pan (Tissue and Cell, 2026)

The VP1 protein of foot-and-mouth disease virus: Bridging pathogenicity and control strategies - Yize Li; Xiaoyu Ge; Jing Yang; Jiaxuan Li; Wen Cui; Xiaona Wang; Lijie Tang (The Veterinary Journal, 2026)

Epimedium polysaccharide alleviates adenine-induced oligoasthenozoospermia in mice by inhibiting ferroptosis and inflammation through TLR4/NF-κB and SLC7A11/GPX4 axis - Kun-Yang Tang; Wang Ai; Xiao-Cui Jiang; Min Xiao; Yan-Yan Zhou; Xiao-Ming Yu; Shu-Hui Chen; Jing-Ling Zhao (Reproductive Biology, 2026)

Comparison of different machine learning models coupling with logistic regression for landslide susceptibility mapping - Jian Ji; Junhan Deng; Hongzhi Cui; Bin Tong; Xintao Tang; Te Pei (Gondwana Research, 2026)

Adenine and myristic acid from Limosilactobacillus reuteri enhance growth and freeze-drying tolerance of Bifidobacterium bifidum CCFM1167 - Tianyu Shen; Shuyu Guo; Bingyong Mao; Xin Tang; Qiuxiang Zhang; Hongtao Zhang; Qixiao Zhai; Jianxin Zhao; Wei Chen; Shumao Cui (Food Bioscience, 2026)

Bifidobacterium animalis subsp. lactis CCFM1479 synergistically alleviates fatigue in mice with ginsenoside Rb1 - Xin Tang; Jiang Wang; Haorui Ma; Fei Liu; Jin Liu; Qiuxiang Zhang; Jianxin Zhao; Wei Chen; Bingyong Mao; Shumao Cui (Food Bioscience, 2026)

Microwave-assisted synthesis of Cu-doped UiO-66 activated persulfate for tetracycline degradation - Can Cui; Lan Wang; Shaolin Deng; Tianxi Yuan; Yanzi Yang; Minghong Tang; Hangzhou Jiang; Wenyuan Tan (Environmental Research, 2026)

Long-term exposure to fine particulate matter and its constituents, genetic susceptibility, and incident bipolar disorder - Xinru Zhao; Yudiyang Ma; Ning Chen; Lei Zheng; Meiqi Xing; Feipeng Cui; Jianing Wang; Linxi Tang; Yaohua Tian; Peng Xiong; Yu Chen (Environmental Pollution, 2026)

Interpretable machine learning guides rational design of dual-site catalysts for synergistic aerobic oxidation of benzylamine - Zhiming Ma; Shiqiang Liu; Xinxin Wang; Ruizhi Wang; Mengzhou Chang; Chuang Chen; Zijian Wang; Huapeng Cui; Maohong Fan; Lei Wang; Yong Yang; Enling Tang (Chemical Engineering Journal, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

National clusters and carbon emissions based on “N + 3E” framework: insights from global carbon source and sink - Ningxin Cui; Feng Dong; Zhicheng Li; Qingteng Tang (Clean Technologies and Environmental Policy, 2026)

Transcriptional regulator Rv2250c affects isoniazid resistance by down-regulating the expression of efflux pump Rv3728 in Mycobacterium tuberculosis - Hui Wang; Yingying Cui; Guanghui Dang; Jiajun Zhang; Yiyi Tang; Tingting Feng; Xinxin Zang; Ningning Song; Siguo Liu (Archives of Microbiology, 2026)

Adaptive VP1 sites 93 and 97 modulate antigenic evolution and receptor binding of Senecavirus A: Phylogenetic analysis and validation with recombinant viruses - Jing Yang; Zhiliang Zhang; Weijia Sha; Mingyue Peng; Yize Li; Xiaoyu Ge; Jiaxuan Li; Wen Cui; Yanping Jiang; Xiaona Wang; Lijie Tang (Veterinary Microbiology, 2026)

Overcoming gastrointestinal mucosal barriers: Mechanistic innovations and technical advances in mucosal targeting strategies for animal oral vaccines - Meijun Yu; Yue Li; Zhaojun Wang; Ping Han; Yanping Jiang; Wen Cui; Yijing Li; Lijie Tang; Shuo Jia; Hongzhe Zhao; Yingying Ma; Jiaxuan Li; et al. (Veterinary Microbiology, 2026)

Sub-inhibitory tilmicosin promotes horizontal transfer of blaNDM via extracellular vesicles through activation of the zraS/zraR system - Jing Zuo; Di Xie; Qian Chen; Ke Wu; Jian Yang; Yulian Hu; Heting Xu; Yizhi Tang; Changwei Lei; Cui Li; Hongning Wang (Veterinary Microbiology, 2026)

A Joint Maintenance strategy for offshore wind turbines based on multiple opportunity windows and dynamic double thresholds - Jia Fu; Qiushi Cui; Yabo Tang; Jie Gao; Changxin Chen (Ocean Engineering, 2026)

Foliar silicon application enhances rare earth element accumulation in the hyperaccumulator Phytolacca americana - Rui-Qi Zhang; Cui-Ling Huang; Ling-Xiu Zhou; Rong-Liang Qiu; Chong Liu; Antony van der Ent; Jean-Louis Morel; Wen-Shen Liu; Ye-Tao Tang (Journal of Environmental Sciences, 2026)

Sustainable antibiotic degradation in a pH-adaptable heterogeneous electro-Fenton system: Insights into cross-scale mechanism validation - Meiyi Tang; Tao Hou; Hongli Lu; Yutong Xue; Meiqi Ren; Dan Cui (Journal of Environmental Sciences, 2026)

Application of layered double hydroxides (LDHs) derived catalysts for selective catalytic reduction of NOx with NH3 - Tian-yu Lv; Zuo-lin Cui; Rui-tang Guo (Fuel, 2026)

Effects of ultrasound duration and microwave temperature control synergistic on antioxidant metabolite libraries and mechanistic pathways in Camellia oil - Wenwei Wang; Shiman Sun; Qingyang Li; Maokai Cui; Lingyuan Zhou; Menghao Du; Xuezhi Fang; Fubin Tang; Yihua Liu (Food Chemistry, 2026)

Synergistic regulation of thiourea and SDS on the structure of H2TiO3 and its efficient lithium extraction mechanism - Changxiang Yang; Kaiyang Zheng; Liang Shi; Shilin Zhang; Jianmin Yang; Shuyan Xiong; Lei Wang; Shuhan Cui; Aidong Tang; Jinlong Jiang (Chemical Engineering Journal, 2026)

A core-shell fiber membrane with synergistic radiative cooling and thermal buffering for all-weather personal comfort - Xiaohong Wu; Akbar Bashir; Chak-Yin Tang; Gary Chi-Pong Tsui; Ziqi Li; Nanhao Chen; Yichi Zhang; Yan Chen; Jie Cui; Juncheng Zhuang; Chen Liu; Yuanyuan Li; et al. (Chemical Engineering Journal, 2026)

Asymmetrical infrared metasurfaces for augmented marine microplastic detection - Shuming Zhang; Dongyu Cui; Yihan Tang; Qikun Yang; Zhijuan Su; Wei Huang; Faheng Zang (Chemical Engineering Journal, 2026)

Negative edge effects on forest carbon stocks in China: an estimate based on inventory data - Zeng Cui; Jinlong Chen; Zhiyao Tang (Science China Life Sciences, 2026)

Lacticaseibacillus Paracasei CCFM1350 Demonstrates Potentials in Hair Growth and Treating Alopecia in Mice - Yuhan Guo; Tongtong Zhang; Xin Tang; Bingyong Mao; Qiuxiang Zhang; Jianxin Zhao; Shumao Cui (Probiotics and Antimicrobial Proteins, 2026)

Blackwellomyces napialus (Cordycipitaceae, Hypocreales), a Novel Species Parasitic on Napialus hunanensis from China - Jin-Long Jia; Cui-Yuan Wei; Mei Tang; Zhu-Yu Cheng; Ya-Nan Wang; Zhu-Liang Yang; Gang Deng; Yuan-Bing Wang (Current Microbiology, 2026)

Long-term manure addition restores soil microbial network complexity disrupted by chemical fertilization across 3 m soil profiles - Yiwei Shang; Xiaotong Tang; Faisal Zaman; Xingjie Wu; Yifan Guo; Duo Liu; Jingjing Peng; Zhenling Cui (Agriculture, Ecosystems & Environment, 2026)

Synthesis and Characterization of a Cd (II) Coordination Compound with Efficient and Selective Detection of Cu²⁺, Cr₂O₇²⁻ and MnO₄²⁻ - Xinxin Yi; Xin Li; Shilong Song; Jiyue Tang; Minghe Cui; Xiuyan Wang (Journal of Fluorescence, 2026)

Metagenomic insights into the trophic gradient influence on nitrogen cycling microbiomes in plateau lakes - Sicen Yan; Hafiz Adeel Ahmad; Yongchao Xie; Shufeng Liu; Jiang Wu; Jiaxin Cui; Bo Yang; Lei Su; Tengda Ding; Tang Liu (Marine Pollution Bulletin, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Revisit the improvement of coagulation pretreatment on ozonation performance: The critical roles of HO• and O3 for effluent organic matter transformation and micropollutant degradation - Rui Hu; Hao-Tong Zheng; Boxi Tang; Jialing Tu; Yu-Hong Cui; Xuedong Zhai; Gang Wen; Zheng-Qian Liu (Journal of Cleaner Production, 2026)

Enhanced performance of Cr-doped CeMn/Hβ catalysts for complete oxidation of chlorobenzene-containing volatile organic compounds and their mechanistic insights - Kang Zhou; Shun Wang; Yunrui Zhao; Wei Zhao; Hui Shi; Zhaoyang Fei; Xian Chen; Jihai Tang; Mifen Cui; Xu Qiao; Ming Xia (Journal of Environmental Chemical Engineering, 2026)

Encapsulation of probiotics based on electrostatic interaction and layer-by-layer assembly method to enhance environmental resistance - Xuewu Liu; Bingyong Mao; Xin Tang; Qiuxiang Zhang; Qixiao Zhai; Jianxin Zhao; Wei Chen; Shumao Cui (Food Hydrocolloids, 2026)

P2X7 receptor-mediated cGAS-STING pathway activation underlies chronic stress-induced depressive-like behaviors - Xi-Meng He; Yi Zhang; Cui-Yuan Chen; Yu-Li Han Tang; Xuan Li (Purinergic Signalling, 2026)

Streptococcus salivarius CCFM1416 Modulates Oral Immunity via IL-17/IKBζ and Combats Candida albicans Infection - Lijiang Ding; Yanxiao Zhang; Qiuxiang Zhang; Xin Tang; Yueyan Wang; Bingyong Mao; Jianxin Zhao; Shumao Cui (Probiotics and Antimicrobial Proteins, 2026)

Accelerating multi-GNSS and multi-frequency PPP-AR convergence using global operational NWM forecasts - Shi Du; Jungang Wang; Bobin Cui; Longjiang Tang; Xinghan Chen; Guanwen Huang; Harald Schuh (GPS Solutions, 2026)
Precise point positioning with ambiguity resolution (PPP-AR) provides globally available centimeter-level positioning, but its convergence time remains a limiting factor for time-critical applications. One important contributor to slow convergence is short-term mismodeling of the zenith wet delay (ZWD), which affects the float ambiguity estimates and delays integer fixing. Numerical weather models (NWMs) offer physically realistic, globally consistent tropospheric predictions that can mitigate this issue. This study investigates the use of operational Global Forecast System (GFS) forecasts to augment real-time PPP-AR through adaptive ZWD accuracy constraints. Using ZTD data from nearly 400 IGS stations in 2024, we analyze the performance of GFS-derived delays and identify a clear latitudinal dependence, with RMS differences reaching about 2 cm in tropical regions and dropping to below 1 cm at high latitudes. Based on these characteristics, a latitude-dependent accuracy model is constructed and applied to dual- and triple-frequency multi-GNSS PPP-AR for 223 MGEX stations across four representative months. The results demonstrate that GFS-derived tropospheric augmentation reduces PPP-AR convergence times by 20–40% globally, with larger improvements in summer and at mid- to high latitudes. These seasonal and latitudinal patterns arise from atmospheric variability: summer months exhibit stronger short-term water-vapor fluctuations that amplify the benefit of external ZWD constraints, while mid- and high-latitude regions generally show more stable tropospheric conditions, allowing NWM-derived delays to be more accurate than in the tropics. In addition to convergence, the augmentation also improves the time to first fix (TTFF), defined as the first epoch at which ambiguities remain fixed for ten consecutive epochs, with typical reductions of about one minute and relative improvements of roughly 15–25%, particularly in mid- and high-latitude regions. After convergence, the augmentation has minimal impact on positioning accuracy. These findings demonstrate that operational GFS forecasts can serve as an effective global source of tropospheric information for accelerating PPP-AR, offering a practical pathway toward improved performance in time-sensitive applications.

High-loading single-atom photocatalysts for high-selectivity conversion of CO2 to ethanol - Long-Shuai Zhang; Feiyao Wu; Shenrui Liang; Qianqian Tang; Hui Li; Huang Zhou; Fanqi Meng; Xunheng Jiang; Haiyan Liu; Qing Sun; Meifeng Wu; Yitao Cui; et al. (Science Bulletin, 2026)

Edge effects on forest dynamics in China from 2000 to 2020: Evidence from satellite remote sensing - Jinlong Chen; Zeng Cui; Zhiyao Tang (Remote Sensing of Environment, 2026)

BmTrpA1-Mediated ILP/AKT/FOXO signaling Underlies Temperature-Dependent diapause in Silkworms, Bombyx mori - Yizhong Zhang; Haoping She; Shanshan Wang; Qianyi Cui; Wenjie Zhang; Shunming Tang; Xingjia Shen; Juan Zhu (Journal of Insect Physiology, 2026)

Association of plasma metals with total burden of cerebral small vessel disease: Evidence from China - Lei Zheng; Hao-Long Zeng; Ying Hui; Feipeng Cui; Yudiyang Ma; Jianing Wang; Linxi Tang; Meiqi Xing; Shuohua Chen; Liming Cheng; Shouling Wu; Zhenchang Wang; et al. (Journal of Hazardous Materials, 2026)

The influence of fulvic acid on molybdenum bioavailability assessed by Caenorhabditis elegans - Qian Huang; Lingfang Cui; Zhixin Song; Ming Li; Chao Zhang; Wenzhong Tang; Jianyin Huang (Journal of Environmental Management, 2026)

Collagen type XV regulation via MMP2-dependent degradation governs ovarian development in the rice stem borer, Chilo suppressalis - Yue Li; Suijie Kuang; Yan Tang; Zhuotian Yao; Yechen Pan; Ziren Zang; Yang Cui; Hongshuai Gao; Lin Qiu; Yansong Xiao; Tin Liu; Qi Su; et al. (Insect Biochemistry and Molecular Biology, 2026)

Twinned structure–enhanced S-scheme heterojunction in Zn0.8Cd0.2@g-C3N4 for efficient CO2 photocatalytic reduction - Ming-yang Liu; Hao-wen Zhu; Qing-shan Wang; Cong Liu; Heng-fei Cui; Jun-ying Tang; Rui-tang Guo (Fuel, 2026)

Visualization study on combustion characteristics of direct-injection methanol ignited by micro-injection diesel in a hydrogen-rich syngas atmosphere - Yuanyou Tang; Wuqiang Long; Zhizhuo Dai; Zechuan Cui; Yang Wang; Ge Xiao; Pengbo Dong; Hua Tian (Fuel, 2026)

The unsaturated fatty acid of the cell membrane and the accumulation of intracellular glutamic acid as key determinants of freeze-drying tolerance in Bifidobacterium bifidum - Shuyu Guo; Wenrui Zhou; Bingyong Mao; Xin Tang; Qiuxiang Zhang; Jianxin Zhao; Wei Chen; Shumao Cui (Food Research International, 2026)

Aroma formation in peptide-involved Maillard reaction: mechanistic insights, key factors, and control strategies - Tong Zhou; Heping Cui; Xinjing Li; Chen Huang; Guzalnur Askar; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Chemistry, 2026)

Influence of corrosion damage on the fatigue response of Q500qENH weathering steel T-joint welds - Kun Tang; Chuang Cui; Peng Zhang; Haochi Wei; Yan Ma; Qinghua Zhang (Engineering Structures, 2026)

Territorial spatial carbon balance governance from a spatially refined perspective: Incorporating sub-regional differences in spatial driving effects into zoning regulation - Yifei Xu; Mingxiang Wang; Wei Tang; Sinan Li; Wenqi Ai; Wenjing Xu; Dan Xu; Chang Liu; Jiarui Sun; Weixin Cui (Environmental Impact Assessment Review, 2026)

Machine learning unlocks multi-metal synergy in Prussian blue cathodes toward ultralow-cost sodium-ion grid storage - Hong Qian; Zhong Tang; Yuhao Liu; Xiaofei Hou; Xiangyang Liu; Binxia Yuan; Haoyang Cui (Chemical Engineering Journal, 2026)

Temporal and Spatial Variability in Soil Dissolved Organic Matter Under Different land-use Types in Southwest China - Zhixiang Sun; Junfang Cui; Xiangyu Tang; Lei Chen; Jialiang Tang (Journal of Soil Science and Plant Nutrition, 2026)

Exploring potential biomarkers and constructing prediction models of osimertinib based on a retrospective study - Lili Cui; Mao Tang; SuLi Liang; Chen Bu; Yunlei Yun; Shouhong Gao; Zhipeng Wang; Xia Tao (European Journal of Clinical Pharmacology, 2026)

Symbiotic interaction of Chlorella sp. and Shinella sp. for enhanced dissolved organic matter removal from sterilized mixed wastewater - Rumeng Lu; Qiaoyun Huang; Yunpu Wang; Xian Cui; Zhigang Yu; Naif Abdullah Al-Dhabi; Xiang Wang; Roger Ruan; Wangwang Tang; Zihan Li; Ting Zhou; Yuhuan Liu; et al. (Algal Research, 2026)

A provenance study of turquoise artifacts at the Sanxingdui site in Sichuan, China - Zeya Shang; Jianfeng Cui; Honglin Ran; Chong Wang; Zhenbin Xie; Yu Lei; Fei Tang; Dengyi Zhang; Haichao Li (Archaeological and Anthropological Sciences, 2026)

TMEM158-mediated TGF-β signaling pathway modulates the sensitivity of TP53-deficient osteosarcoma to USP14 inhibitors - Zi-Yu Chen; Miersalijiang Yasen; Song-Yao Jiang; Zi-Yi Ye; Qin-Xin Yang; Cui-Ni Lu; Yi Shi; Xin-Yun Liu; Ting-Ting Du; Xiao-Mei Tang; Da Fu; Yu-Shui Ma; et al. (Molecular and Cellular Biochemistry, 2026)

Dynamic response and failure characteristics of twin-arch tunnels reinforced with steel strips under pulse-like ground motions: Insights from shaking table tests - Langzhou Tang; Li Yu; Zexing Li; Zhen Cui; Yang Xiao (Tunnelling and Underground Space Technology, 2026)

Machine learning reveals molecular substructure drivers of organic contaminant translocation in crops - Haodong Lang; Yang Cui; Wen Liu; Shanshan Tang; Wei Gao; Chengyu Zhai; Jing Lu; Yawei Wang (Science of The Total Environment, 2026)

An mRNA microsphere vaccine inhibiting overactivation of DNA sensing mechanisms - Fangke Zhang; Jiancheng Zheng; Fei Wang; Yaping Zhuang; Yunkai Tang; Juan Wang; Yawei Du; Wei-Li Zhao; Min Lu; Weiguo Hu; Wenguo Cui (Science Bulletin, 2026)

Intelligent control for food waste composting using observation–assessment–decision–action cycles: From technical landscape to economic stability analysis - Jufei Wang; Xuesong Peng; Wenbin Tang; Xueru Zhu; Chao Li; Hanpeng Liao; Chen Liu; Wuxiong Weng; Zheming Cui; Shuhe Zheng; Hua Li (Journal of Environmental Management, 2026)

Immiscibility-assisted distillation process and ANN-based control strategy for efficient recycling of ternary mixture in 2-butoxyethanol production - Guilin Wen; Yumeng Wang; Wenxin Wang; Guohua Tang; Xin Li; Peizhe Cui; Zhaoyou Zhu; Yinglong Wang; Wei Lu (Journal of Environmental Chemical Engineering, 2026)

Globally synchronous acceleration of soil formation approximately 12,000 years ago - Licheng Guo; Qiaowen Zhang; Haozhong Xue; Shangfa Xiong; Shiling Yang; Zihua Tang; Linlin Cui; Jingyi Cui; Yongda Wang; Shihao Zhang (Global and Planetary Change, 2026)

Effect of the typical coal ash-analogous minerals on the migration of heavy metals during coal combustion - Mengzhu Yu; Jingwen Chen; Zhicheng Zhu; Yaji Huang; Pu Yang; Hao Xu; Menghui Li; Lu Tang; Xihui Fan; Yifan Xu; Dongxu Cui (Fuel, 2026)

MXene-supported MOF-derived multicore ZrSe2@MnSe2 complex structure for high-rate and long-cycle-life supercapacitors - Yuhan Cui; Jing Sun; Yining Wang; Lijie Zhao; Yanjie Lv; Yuzhe Tang; Wenxi Zhang; Zhongmin Su (Fuel, 2026)

A generalized probabilistic method for fatigue life prediction of butt-welded joints with multiple cracks based on equivalent initial flaw size distribution - Yan Ma; Chuang Cui; Kun Tang; Yong Xia; Qinghua Zhang; Wulve Lao (Engineering Structures, 2026)

The efficient ethane oxychlorination to ethylene on Cu Zn LDO through confinement-interface synergy - Kunhao Bi; Baosen Tang; Wei Cui; Shaoqing Qu; Weizhen Sun; Ling Zhao (Chemical Engineering Journal, 2026)

Iron and platinum alternating active sites for efficient photocatalytic overall water splitting - Yanfei Fan; Yan Liu; Ying Liang; Kang Chen; Qingqing Li; Dongxu Pan; Shiqiu Zhang; Guanwei Cui; Bo Tang (Chemical Engineering Journal, 2026)

Structural analysis and immunomodulatory properties of lipopolysaccharide from the gut symbiont Phocaeicola dorei - Zhiying Lin; Huazhi Tang; Limei Che; Mingsheng Chen; Zixin Ye; Xiaotong Yang; Lin Sun; Kevin H. Mayo; Guihua Tai; Liangnan Cui; Yifa Zhou (Carbohydrate Polymers, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

High lytic activity of endolysin LysDCp1 from phage DCp1 against Clostridium perfringens and biofilms - Ruixue Ma; Zhaohui Tang; Jianchao Zhao; Ziyang Li; Yanshun Cui; Can Zhang; Huiying Ren; Shouzhen Xu; Ling Zou; Jing Ma; Jianbao Dong; Xiaojing Hao; et al. (Veterinary Research Communications, 2026)

Integrated ionospheric delay processing strategy for PPP-RTK: improving uncertainty estimation accuracy and mitigating delay errors - Shi Du; Bobin Cui; Jungang Wang; Longjiang Tang; Guanwen Huang; Harald Schuh (GPS Solutions, 2026)

Development of a high-throughput LLE-UPLC-QqQ-MS/MS method and comprehensive profiling of urinary steroid hormones in Chinese elderly adults - Xiao Ma; Huimin Ren; Li Zhao; Xiaojie Guo; Jiran Zhang; Juan Liu; Xiaona Wang; Mengyao Wang; Yifu Lu; Shilu Tong; Hongyang Cui; Hong Chang; et al. (Analytica Chimica Acta, 2026)

Virgibacillus aidingensis sp. nov., a bacterium isolated from a hypersaline sediment in Xinjiang Province, North-west China - Li Yang; Hua-Wei Huang; Juan Wang; Cui-Ping Miao; Yi-Qing Li; Xiang-Tao Cen; Li-Xing Zhao; Wen-Yong Zhu; Shu-Kun Tang (Antonie van Leeuwenhoek, 2026)

Current progress in the ginger oleoresin: bioactivities, extraction and encapsulation technologies - Chen Huang; Heping Cui; Xinjing Li; Guzalnur Askar; Jingyang Yu; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Critical Reviews in Food Science and Nutrition, 2026)

Disasters caused by underground water pipe leakage in Chinese cities: Failure modes, influencing factors and prevention countermeasures - Jiawei Xu; Jinxing Lai; Junling Qiu; Haidong Jiang; Hao Sun; Jinzhao Tang; Guanhua Cui (Tunnelling and Underground Space Technology, 2026)

Cytochalasins from the marine-derived fungus Acremonium implicatum DFFSCS001 and their anti-inflammatory activities - Yu-Qian Tang; Chu-Xing Liang; Hui Cui; Xiao Liang; Shu-Hua Qi (Phytochemistry, 2026)

Bearing characteristics of tripod bucket foundation for offshore wind turbines under horizontal cyclic loading - Kunpeng Wang; Penghui Tang; Chunyi Cui; Hailong Liu (Ocean Engineering, 2026)

Preparation of iron oxide/montmorillonite catalyst and its green remediation performance of pyrene-contaminated soil - Yun-rui Zhao; Kang Zhou; Xiao-xiao Qi; Hui Shi; Jihai Tang; Mifen Cui; Xu Qiao; Ming Xia (Journal of Water Process Engineering, 2026)

Association between prenatal PFAS exposure and catch-up growth in children born with adverse outcomes: evidence from a prospective cohort study - Su-Qin Tan; Yan-Xi Li; Shao-Ya Huang; Shen-Pan Li; Qiong Zhang; Cui-Lan Tang; Ying-Chao Ye; Guang-Hui Dong; Jian Chen; Dan Cai; Xiao-Wen Zeng (Journal of Hazardous Materials, 2026)

RAD51 m6A and PARylation modification orchestrate benzene-induced haematological toxicity - Lin Chen; Fengzhen Cui; Han Li; YuTao Zeng; Zhongming Wu; Weitian Chen; Qiaosheng Wen; Chunnian You; Yunqiang Xu; Lei Sun; Mingwei Sun; Qian Sun; et al. (Journal of Hazardous Materials, 2026)

Plant-to-camera enabled 3D morphological reconstruction: A high-fidelity approach for plant phenotyping - Aobo Du; Yinghua Wang; Xianglong Shi; Chenxi Cui; Yan Tang; Kai Xie; Jiashi Wang; Jinbao Liu; Wanneng Yang; Peng Song; Ruifang Zhai (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Micro-macro progressive deterioration patterns of water-immersed coal: Non-uniform surface and pore damage - Bo Li; Zhen Shi; Zhenfeng Wang; Junxiang Zhang; Junqi Cui; Yaocai Tang; Peiliang Ren (Fuel, 2026)

Recent progress on Cu-based MOF electrocatalysts for CO2 reduction - Heng-fei Cui; Xiao-jing Liu; Cong Liu; Hao-wen Zhu; Ming-yang Liu; Rui-tang Guo (Fuel, 2026)

Low-cost supported ionic liquid [TETA][HCOO]/X-5: Adsorption and regeneration performance for CO2 capture from flue gas - Chengyu Han; Chuanjia Qi; Ying Ming; Jiyun Tang; Yong Dong; Lin Cui (Fuel, 2026)

Exogenous cysteine oxidation induced secondary browning of light-colored glycine-xylose Maillard reaction products through promoted formation of glyoxal and methylglyoxal - Qian Hou; Tong Zhou; Xinjing Li; Cuimin Hua; Heping Cui; Foxin Zhang; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Chemistry, 2026)

Improving essential oil extraction and characteristic aroma retention of black pepper through efficient cell rupture and enzymatic hydrolysis - Xiaozhen Sun; Heping Cui; Tong Zhou; Yishun Yao; Jianzeng Liu; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho; Wenjian Yang (Food Bioscience, 2026)

Lactiplantibacillus plantarum CCFM1296 postbiotics ameliorate skin aging in mice associated with enhanced endogenous hyaluronic acid synthesis - Xin Tang; Haobo Cui; Qing Hong; Bingyong Mao; Qiuxiang Zhang; Jianxin Zhao; Wei Chen; Shumao Cui; Zhenmin Liu (Food Bioscience, 2026)

Comparative toxicological effects of traditional and biodegradable microplastics on pepper (Capsicum annuum L.): physiological and metabolomic insights - Rongchao Yang; Mingzhu Guan; Youyang Fu; Xiao Yang; Mangu Hu; Yilan Cui; Xinming Tang; Yueqin Zhang (Environmental Research, 2026)

Synergistic enhancement of breakdown and dielectric properties in dielectric energy storage polymer via incorporating TiO2-loaded Al2O3 nanotube featuring “cable-tie-like” composite structure - Guanfei Liu; Shuimiao Xia; Xuyuan Fan; Qingyang Tang; Hongzhi Cui; Hongqiang Wang; Zhicheng Shi (Chemical Engineering Journal, 2026)

VOCs-driven ozone extremes during dry and wet heatwaves in the Jiangsu–Shandong–Henan–Anhui Boundary: Integrating meteorological forcings and SHAP interpretation - Chaolong Wang; Sufan Zhang; Yisheng Zhang; Shanshan Cui; Xiaofei Qin; Alex Guenther; Jianhui Bai; Dasa Gu; Jinhua Du; Jingchao Tang; Wanxiang Yao; Ming Wang; et al. (Atmospheric Research, 2026)

Assessing Spatiotemporal Variability in Soil Moisture under a Changing Climate Using Hydrological Models in Hilly Landscapes - Muhammad Waseem Rasheed; Junfang Cui; Jialiang Tang; Abid Sarwar; Mostafa Moradzadeh; Muhammad Faheem (Water Resources Management, 2026)

Hydrogen as a Potential Modulator: Implications for Mast Cell-Sleep-Wake Rhythm-Melatonin Interactions in Sleep Disorders - Chao Cui; Wenjie Tang; Yifeng Guo; Jingfei Shi; Yuhong Gao; Haixu Chen; Youzhen Wei (Molecular Neurobiology, 2026)

The Role of Toll-like Receptor 3 Signaling in Cognitive Impairment Induced by Propofol Addiction - Jiahui Wu; Liyun Deng; Rui Gao; Ying Cui; Yidan Tang; Changliang Liu; Tao Zhu; Chan Chen (Molecular Neurobiology, 2026)

Molecular phylogeography and population history of Saccostrea mordax based on mitochondrial DNA - Zeyu Tang; Cui Li; Guochen Zang; Zhenqiang Liu; Zongmei Cui; Haiyan Wang (Journal of Oceanology and Limnology, 2026)

Systematic Review and Meta-Analysis on Heavy Metals and Trace Elements in Mild Cognitive Impairment - Yaxin Dong; Lu Ren; TianRan Tang; Xinyi Zhang; Dan Han; Yingyi Luo; Liqiang Wang; Zonghui Cui; Sheng Ji; Jianheng Zheng; Ying Qing (Biological Trace Element Research, 2025)

Rare earth element hyperaccumulation in vascular plants: Occurrence, mechanisms, and applications - Ruo-Rong Liu; Cui-Ling Huang; Hong-Xiang Zheng; Chong Liu; Rui-Qi Zhang; Yue Cao; Antony van der Ent; Can-Die Xie; Wen-Shen Liu; Jean Louis Morel; Catherine Sirguey; Damien Blaudez; et al. (Critical Reviews in Environmental Science and Technology, 2025)

Impact of low-emission driving behavior on brake wear PM emissions: insights from a real-world evaluation - Ye Liu; Tangjian Wei; Haibo Chen; Sijin Wu; Yili (Kelly) Tang; Zhiyuan Lin; David Watling; Jingwen Yao; Nansong Yue; Chenxi Wang; Dingsong Cui; Dimitris Margaritis (Transportation Research Part D: Transport and Environment, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Temporal and spatial heterogeneity of antarctic krill abundance in relation to seawater temperature - Xuesen Cui; Jiasheng Li; Fenghua Tang; Guoqing Zhao; Yumei Wu; Heng Zhang (Regional Studies in Marine Science, 2025)

Biomass-derived Fe active sites on TiO2: Dual-functional charge mediation and pathway regulation for efficient photocatalytic nitrogen oxide complete oxidation - Jiaqi Wang; Aijiang Yang; Songxia Wang; Yin Tang; Yan Li; Wen Cui (Journal of Environmental Chemical Engineering, 2025)

Numerical insights into thermal-hydraulic-mechanical-damage (THMD) fields evolution over hydraulic fracturing in hot dry rock - Xiaotian Wu; Yingchun Li; Tianjiao Li; Guanglei Cui; Chun'an Tang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Mechanism of high glycine dosage promoting degradation and oxidation of sorbitol for browning - Xiaotian Huang; Heping Cui; Khizar Hayat; Jingyang Yu; Ahmad Mohammad Salamatullah; Shuqin Xia; Chi-Tang Ho (Food Research International, 2025)

Silane-modified starch reinforced chitosan/lignosulfonate composite film for grape preservation - Xijiao Bian; Jiaqian Cui; Junwei Tang; Jungang Jiang; Yifan Zhang; Guowen Zhou; Lei Wang (Food Research International, 2025)

Identification of characteristic aroma compounds in blanched garlic through multidimensional analysis and improvement of sensory quality via cysteine-assisted mild blanching - Mengzhuo Wang; Xiaomin Wang; Yishun Yao; Jianzeng Liu; Heping Cui; Wenjian Yang; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Research International, 2025)

Quercetin alleviates ethanol-induced hepatocyte senescence by interacting with glycinamide ribonucleotide transformylase - Chen Huimin; Peng Shufen; Cui Zhaoyu; Liu Jiaxin; Chen Li; Yin Xingzhu; Wu Bangfu; Zhao Ying; Wang Yu; Mo Li; Liang Chanhua; Li Dongyan; et al. (Food Research International, 2025)

Integrated multi-omics and network pharmacology reveals antioxidant-active metabolites and health benefits of Camellia oleifera seed oil - Lingyuan Zhou; Jiarong She; Qingyang Li; Qiong Zheng; Jie Yang; Maokai Cui; Tiantian Chen; Shiman Sun; Fubin Tang; Yihua Liu (Food Chemistry, 2025)

Erratum to “Dynamic changes in flavonoid profiles and their bioactive properties during rice yellowing” [Food Chem. 492(Part 3) (2025) 145539] - Jinguang Liu; Caiyun Tang; Yanan Qv; Xiao Zheng; Yawen Wang; Mixue Yan; Xuejiao Li; Yu Cui; Yilun Chen; Yuqian Liu (Food Chemistry, 2025)

Electrostatic spray drying enhances transferrin hydrophilicity for improved rosmarinic acid binding: Insights into biological activity and molecular mechanism - Ru-yi Zhang; Zhi-shuo Zhang; Ting-ting Tang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Yan-jun Yang; Cui-hua Chang (Food Chemistry, 2025)

Stereoselectivity during enzymatic oxidation of catechins and their products' characteristic in taste receptors and color properties - Zekai Wang; Qing-Qing Cao; Mingchun Wen; Yahui Li; Yuqing Cui; Zisheng Han; Xiaochun Wan; Chi-Tang Ho; Yong-Quan Xu; Liang Zhang (Food Chemistry, 2025)

Controlled formation of characteristic aroma compounds induced by added seasonings during electromagnetic cooking of braised pork: Weakened lipid oxidation and accelerated Maillard reaction - Xiaomin Wang; Yishun Yao; Jingyang Yu; Heping Cui; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho; Ahmad Mohammad Salamatullah (Food Chemistry, 2025)

Quercetin alleviates oleic acid-induced acne in mice: Integrated analysis of skin lipid metabolism, gut microbiota and serum metabolomics - Jie Li; Bingyong Mao; Xin Tang; Qiuxiang Zhang; Jianxin Zhao; Hao Zhang; Shumao Cui (Food Bioscience, 2025)

Associations between residential greenness exposure during pregnancy and bone mineral density in early childhood - Yibing Zhu; Linxi Tang; Yudiyang Ma; Bin Sun; Haibo Li; Feipeng Cui; Jingmin Guo; Yaohua Tian; Chong Miao (Environmental Research, 2025)

Piperazine concentration-driven effect fabricated NF membrane with ambidextrous selectivity for SO42−/Cl− and Mg2+/Na+: Mechanism and efficient water purification - Hailin Chang; Shilei Fu; Ziao Zhang; Yating Hu; Zijian Cui; Jun Ma; Kexin Hou; Xiaobin Tang; Guibai Li; Heng Liang (Desalination, 2025)

Two-stage inoculation with Comamonas testosteroni modulates bacterial community and enhances PAHs biodegradation in contaminated soil co-composting - Fangzhi Jiang; Meiqi Li; Qi Liu; Chang Xu; Pengfei Tang; Yufeng Zhao; Jizhe Cui; Cailing Qiu; Qian Lu (Chemical Engineering Journal, 2025)

A 3D porous AgNWs/graphene/PDMS sensor enabling multifunctional applications for gesture recognition and health monitoring - Li Wang; Yaxin Wang; Shaoqi He; Jiahong Wen; Qifeng Du; Yongjun Zhang; Wenting Zhang; Renxian Gao; Kun Zhang; Rufei Cui; Fengyi Zhang; Xiqiang Zhong; et al. (Chemical Engineering Journal, 2025)

Structure-guided valorization of microalgal biomass for renewable and versatile applications - Ziyang Wang; Jiarong Tian; Yunuo Wang; Yu Tang; Shaoqing Cui (Bioresource Technology, 2025)

Bacterial viability retention in probiotic foods: a review - Xuewu Liu; Bingyong Mao; Xin Tang; Qiuxiang Zhang; Jianxin Zhao; Wei Chen; Shumao Cui (Critical Reviews in Food Science and Nutrition, 2025)

Association of Serum Neurofilament Light and Glial Fibrillary Acidic Protein with Cerebral Small Vessel Disease in Nondemented Middle-to-Old Aged Population - Xiao-Hong Huang; Feng Gao; Jing Yuan; Ding-Ding Zhang; Mei-Jun Shu; Fei-Fei Zhai; Fei Han; Ming-Yu Tang; Ming-Li Li; Li-Xin Zhou; Jun Ni; Ming Yao; et al. (Translational Stroke Research, 2025)

BS-D275: A novel locus on the chromosome arm 2DS governing branched spike development in wheat - Yunfeng Qu; Yongkang Ren; Jinghuang Hu; Yi Liu; Dan Qiu; Yahui Li; Qiuhong Wu; Miao He; Qing Guo; Yu Sun; Wenze Yan; Zhaohui Tang; et al. (Theoretical and Applied Genetics, 2025)

Unraveling the potential mechanism and prognostic value of pentose phosphate pathway in hepatocellular carcinoma: a comprehensive analysis integrating bulk transcriptomics and single-cell sequencing data - Bin Li; Tao Zeng; Cui Chen; Yuankai Wu; Shuying Huang; Jing Deng; Jiahui Pang; Xiang Cai; Yuxi Lin; Yina Sun; Yutian Chong; Xinhua Li; et al. (Functional & Integrative Genomics, 2025)

A combination strategy of HPLC and boric acid modified β-CD polymer for super-efficiently separating chiral substances with O/N atoms in chiral and/or adjacent carbons - Xiaoqian Yuan; Yuchen Cui; Yaqin Nan; Ruijun Tang; Xinru Wang; Yanmei Xu; Xinghua Jin; Yiwen Wang; Ding Cheng; Youxin Li (Analytica Chimica Acta, 2025)

Modulation of greenhouse gas emissions and soil organic carbon in rice paddies through various crop rotation systems combined with water-saving irrigation: Insights into soil bacterial composition and functional alterations - Ligong Peng; Sicheng Deng; Wentao Yi; Yizhu Wu; Baoling Cui; Yingying Zhang; Xiangbin Yao; Xuechan Zhang; Hong Yang; Xiangru Tang (Agriculture, Ecosystems & Environment, 2025)

Construction and Comparison of Different Models to Forecast Central Fishing Grounds for Trawl Fishery Targeting Argentine Shortfin Squid (Illex argentinus) in the Southwest Atlantic - Chen Shang; Haibin Han; Keji Jiang; Yongchuang Shi; Wei Fan; Fenghua Tang; Heng Zhang; Xuesen Cui (Fishes, 2025)
The abundant Argentine shortfin squid resource plays a key role in the Patagonian Large Marine Ecosystem, the Polar Frontal Zone Ecosystem, and the South Atlantic Subtropical Gyre Ecosystem. In this article, we analyzed the annual and monthly changes in catch per unit effort (CPUE) of Argentine shortfin squid with a spatial resolution of 0.25° × 0.25° and constructed three ensemble learning and two deep learning fishing grounds forecasting models using catch information and spatial–temporal and marine environmental data. The results of the study were as follows: 1. From 2016 to 2021, Argentine shortfin squid in the Southwest Atlantic experienced notable interannual fluctuations, with the resource showing an increase and then remaining stable from 2016 to 2018, a decline in 2019, and a substantial increase from 2020 to 2021. Seasonally, CPUE was low from November to January, rose significantly from February to May, and declined in June; 2. The XGBoost model had the best overall performance among the three tree models, achieving an average of 68.86% accuracy, 70.19% F1-score; 3. In the 2021 actual production data validation, the Fusion ResNet18 model achieved an average production data accuracy of 74.47%, F1-score of 73.85%; the Fusion 3DResNet18 model achieved an average production data accuracy of 81.27%, F1-score of 82.43%. This indicates that convolutional neural networks, particularly 3D versions, are more suitable than decision tree-based ensemble models for predicting Argentine shortfin squid fishing grounds. Highly accurate fishing grounds forecasts help enterprises save production costs while providing some reference for the sustainable development of fishery resources.

Pore-Structure-Controlled Acoustic Characteristics for Predicting Shallow Gas Distribution in Polar Offshore Drilling - Lei Li; Li He; Ying Zhao; Yu Song; Shiming Wei; Guojing Zhu; Qingying Tang; Tiancong Cui (Journal of Marine Science and Engineering, 2025)
Shallow gas drilling in polar seas poses severe geological hazards, particularly unexpected eruptions that threaten platform safety and the marine environment. Accurate prediction of shallow gas occurrence and eruption risk is therefore essential for safe deep-water operations. However, previous studies seldom considered the coupled effects of gas pressure and pore-structure evolution on acoustic wave velocity, leading to deviations in hazard assessment. In this study, laboratory experiments and numerical simulations were conducted to clarify these mechanisms. Results revealed a non-monotonic relationship between porosity and P-wave velocity in shallow gas-bearing sediments: P-wave velocity decreases with increasing porosity at low porosity levels but increases beyond a critical threshold. This is attributed to changes in particle interactions and cementation that enhance the shear modulus. The inflection porosity for shallow gas (78%) highlights the diagnostic role of pore-structure evolution in predicting shallow gas distribution. A mathematical correlation between P-wave velocity and formation pressure was further established, and MP-PIC simulations showed that higher pressure coefficients significantly accelerate eruption rates, with a 0.1 increase in the pressure coefficient raising the instantaneous eruption velocity by 5.27 m3/min. Based on these findings, a quantitative evaluation method was developed to assess shallow gas hazard risk, providing engineering guidance for site selection and real-time risk prediction, and contributing to safer offshore drilling and ecological protection in polar environments.

Sub-inhibitory gentamicin promotes extracellular vesicles biogenesis and blaNDM dissemination in carbapenem-resistant Escherichia coli via mrdA/mrdB pathway - Jinpeng Li; Jing Zuo; Heting Xu; Jian Yang; Yulian Hu; Yun Han; Yizhi Tang; Changwei Lei; Cui Li; Hongning Wang (Veterinary Microbiology, 2025)

Dammarane triterpenoids with anti-inflammatory and promoting glucose uptake activities from the leaves of Cyclocarya paliurus - Xiaoqin Liang; Qingfang Zheng; Biqun Zou; Yanqin Li; Liwei Pan; Chenyang Ren; Jiwen Xin; Bo Yang; Ruiyun Yang; Weifeng Xu; Chaowen He; Yanling Cui; et al. (Phytochemistry, 2025)

Nonlinear trajectory tracking control of UVMS with compositing fuzzy disturbance observer and robust state-dependent Riccati equation - Qirong Tang; Yuanjie Di; Tong Li; Yuanzhe Cui; Zongwu Xie; Linlin Feng; Min Yu (Ocean Engineering, 2025)

Scour prediction, monitoring, and protection measures for offshore wind turbines: Recent advancements and insights - Jingcheng Cui; Ting Bao; Xuanming Ding; Chong Tang; Tianbo Li; Weizhen Zhou (Ocean Engineering, 2025)

Breaking the zero-flux paradigm: an iterative surface energy balance framework for enhanced cold pixel characterization - Jun Wei; Zhiliang Zhang; Bo Liu; Yuanlai Cui; Yufeng Luo; XiaoPei Tang (Journal of Cleaner Production, 2025)

Efficient biosorption of molybdenum (VI) using Chlorella pyrenoidosa biomass: Mechanistic insights and sustainable application in water remediation - Zhixin Song; Lingfang Cui; Xunan Li; Zichen Zhang; Chao Zhang; Gangfu Song; Yu Zhao; Wenzhong Tang (Journal of Cleaner Production, 2025)

Rapid formation of acetaldehyde and its influence on ozone formation in a petrochemical industrialized region - Can Cui; Yujiao Zhu; Xiaoyu Yan; Xin Zhang; Min Zhao; Jiangshan Mu; Xuelian Zhong; Jinghao Tang; Yanqiu Nie; Cong An; Wanghui Chu; Yue Sun; et al. (Journal of Environmental Sciences, 2025)

Dynamic changes in flavonoid profiles and their bioactive properties during rice yellowing - Jinguang Liu; Caiyun Tang; Yanan Qv; Xiao Zheng; Yawen Wang; Mixue Yan; Xuejiao Li; Yu Cui; Yilun Chen; Yuqian Liu (Food Chemistry, 2025)

Amino acid promotes the formation of enals and 1-octen-3-ol from linoleic acid during the thermal reaction between alanine-xylose Amadori compound and Agrocybe aegerita enzymatic hydrolysates - Tong Zhou; Qingqing Chai; Man Zhang; Heping Cui; Mingzhou Song; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Bioscience, 2025)

Nitrogen fertilizer accelerated silk growth and increased grain yield of maize under low light stress - Wenwen Han; Yarong Zhang; Jianhong Ren; Xinru Zhang; Zhiyi Tang; Zhihua Wu; Lingxin Shi; Guangzhou Liu; Dahong Bian; Yanhong Cui; Xiong Du; Zhen Gao (Field Crops Research, 2025)

rGO/polypyrrole-modified bioelectrode reshapes microbial communities for enhanced energy-recovering denitrification in carbon-limited wastewater - Yue-Jia Yang; Hong-Li Lu; Naif Abdullah Al-Dhabi; Wang-Wang Tang; Shuai Wang; Dan Cui (Environmental Research, 2025)

Novel HN-AD bacterium G11: Deciphering the denitrification mechanism and nanoFe3O4 enhancement research - Qile Gao; Jun Li; Zhaoming Zheng; Peng Tang; Yanan Cui (Environmental Research, 2025)

Residential greenness modifies the association between long-term exposure to PM2.5 components and allergic diseases in schoolchildren: A large-scale study in Southern China - Hua-Lian Chen; Chao-Yang Chen; Cui-Lan Tang; Wei-Guo Liao; Hui-Xian Zeng; Wen-Jie Meng; Qi-Zhen Wu; Guang-Hui Dong; Jian Chen; Xiao-Wen Zeng (Environmental Pollution, 2025)

Universal ionic wind tweezer for non-contact, phase-inclusive micromanipulation - Qiang Tang; Chengcheng Song; Manfei Liu; Xiaxia Cui; Junjie Zhang; Zetao Wang; Sheng Zhang (Chemical Engineering Journal, 2025)

Recent advances in non-precious metal electrocatalysts for anion exchange membrane water electrolysis: Mechanistic insights, catalyst design, and structural regulation strategies - Qing Wang; Yuan Wang; Hon Man Luk; Jihui Tang; Shuang Wu; Dongyang Wu; Zhongyuan Hu; Da Cui; Jinghui Zhang (Chemical Engineering Journal, 2025)

Thermodynamic and kinetic improvement of MgH2 via the synergism of Al species and Nb-TiO2 - Mengran Li; Jialing Gu; Qinke Tang; Jiabao Bai; Bin Cui; Ruoyu Ma; Yunfeng Zhu; Rui Shi; Yao Zhang; Jiguang Zhang; Yana Liu; Jun Wang; et al. (Chemical Engineering Journal, 2025)

Preparation and optimization of pickering emulsion stabilized by organosilane-modified palygorskite to encapsulate natural colorants for cosmetic application - Peixuan Tan; Hongyan Cui; Chao Jiang; Chunying Jiang; Qiongyi Huang; Jingying Li; Ying Tang; Yongjun Feng (Applied Clay Science, 2025)

In-situ formation of green rust during Fe(II) coagulation: Dual reductive and adsorptive pathways for dyeing wastewater treatment - Xian Zhao; Jia-Yi Wang; Yu-Qian Wang; Chen-Hao Cui; Xin Yan; Wei Dai; An-Ran Zhang; Zhen-Ying Zhang; Ding-Ding Tang; Yan Zhou; Qiong Qin; Ji-Wei Pang; et al. (Water Research, 2025)

Experimental investigation on local scour around a cubic artificial reef in bidirectional tidal currents - Linlin Wang; Mingda Yang; Muk Chen Ong; Fenfang Zhao; Yujie Cui; Yanli Tang (Ocean Engineering, 2025)

Trophodynamic mechanisms of per- and polyfluoroalkyl substances in oligotrophic ecosystem from the Tibetan Plateau river - Yanan Li; Jiao Ren; Yawen Li; Fengfeng Dong; Qiusheng He; Yang Cui; Ke Zhang; Zhentao Wang; Xinqi Xin; Yitao Pan; Jianhui Tang (Journal of Hazardous Materials, 2025)

Optimizing organic waste co-composting: Component ratio thresholds for dual enhancement of maturity and gaseous emission reduction - Ruonan Ma; Ruolan Tang; Guannan Zheng; Jiani Wang; Zhongliang Cui; Yan Liu; Guoxue Li; Fanqiao Meng; Jing Yuan (Journal of Environmental Chemical Engineering, 2025)

Mechanistic insights into H2O2 activation by high-density iron single-atom catalysts for efficient water treatment: Surface-bound radical and singlet oxygen - Fuhang Xu; Cui Lai; Mingming Zhang; Zuying Yao; Dengsheng Ma; Bisheng Li; Meng Qin; Huchuan Yan; Xiuqin Huo; Xing Fan; Biting Wang; Shiyu Liu; et al. (Journal of Environmental Chemical Engineering, 2025)

A green process for treatment of Bayer red mud into synthetic soil - Tao Wang; Pengkun Cui; Yexuan Tang; Jianli Tan; Menglin Qin; Xuemin Cui (Journal of Environmental Chemical Engineering, 2025)

Valorizing and detoxifying alkaline lime mud waste from pulp mills via the production of high activity lime and lye - Tao Wang; Jianli Tan; Jiazheng Liu; Yexuan Tang; Yan He; Xuemin Cui (Journal of Environmental Chemical Engineering, 2025)

Vacancy-rich Nd2S3/TiO2 S-scheme heterojunction for boosted photocatalytic tetracycline hydrochloride degradation: Interfacial engineering and mechanism insight - Qiang Wang; Ying Tang; Tiantian Li; Dan Cui; Weixia Yang; Li Zhang; Kezhen Qi; Feng Yu (Journal of Environmental Chemical Engineering, 2025)

Biochar reduces microbial fertilizer-induced microbial community stability by weakening heterogeneous selection in poplar plantation soil - Minmin Cao; Qi Lu; Lina Cui; Genmei Wang; Xiang Zheng; Dun Wang; Yinuo Kong; Ye tian; Luozhong Tang; Huanchao Zhang (Forest Ecology and Management, 2025)

Peroxydisulfate activation by copper metal-organic framework derivatives: Deciphering the role of copper species - Shiyu Liu; Cui Lai; Lei Qin; Dengsheng Ma; Xuerong Zhou; Huchuan Yan; Fuhang Xu; Lin Tang; Xingzhong Yuan (Environmental Research, 2025)

Hysteretic model for shear-type friction steel truss coupling beams - Yao Cui; Jindian Hu; Zhuoxin Wang; Qi Tang; Tao Wang (Engineering Structures, 2025)

Oxygen vacancy-assisted CuCo tandem catalyst boosts efficient electrocatalytic neutral ultralow-concentration nitrate to ammonia - Xing Fan; Cui Lai; Lei Qin; Mingming Zhang; Huchuan Yan; Shiyu Liu; Dengsheng Ma; Qianting Liu; Lin Tang (Chemical Engineering Journal, 2025)

Ultrasound triggered spatial-temporal NO gas release to enhance sonodynamic therapy and immune checkpoint blockade therapy against pancreatic cancer - Wanrui Shi; Jianfeng Zhang; Ruiqi Wu; Shiti Shama; Shi Tan; Heng Xue; Yan Sun; Qingshuang Tang; Suhui Sun; Rui Tang; Guotao Feng; Xiaoda Li; et al. (Chemical Engineering Journal, 2025)

In situ tracking of MOF structural reconstruction toward a Cu/Bi/MOF composite electrocatalyst for efficient CO2-to-formate conversion - Yutao Cao; Yongjian Zhao; Tingting Tang; Shuo Cui; Min Li; Xianhu Sun; Wei Cui; Hong Zhao (Chemical Engineering Journal, 2025)

Synergistic band structure tailoring and texturing enhance cooling-power generation Bifunctionality in Bi0.4Sb1.6Te3 - Lin Liao; Jingjing Cui; Keke Liu; Xili Wen; Xingyan Dong; Ming Liu; Ding Luo; Yu-Ke Zhu; Xianli Su; Jiehe Sui; Jinsong Wu; Xinfeng Tang (Chemical Engineering Journal, 2025)

Competitive ion driven reversible Cu and Ni electrodeposition for smart windows with synergistic optical and thermal regulation - Wenhao Wang; Long Wang; Gu Liu; Lijun Yang; Tonghao Liu; Yina Cui; Lixuan Zhang; Qingyi Kang; Xu Tang; Lele Ma; Jinwen Ren; Xinyu Zhu; et al. (Chemical Engineering Journal, 2025)

Rational design of freeze-crosslinked polysaccharide sponges for efficient non-compressible hemostasis and liver repair - Peng Zhou; Weixiao Ding; Hongyan Wang; Xinmeng Li; Jian Cui; Guangjiu Liu; Zhiqi Chen; Chao Tang; Yishan Jiang; Lei Zhang; Dongping Sun (Carbohydrate Polymers, 2025)

Improving GNSS ultra-rapid orbit accuracy via multi-session normal equation stacking - Longjiang Tang; Jungang Wang; Zhiwei Qin; Bobin Cui; Huizhong Zhu (Advances in Space Research, 2025)

Genetic influence of the brain on epigenetic age acceleration: evidence of a large‐scale genetic correlation study - Chengcheng Li; Jiaze Tang; Junshuan Cui; Niya Long; Wu Cen; Qibo Wu; Ming Yang; Liangzhao Chu; Xingwang Zhou (Biogerontology, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

The spatial distribution relationship between mesoscale eddies and chub mackerel and its preliminary analysis of causes in the Northwest Pacific Ocean - Xiumei Fan; Xuesen Cui; Shenglong Yang; Fenghua Tang (Frontiers in Marine Science, 2025)
Chub mackerel (Scomber japonicus ) is a commercially important small pelagic fish species whose distribution is strongly influenced by marine environmental conditions. Mesoscale eddies, which are widespread in the Northwest Pacific Ocean, alter the spatial patterns of local environmental variables, thereby affecting the distribution of chub mackerel. This study analyzed fishery production data of chub mackerel in the Northwest Pacific, concurrent mesoscale eddy data, and oceanographic environmental datasets. Spatial comparisons between catch distributions and eddy polarity revealed distinct southwest-northeast-oriented cyclonic eddy zones within fishing grounds. Cyclonic eddy zones were located north of anticyclonic eddy zones, with catches predominantly distributed between these zones and skewed toward cyclonic eddies. Higher catch densities were observed near cyclonic eddies compared to anticyclonic eddies, with elevated yields both inside and along the edges of cyclonic eddies. In contrast, anticyclonic eddies exhibited higher catches along their peripheries but lower values within their cores. Spatial clustering analysis using Moran’s Index and hotspot detection via the General G Index revealed statistically significant aggregation of chub mackerel catches in the southern-central regions of cyclonic eddies and the northwestern margins of anticyclonic eddies (p<0.01). The distribution characteristics of catch yields within eddy-affected areas exhibit notable similarities with environmental variable patterns. GAM modeling revealed significant correlations between chub mackerel distribution in these mesoscale eddy regions and environmental variables, with anticyclonic eddies explaining 32.8% and cyclonic eddies accounting for 47.2% of the deviance explained rate. These findings provide valuable insights into the mechanisms underlying mesoscale eddy impacts on mackerel distribution, which crucially contribute to the sustainable management and conservation of mackerel resources.

Can environmental system reform enhance firms’ export product quality? Evidence from the environmental vertical reform in China’s prefecture-level cities - Yan Jiang; Long Tang; Xiaotian Wei; Cui Huang (Environment, Development and Sustainability, 2025)

Formation of characteristic aroma in traditional livestock and poultry meat dishes and strategies of aroma control and standardization for industrial cooking - Yishun Yao; Shaoyun Wang; Xiaomin Wang; Heping Cui; Jingyang Yu; Khizar Hayat; Qingrong Huang; Xiaoming Zhang; Chi-Tang Ho (Trends in Food Science & Technology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Exploring the links between wetland design parameters, hydraulic behaviors, and treatment performance using an improved analysis framework - Bochao Zhang; Junzhe Luo; Yuting Zhang; Jiaer Wang; Chi Tang; Yufeng Luo; Yuanlai Cui (Journal of Hydrology, 2025)

Recovery of rare earth elements from sediments affected by mining activities - De-Xiang Xu; Xuan-Pu Cheng; Cui-Ling Huang; Xiao-Rui Liu; Can-Die Xie; Rong-Liang Qiu; Chang Liu; Mei-Na Guo; Jean-Louis Morel; Wen-Shen Liu; Ye-Tao Tang (Journal of Hazardous Materials, 2025)

Chlorinated paraffins in plasma of healthy elderly adults: Method development, temporal variability, and exposure determinants - Ke Fang; Xiaojie Guo; Runming He; Yibin Sun; Yixuan Huang; Hongyang Cui; Yifu Lu; Wen Gu; Chao Wang; Yi Wan; Song Tang; Xiaoming Shi (Journal of Hazardous Materials, 2025)

Role of exogenous xylose during its co-heating with alanine-xylose Amadori compound: Competitively promoting 2-furfural formation and limiting pyrazines generation - Tong Zhou; Qingqing Chai; Man Zhang; Heping Cui; Ahmad Mohammad; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Chemistry, 2025)

Integrating widely targeted metabolomics and network pharmacology to provide insights into the mechanism of nutrition changes in walnut kernel under different drying methods - Wenwei Wang; Qingyang Li; Maokai Cui; Danyu Shen; Runhong Mo; Fubin Tang; Yihua Liu (Food Chemistry, 2025)

Pediococcus acidilactici CCFM1365-fermented Pueraria lobata as a therapeutic intervention for alcoholic liver disease - Yongkang Zhou; Wenyi Zhang; Xin Tang; Bingyong Mao; Wei-Lian Hung; Jian He; Jinrui Du; Qiuyue Jiang; Haotian Feng; Jianxin Zhao; Wei Chen; Shumao Cui (Food Bioscience, 2025)

Directional synthesis of high-density aviation fuel through CO2 hydrogenation coupling with naphthalene alkylation over ZnZrOx/Hβ catalyst - Xiaopo Niu; Hongming Qian; Dongyuan Cai; Wenli Zhao; Qingfa Wang; Quanli Ke; Guokai Cui; Chunliang Ge; Lina Tang; Hanfeng Lu (Chemical Engineering Journal, 2025)

S-scheme/Schottky dual heterojunction BiOBr/Fe3O4/Ti3C2 MXene boost synergistic roles of photocatalysis and persulfate activation via multi-channel photoelectron transfer - Xiaoyan Wei; Caiwei Su; Hanbing Zhang; Xianglong Tang; Jingyi Zhou; Fan Ye; Cui Pan; Yuelong Qin; Kun Liu; Zhangfa Tong (Chemical Engineering Journal, 2025)

Logic-gate nanocompiler for oxidative/reductive molecular parallel detection during hepatic ischemia-reperfusion injury - Tao Tang; Fushou Liu; Longshua Qin; Hao Li; Wen-Ping Lin; Yi-Ping Gu; Fangtao Tan; Linfeng Wang; Huan Liu; Mingxi Zhang; Ran Cui (Chemical Engineering Journal, 2025)

Trees suppress growth but sustain water consumption in response to flash drought in a subtropical forest - Yongqiang Zhang; Zeng Cui; Yun-Hao Bai; Hong-Tu Zhang; Zhiyao Tang (Agricultural and Forest Meteorology, 2025)

Influence of fissure-induced linear infiltration on the evolution characteristics of the loess tunnel seepage field - Junling Qiu; Guanhua Cui; Jinxing Lai; Kai Zhao; Kunjie Tang; Lei Qiang; Ding Jia (Tunnelling and Underground Space Technology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

One-billion-year-old eukaryotic algal fossil Arctacellularia from North China and its implications for the evolution of pre-Cryogenian filamentous multicellularity - Rui Huang; Guangjin Li; Jiayue Wang; Qing Tang; Mingyang Qiu; Qian Chen; Hanzhi Qu; Chengxi Wu; Wenfei Cui; Xianqin Yan; Chuanming Zhou; Xunlai Yuan; et al. (Precambrian Research, 2025)

Oleanane-type triterpenoids from Sabia limoniacea with nitric oxide inhibitory activity - Ping Hou; Liwei Pan; Liuting Peng; Chunqiu Gan; Chenyang Ren; Ruiyun Yang; Weifeng Xu; Chaowen He; Yanlin Cui; Wen Tang; Jun Li; Yan Huang (Phytochemistry, 2025)

Bridging the knowledge gap: From poly(butylene adipate-co-terephthalatebutylene) degradation to CO2-generating mineralization under the synergistic effect of bacteria and fungi - Yue Wang; Qi Liu; Chang-Hong Xie; Ruo-Tong Zhao; Qiu-Xiang Tang; Dong-Fei Han; Yi-Ning Xia; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

Virus-host interactions driving the transfer of antibiotic resistance genes in a river-reservoir system under heavy rainfall - Yuan Xin; Junya Zhang; Qihe Tang; Minghai Wei; Liying Zhu; Yu Zhao; Yunwei Cui; Tongwen Sun; Yuansong Wei; Hans Hermann Richnow (Journal of Hazardous Materials, 2025)

A machine learning-assisted electrochemical nanosensor based on bimetal-codoped MOF composites for simultaneous detection and removal of multiple fluoroquinolone antibiotics - Suisui He; Jiaheng Zhang; Junlin He; Zhonghui Luo; Wen Chen; Huimin Tang; Jiaqi Long; Jun Wang; Hua Wei; Cui-Yun Yu (Journal of Cleaner Production, 2025)

Water availability and hydrological connectivity mediate the responses of alpine soil prokaryotes to temperature changes at the watershed scale - Wencong Lv; Liyuan Ma; Jianqing Du; Li Tang; Biao Zhang; Danhong Chen; Qiang Liu; Shutong Zhou; Zhe Pang; Lin Chen; Yanbin Hao; Kai Xue; et al. (Journal of Environmental Management, 2025)

Structural design and performance optimization of different crystalline zinc sulfide anodes in sodium-ion batteries - Yu Hao; Yaru Cui; Juan Wang; Jinpeng Hu; Qinghuan Tang; Shufeng Yang (Chemical Engineering Journal, 2025)

Bioluminescent fungi-inspired room temperature phosphorescence mycelia - Xin Li; Jin-Xin Ma; Ping Wu; Qian Gao; Hao Wang; Lu-Xin Tang; Feng Peng; Bao-Zhong Lü; Jing Si; Bao-Kai Cui (Chemical Engineering Journal, 2025)

Progressive trend, conceptual terminology, and future directions of green façade research: A review of literature in 2010–2023 - Y. Cui; J. Tang; B.-J. He (International Journal of Environmental Science and Technology, 2025)

Emulsifier is beneficial for declining dietary lipid requirement of aquatic crustaceans by accelerating the absorption, transport and deposition of lipids: A case study in mud crab (Scylla paramamosain) - Zihao Ye; Jinjin Liu; Shihui Cui; Jing Chen; Mengyao Tang; Chaojia Chen; Yifang Xu; Ziyi Wang; Yuan Huang; Shaowei Zhai; Ziping Zhang; Chao Fan; et al. (Animal Feed Science and Technology, 2025)

Advancements in the investigation of the mechanisms underlying cognitive aging - Honglu Zou; Shuo Zhang; Xinxin Cui; Hongyan Xu; Zhangying Zhou; Danmeng Cheng; Yanan Han; Youcai Tang; Anqin Dong; Xianwen Dong (Biogerontology, 2025)

Gut microbiota: a superior operator for dietary phytochemicals to improve atherosclerosis - Jian Ai; Xin Tang; Bingyong Mao; Qiuxiang Zhang; Jianxin Zhao; Wei Chen; Shumao Cui (Critical Reviews in Food Science and Nutrition, 2025)

Development of an Ellipsoid Based Chart Datum Around the China Seas - Yanguang Fu; Yanxiong Liu; Mehdi Khaki; Fukai Peng; Xiaolong Mi; Yikai Feng; Xiaoli Deng; Long Yang; Qinghua Tang; Li Cui (Marine Geodesy, 2025)

Prediction of potential fishing grounds for chub mackerel in the Northwest Pacific utilizing a combination of multivariable Gaussian mixture model and Bayesian approach - Fenghua Tang; Yaoji Ba; Shengmao Zhang; Shenglong Yang; Guoqing Zhao; Zuli Wu; Jiasheng Li; Xuesen Cui (Regional Studies in Marine Science, 2025)

Degradation of biodegradable plastic films in soil: microplastics formation and soil microbial community dynamics - Yue Wang; Run-Hao Bai; Qi Liu; Qiu-Xiang Tang; Chang-Hong Xie; Aurore Richel; Christophe Len; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

Addressing challenges and advancing solutions: Enhancing semi-coking wastewater treatment for a sustainable prospect - Tingting Cui; Chunhui Zhang; Bingxu Quan; Liwei Wang; Zhao Zhang; Peidong Su; Yuanhui Tang; Guifeng Zhao; Ping Qiao; Junqiang Guo; Rui Zhang (Journal of Environmental Management, 2025)

Geochemical evidence for Late Eocene to Oligocene climate change in the Lühe Basin of the southeastern Tibetan Plateau - Hao Cui; He Tang; Zhifeng Liu; Jianghao Bai; Juncai Chen; Gangjian Wei (Journal of Asian Earth Sciences, 2025)

Topographic stress proxy as a new causative factor in landslide susceptibility mapping - Weilin Kong; Ruilong Wei; Chunhao Wu; Peng Cui; Guoqing Chen; Yifan Zhang; Dongchen Li; Chenxiao Tang (Gondwana Research, 2025)

Dual role of exogenous xylose in regulating pyrazines and furans formation during the thermal degradation of N,N-di(1-deoxy-d-xylulos-1-yl)lysine through temperature, reaction time, and xylose concentration control - Han Zhang; Heping Cui; Xue Xia; Shahzad Hussain; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Chemistry, 2025)

Nitrogen level determines arbuscular mycorrhizal fungi nitrogen uptake rate of Stipa purpurea in alpine steppe - Jiahui Sun; Yu Tang; Keyu Chen; Shijie Ren; Hailan Shi; Qiang Dong; Junfu Dong; Lin Zhang; Xiaoyong Cui; Yanfen Wang; Baoming Ji; Jing Zhang (Plant and Soil, 2025)

Cerium oxide nanoparticles as potent inhibitors of ferroptosis: role of antioxidant activity and protein regulation - Chenran Feng; Tong Yang; Jie Zhou; Chen Wang; Zheng Chu; Ying Zhang; Junzhe Zhang; Yin Kwan Wong; Cui Liu; Peng Gao; Ang Ma; Huan Tang; et al. (Journal of Molecular Medicine, 2025)

Enhancements of triple-frequency signals and multi-constellation combinations in PPP-RTK Services: improving convergence speed and expanding service coverage - Shi Du; Bobin Cui; Longjiang Tang; Jungang Wang; Guanwen Huang; Harald Schuh (GPS Solutions, 2025)

Preparation, characterization and antibacterial activities of bio-based schiff base Copper Complex intercalated montmorillonite - Xianchang Liang; Wenjing Wang; Mingyuan Tang; Yuanyuan Kang; Mingjun Cui; Haichao Zhao (Applied Clay Science, 2025)

Underwater Reverberation Suppression Using Wavelet Transform and Complementary Learning - Jiajie Liu; Qunfei Zhang; Xiaodong Cui; Chencong Tang; Zijun Pu (Oceans, 2025)
Reverberation is the primary interference of active detection. Therefore, the effective suppression of reverberation is a prerequisite for reliable signal processing. Existing dereverberation methods have shown effectiveness in specific scenarios. However, they often struggle to exploit the distinction between target echo and reverberation, especially in complex, dynamically changing underwater environments. This paper proposes a novel dereverberation network, ERCL-AttentionNet (Echo–Reverberation Complementary Learning Attention Network). We use the Continuous Wavelet Transform (CWT) to extract time–frequency features from the received signal, effectively balancing the time and frequency resolution. The real and imaginary parts of the time–frequency matrix are combined to generate attention representations, which are processed by the network. The network architecture consists of two complementary UNet models sharing the same encoder. These models independently learn target echo and reverberation features to reconstruct the target echo. An attention mechanism further enhances performance by focusing on target information and suppressing irrelevant disturbances in complex environments. Experimental results demonstrate that our method achieves a higher Peak-to-Average Signal-to-Reverberation Ratio (PSRR), Structural Similarity Index (SSIM), and Peak-to-Average Ratio (PAR) of cross-correlation while effectively preserving key time–frequency features, compared to traditional methods such as autoregressive (AR) and singular value decomposition (SVD).

Stepwise leaching rare earth from weathered crust elution-deposited rare earth ores by the inhibition leaching of aluminum with HMTA - Zhengyan He; Qin Zuo; Yuchen Tang; Wenqian Cui; Zhigao Xu; Ming Wu; Jun Qu; Ruan Chi (Environmental Science and Pollution Research, 2025)

The combination of microplastics and glyphosate affects the microbiome of soil inhabitant Enchytraeus crypticus - Huihui Yang; Guogang Zheng; Guoyan Qin; Qi Zhang; Ziyao Zhang; Bingfeng Chen; Chaotang Lei; Meng Liu; Rui Cui; Liwei Sun; Shengjie Xia; W.J.G.M. Peijnenburg; et al. (Journal of Hazardous Materials, 2025)

Light absorption of black and brown carbon in eastern China - Rongzhi Tang; Weizhen Cui; Xiuli Zhang; Yu Tan (Journal of Hazardous Materials, 2025)

Green and efficient conversion of polypropylene wastes into Ni@CNTs hybrids and their application for fire resistant polycarbonate composites - Junlin Zhu; Zhaotian Ba; Yuanmeng Lou; Cui Li; Lili Ma; Jie Liu; Xin Wen; Tao Tang (Journal of Environmental Chemical Engineering, 2025)

Comprehensive mechanisms of epigallocatechin-3-gallate (EGCG) metabolism during tea dieback disease infection in tea plant (Camellia sinensis) - Yiyong Chen; Bo Zhou; Jianlong Li; Man Zhang; Yingying Cui; Jinchi Tang (Food Bioscience, 2025)

Enhancement of 1-octen-3-ol in Lentinus edodes Maillard peptides through exogenous linoleic acid and its synergistic effect with l-cysteine - Mengli Wang; Xinjing Li; Foxin Zhang; Heping Cui; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Bioscience, 2025)

Effect of modified atmosphere on the growth of dominant fungal species in grains during storage - Zhihui Qi; Wenbo Gao; Yuqing Lei; Xuguang Liu; Haiyang Zhang; Miao Cui; Lin Tian; Shuyi Wang; Zhongming Wang; Fang Tang (Food Packaging and Shelf Life, 2025)

Prenatal exposure to ozone and bone mineral density in early childhood: Susceptible window identification - Linxi Tang; Yibing Zhu; Yudiyang Ma; Chong Miao; Bin Sun; Feipeng Cui; Jingmin Guo; Yaohua Tian (Environmental Research, 2025)

Engineering external and internal precursors to boost the synthesis of confined carbyne - Yanghao Feng; Wendi Zhang; Kunpeng Tang; Yingzhi Chen; Huiju Cao; Yuan Hu; Weili Cui; Lei Shi; Guowei Yang (Chemical Engineering Journal, 2025)

Janus-structured lignin hydrogel evaporator via laser direct writing for high efficiency seawater desalination and solar power generation - Yuhan Liu; Zhongwei Zhang; Jiangang Wang; Chen Hu; Jiaxin Tang; Meng Shi; Hongyou Cui; Dongfeng Qi (Chemical Engineering Journal, 2025)

Lacticaseibacillus paracasei CCFM1222 Ameliorated the Intestinal Barrier and Regulated Gut Microbiota in Mice with Dextran Sulfate Sodium-Induced Colitis - Weiling Guo; Xin Tang; Qiuxiang Zhang; Feifei Xiong; Yongqiu Yan; Jianxin Zhao; Bingyong Mao; Hao Zhang; Shumao Cui (Probiotics and Antimicrobial Proteins, 2025)

Analysis of coupled wetland soil–plant ecological stoichiometric characteristics of carbon, nitrogen, and phosphorus under different disturbance intensities - Yuhan Zou; Xiying Tang; Lijuan Cui; Huazhe Li; Yinru Lei; Xinsheng Zhao; Xiajie Zhai; Jing Li; Jinzhi Wang; Rumiao Wang; Wei Li (Plant and Soil, 2025)

Roseateles cavernae sp. nov., a Bacterium Isolated from Freshwater of the Old Huanglong Cave in Yunnan Province, South-West China - Yu-Man Zhang; Qian Jiang; Mu-Yao Li; Qing-Yu Miao; Yi-Qing Li; Min Yin; Cui-Ping Miao; Shu-Kun Tang (Current Microbiology, 2025)

Experimental research and application of a new no-pillar green coal mining method - Qiang Fu; Jun Yang; Yubing Gao; Hongxu Song; Yuxuan Liu; Hongyu Jin; Jiarui Tang; Junpeng Zhao; Jianbo Cui (Bulletin of Engineering Geology and the Environment, 2025)

Dynamic motion response of a large-scale steel aquaculture cage during towing - Shuai Niu; Zhi Wang; Lianyi Guo; Lianghao Tang; Tianyu Gu; Can Cui; Dejun Feng; Fukun Gui; Xu Yang (Frontiers in Marine Science, 2025)
As global aquaculture ventures further into offshore environments, the safe transport of large-scale aquaculture net cages across varied marine conditions has become a critical technical concern. This study conducts a detailed numerical simulation of the wet towing process for an octagonal aquaculture cage using AQWA software, systematically examining the effects of towline length, towing speed, towing configuration, and environmental factors on the cage’s dynamic response and towline load characteristics. The findings reveal that towline length and towing speed are pivotal in determining the pitch amplitude of the cage and the resulting towline tension. Compared to a towline length of 200 m, using a towline length of 150 m combined with a towing speed of 0.5 m/s reduces pitch amplitude by 51.6% and towline tension by 24.8%. Additionally, an interval towing arrangement significantly enhances cage stability while minimizing towline stress. Under conditions of low wave height and longer wave period, the cage’s motion response remains stable, contributing to enhanced transport safety. This research offers critical theoretical foundations and optimization strategies for the wet towing design considerations of offshore aquaculture cages, providing valuable insights to advance transport safety in challenging marine environments.

Global prevalence of Porcine Astrovirus: A systematic review and meta-analysis - Xiaoyu Ge; Yize Li; Feipeng Zhao; Xin’ao Ma; Jiaxuan Li; Yanping Jiang; Wen Cui; Xiaona Wang; Lijie Tang (Preventive Veterinary Medicine, 2025)

Computational fluid dynamics and machine learning assisted Al-LDH adsorbent reactor design for lithium recovery from salt lakes - Jiangtao Yu; Minmeng Tang; Peng Cui; Jianquan Deng; Haiying Mi; Li Zhang; Linlin Chen; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2025)

Vacancy engineering regulating specific capacitance of supercapacitors in MOF-on-MOF derived CoSe2 quantum dots embedded in carbon and CoSe2 hollow cages - Shuangxing Cui; Yaozong Gu; Yifan Tang; Wan Cui; Guochang Li; Qiuju Zhang; Lei Han (Chemical Engineering Journal, 2025)

Development and validation of a fully coupled dynamic analysis tool for an articulated foundation offshore wind turbine - Pei Zhang; Cui Li; Jiayang Gu; Yaoyu Hu; Yan Li; Yougang Tang (Ocean Engineering, 2025)

High-resolution sea surface height reconstruction method based on deep learning gradient constraint embedding method - Jifeng Cui; Fangjie Yu; Junwu Tang; Xinglong Zhang; Ge Chen (Ocean Engineering, 2025)

Large-scale genomic and phenomic analyses of modern cultivars empower future rice breeding design - Xiaoding Ma; Hao Wang; Shen Yan; Chuanqing Zhou; Kunneng Zhou; Qiang Zhang; Maomao Li; Yaolong Yang; Danting Li; Peng Song; Cuifeng Tang; Leiyue Geng; et al. (Molecular Plant, 2025)

Research on the synergistic effects of market-oriented environmental regulations on pollution and carbon emission reduction - Yan Tang; Yang Hu; Anqi Cui (Journal of Environmental Management, 2025)

Hydrological connectivity and dissolved organic matter impacts nitrogen and antibiotics fate in river-lake system before and after extreme wet season - Yu Zhao; Yuanmeng Song; Lulu Zhang; Jiansheng Cui; Wenzhong Tang (Journal of Environmental Management, 2025)

Adsorption of polycyclic aromatic hydrocarbons (PAHs) in soil and water on pyrochars: A review - Lishi Tang; Panpan Wang; Chengze Yu; Ning Jiang; Jiaqi Hou; Jun Cui; Shuaishuai Xin; Yanjun Xin; Mingxiao Li (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “Excellent performance of Ce doped CoMn2O4/TiO2 catalyst in NH3-SCR of NO under H2O&SO2 conditions” [J. Environ. Chem. Eng. 12 (2024) 113849] - Fengyu Gao; Yaxin Niu; Yue Cui; Yuanyuan Liu; Ning Luo; Jiajun Wen; Erhong Duan; Chengzhi Wang; Honghong Yi; Yuansong Zhou; Xiaolong Tang (Journal of Environmental Chemical Engineering, 2025)

Effects of trimethoprim on activated sludge system: Biological nutrient removal and microbial community structure - Xianjin Xie; Kangping Cui; Yihan Chen; Xinrui Yuan; Yuchao Tang; Kun Wang; Shijie Sun; Chen-Xuan Li (Journal of Environmental Chemical Engineering, 2025)

Identification of Dendrobium officinale species and authentication of commercial products by DNA barcoding and high-resolution melting analysis - Zhilong He; Zhao Yang; Cui Dong; Shanshan Yan; Jing Lin; Hexigeduleng Bao; Fan Tang; Leilei Zhang; Cheng Zhu; Yan Hu; Yanfei Ding (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

The effects of Licoflavone on hepatic lipid accumulation: In vitro and in vivo studies - Fei Liu; Jiang Wang; Xin Tang; Bingyong Mao; Qiuxiang Zhang; Jianxin Zhao; Wei Chen; Shumao Cui (Food Bioscience, 2025)

Prevalence and Predictors of Hemorrhagic Foci on Long-term Follow-up MRI of Recent Single Subcortical Infarcts - Shuai Jiang; Wen-Zuo Shang; Jing-Yu Cui; Yu-Ying Yan; Tang Yang; Yi Hu; Le Cao; Xun Yue; Ruo-Su Pan; Chen Ye; Jia-Yu Sun; Bo Wu (Translational Stroke Research, 2025)
Hemorrhagic foci surrounding the lacune in the long-term evolution of recent single subcortical infarcts (RSSIs) remains largely unexplored. We aimed to determine the prevalence, characteristics, and predictors of hemorrhagic foci in patients with RSSI. From a prospective, longitudinal study of RSSIs, we recruited patients who underwent multimodal MRI assessments both at baseline and approximately one year after the stroke onset. Hemorrhagic foci were identified using susceptibility-weighted imaging (SWI). Among 101 patients with RSSI, nearly half (n = 45, 44.6%) had hemorrhagic foci within the index RSSI lesions on follow-up SWI. RSSIs with hemorrhagic foci formation were associated with a longer time to follow-up imaging (median 449 versus 401 days, P = 0.005) and higher likelihood of being located in the anterior circulation compared to those without hemorrhagic foci (88.9% versus 64.3%, P = 0.003). Hemorrhagic foci were also associated with larger lesion size (P < 0.001), a higher proportion of cavitation formation (P = 0.003), higher baseline NIHSS scores (P = 0.004), and poorer functional outcomes (P = 0.001). In the subset of RSSIs in the lenticulostriate artery (LSA) territory, after adjustment for covariates, larger initial lesion volume (OR 1.80, 95% CI 1.13–2.87; P = 0.014) and greater decreases in LSA total length (OR 0.59, 95% CI 0.36–0.96; P = 0.035) were independently associated with hemorrhagic foci formation. The extent of ischemia in the initial infarct is predictive of the presence of hemorrhagic residues. Our findings contribute to the current understanding of the mechanisms underlying the evolution of RSSIs.

Astrocytic adenosine A2B receptors: a crucial player in brain function - Cui-Yuan Chen; Yong Tang (Purinergic Signalling, 2025)

Analysis of Codon Usage Patterns in a Rare Palmitoleic Acid Production Oleaginous Yeast, Scheffersomyces segobiensis - Lili Zhang; Wenxing Cui; Dandan Tang; Haohong Lin; Weiliang Dong; Xiujuan Qian; Min Jiang (Current Microbiology, 2025)

Compressive stress induced by desiccation shrinkage in clayey soils - Hao Zeng; Chao-Sheng Tang; Yu-Jun Cui; Abdallah Najdi (Applied Clay Science, 2025)

Improvement of inflammatory bowel disease by lactic acid bacteria-derived metabolites: a review - Weiling Guo; Bingyong Mao; Xin Tang; Qiuxiang Zhang; Jianxin Zhao; Hao Zhang; Wei Chen; Shumao Cui (Critical Reviews in Food Science and Nutrition, 2025)

The mechanisms of tripterygium glycosides-induced reproductive toxicity and detoxification strategies - Zechen Niu; Huanhuan Zhang; Chunzhou Cai; Ting Yang; Tian Ma; Dingqiao Xu; Dongxiao Cui; Yuping Tang (Reproductive Toxicology, 2025)

Alterations in microbial community structures and metabolic function in soil treated with biological and chemical insecticides - Renwen Zheng; Jun Peng; Qianqian Li; Yue Liu; Dongyan Huang; Yangjunlu Sheng; Cui Liu; Lei Qi; Nemat O. Keyhani; Qingfeng Tang (Pesticide Biochemistry and Physiology, 2025)

A water probe for direct pH measurement of individual particles via micro-Raman spectroscopy - Xiaoyu Cui; Mingjin Tang; Tong Zhu (Journal of Environmental Sciences, 2025)

Regulating effect of glycated rice bran protein aggregates and resultant emulsions on the gelatinization and retrogradation properties of rice starch - Yongxue Luo; Hanwen Cui; Wenting Tang; Zeyue Fu; Chuanfen Pu; Qingjie Sun (Food Hydrocolloids, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

A green biocatalyst fabricated by fungal laccase immobilized onto Fe3O4@polyaniline-chitosan nanofibrous composites for the removal of phenolic compounds - Hao Wang; Can Jin; Xin Li; Jin-Xin Ma; Yi-Fan Ye; Lu-Xin Tang; Jing Si; Bao-Kai Cui (Chemical Engineering Journal, 2025)

From soil health to agricultural productivity: The critical role of soil constraint management - Tong Li; Lizhen Cui; Vilim Filipović; Caixian Tang; Yunru Lai; Bernhard Wehr; Xiufang Song; Scott Chapman; Hongdou Liu; Ram C. Dalal; Yash P. Dang (CATENA, 2025)

The Role of Injection Pressure in the Impact Region of Liquid CO2 Flash Boiling Jets for Coal Breaking - Jiawei Cui; Wenchuan Liu; Jiren Tang; Chia-Fon Lee; Zhuoya Zhang; Weiqin Zuo (Rock Mechanics and Rock Engineering, 2025)

Delta Opioid Peptide [d-Ala2, d-Leu5]-Enkephalin Improves Physical and Cognitive Function and Increases Lifespan in Aged Female Mice - Lixia Huo; Hongquan Zhang; Chengwu Tang; Ge Cui; Tao Xue; Huihui Guo; Fandi Yao; Wei Zhang; Wenming Feng (Molecular Neurobiology, 2025)

Sensitive shrubland and unique urbanization patterns: the key to understanding emerging towns growth in arid regions - Qi Zhang; Junling He; Chunying Ren; Cun Chang; Wenxi Tang; Xifeng Ju; Adilai Saitiniyaz; Xin Guo; Liyang Cui; Liming Liu (Environmental Monitoring and Assessment, 2025)

Fertilization effects on soil organic matter chemistry - Dengjie Zhou; Rui Mou; Lihua Wang; Jingru Liu; Yuanxiang Tang; Ji Chen; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Li Zhang; et al. (Soil and Tillage Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Buried interface engineering towards stable zinc anodes for high-performance aqueous zinc-ion batteries - Qing Wen; Hao Fu; Chao Sun; Rude Cui; Hezhang Chen; Ruihan Ji; Linbo Tang; Lingjun Li; Jiexi Wang; Qing Wu; Jiafeng Zhang; Xiahui Zhang; et al. (Science Bulletin, 2025)

Catalytic wet air oxidation of phenol in wastewater over Ru catalysts supported on La doped TiO2: Improvements on activity and stability - Rongji Cui; Qing Zhang; Bingzheng Zhao; Zhicheng Tang (Journal of Water Process Engineering, 2025)

One-step green hydrometallurgical recycling of spent lithium-ion batteries’ cathode - Huifan Li; Yongfang Chen; Zhaowei Cui; Yusen Su; Zhanqi Liu; Xuanli Dong; Zhong Lin Wang; Wei Tang (Journal of Hazardous Materials, 2025)

Preparation of wood formaldehyde-free adhesive by concentrated water delignification black liquor - Ting Zhang; Jianli Tan; Yongqi Li; Yexuan Tang; Yan He; Yuanyuan Ge; Xuemin Cui (Journal of Cleaner Production, 2025)

Phosphorus speciation in the hyporheic zone and its response to sediment-water quality-biological activity coupling effect - Yue Qu; Jinxi Song; Yongqing Long; Nan Li; Songzhe Fu; Bin Tang; Qihao Tao; Qifan Cui; Ken Qin (Journal of Environmental Management, 2025)

Ultrathin LDH-coated SnO2 catalysts linked by hydrogen bonding for PMS activation via interlayer high-speed electron transfer channels: Performance and mechanism - Guangjie Lv; Haoyang Ye; Cui Lai; Dengsheng Ma; Xuerong Zhou; Xiuqin Huo; Hao Deng; Lin Tang; Tao Tong; Ming Yan; Shuyuan Hu; Lei Qin (Journal of Environmental Chemical Engineering, 2025)

Microencapsulation of glutathione through water/oil emulsification and complex coacervation: Improved encapsulation efficiency, physicochemical stability, and sustained release effect - Jingyang Yu; Ge Du; Yishun Yao; Qiuhong Liao; Tong Zhou; Heping Cui; Shahzad Hussain; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Research International, 2025)

Promoted formation of pyrazines by targeted precursor addition to improve aroma of thermally processed methionine-glucose Amadori compound - Shibin Deng; Heping Cui; Shahzad Hussain; Khizar Hayat; Wei Liu; Xiaoming Zhang; Chi-Tang Ho (Food Chemistry, 2025)

Pediococcus pentosaceus CCFM1402 could repair skin barrier via AHR-OVOL1 pathway and OX40 receptor modulation - Baojing Ren; Bingyong Mao; Xin Tang; Qiuxiang Zhang; Jianxin Zhao; Wei Chen; Shumao Cui (Food Bioscience, 2025)

Study on the rational construction methods and mechanical properties of composite beams in transverse negative bending moment zones - Jiawei Liu; Qinghua Zhang; Zhenyu Cheng; Chuang Cui; Kun Tang (Engineering Structures, 2025)

Strongly photosensitive metal-organic coordination polymers as photo-coupled electrocatalysts for CO2 reduction to formate - Kai Cui; Pengbo Lyu; Zhao Zhang; Manchang Kou; Xina Yuan; Jiayi Suo; Xiaoliang Tang; Yu Tang; Weisheng Liu; Yuxi Xu (Chemical Engineering Journal, 2025)

Dual role of multistage inoculation in manipulating bacterial community assembly patterns to improve degradation of lignocellulose during rice or corn straw composting - Da Liu; Ziwei Jiang; Wenxuan Feng; Yufeng Zhao; Pengfei Tang; Jizhe Cui; Zhan Zhao; Qian Lu (Chemical Engineering Journal, 2025)

Efficient oxidative cyanation of fructose to nitriles over Acidic-MnO under ambient air pressure - Wenjie Shao; Junpeng Wang; Meiying Niu; Jun Tang; Qiuhong Pan; Ziguo He; Ping Cui; LiFeng Chen; Zhiyong Fang; Qingping Ke (Chemical Engineering Journal, 2025)

K2CO3-doped CaO-based sorbent for CO2 capture: Performance studies and promotion mechanisms - Pengchao Zang; Jiyun Tang; Yihui Tao; Hao Zhang; Xiaozhe Wang; Lin Cui; Shouyan Chen; Pei Zhao; Yong Dong (Chemical Engineering Journal, 2025)

Impact of human activities on the long-term change and seasonal variability of Ebinur Lake, Northwest China - Haoxin Deng; Qiuhong Tang; Zhidong Zhang; Xingcai Liu; Gang Zhao; Shibo Cui; Zhiping Zhang; Shuai Shao; Jianbao Liu; Fahu Chen (Science China Earth Sciences, 2025)

Inoculation of plant growth-promoting rhizobacteria and rhizobia changes the protist community of alfalfa rhizosphere soil under saline-alkali environment - Yang Sun; Lu Tang; Ying Cui; Dihe Yang; Hong Gao; Jiaxin Chen; Ziying Zheng; Changhong Guo (Applied Soil Ecology, 2025)

Multi-Stage Screening Purification: A New and Effective Method for Cleaning Diatom Samples from Marine Sediments - Kong Deng; Mianmo Meng; Yangbo Lu; Wenming Ji; Guanxiong Tang; Guanqiang Cai; Qinyu Cui; Yongchao Lu; Feng Yang; Dingjie Zhang; Zhanhong Liu (Journal of Marine Science and Engineering, 2025)
Diatoms are critical indicators in marine paleoecology and contemporary ecosystem studies, yet the accuracy of diatom analysis depends on effective purification methods. Current screening and purification techniques often yield low accuracy. This study introduces a multi-stage screening purification method that integrates both physical and chemical techniques to enhance the extraction of diatom remains from marine sediments, thereby improving the reliability of subsequent analysis. Using surface sediment samples from the Pacific Ocean, we compared the effectiveness of three purification methods: heavy liquid suspension purification, single-layer screening purification, and the newly developed multi-stage screening purification method. The study aimed to evaluate the impact of each method on diatom abundance, valve size distribution, and the accuracy of taxonomic identification. The results revealed that the multi-stage method significantly improved the accuracy of diatom abundance calculation. With this method, diatom abundance was 21.9 times higher than that obtained using the heavy liquid suspension method and 6.5 times higher than that obtained using the single-stage method. This method also proved to be cost-effective, easy to use, and produced samples with low impurity levels, which enhanced microscopic observation, identification, and the reliability of taxonomic statistics. Key factors influencing diatom abundance included sieve pore size, heavy liquid concentration, and valve size and density, while the type of acid and oxidant had minimal effect. Additionally, the multi-stage screening method facilitated the classification of diatoms into various size categories, providing a comprehensive view of diatom size distribution, including nano-sized diatoms (diameter

Study on working mechanism and mechanical properties of retractable U-shaped steel gangue prevention structure - Jun Yang; Yuxuan Liu; Changjiang Li; Qiang Fu; Hongxu Song; Jianbo Cui; Jiarui Tang; Junpeng Zhao (Tunnelling and Underground Space Technology, 2025)

Attribution analysis of urban social resilience differences under rainstorm disaster impact: Insights from interpretable spatial machine learning framework - Tianshun Gu; Hongbo Zhao; Li Yue; Jiaojiao Guo; Qinyu Cui; Junqing Tang; Zhaoya Gong; Pengjun Zhao (Sustainable Cities and Society, 2025)

Novel peptide inhibitor of matrix Metalloproteinases-1 from pufferfish skin collagen hydrolysates and its potential Photoprotective activity via the MAPK/AP-1 signaling pathway - Bei Chen; Shuilin Cai; Lulu Cui; Ting Yu; Kun Qiao; Yongchang Su; Min Xu; Haiyan Tang; Shuji Liu; Ming Yang; Zhiyu Liu (Journal of Photochemistry and Photobiology B: Biology, 2025)

Assessing the influence of geo-environmental factors on discontinuous gully erosion at regional scales: A case study of spoon gullies on the loess plateau of China - Chenrui Li; Xin Yang; Yang Chen; Xingyu Zhou; Sijin Li; Xujia Cui; Guoan Tang (Journal of Environmental Management, 2025)

Uracil improves the freeze-drying resistance of Pediococcus acidilactici and Lactococcus lactis by increasing biofilm formation via the uridine monophosphate/LuxS/AI-2 pathway - Xuewu Liu; Shuanglu Hu; Bingyong Mao; Xin Tang; Qiuxiang Zhang; Jianxin Zhao; Shumao Cui (Food Bioscience, 2025)

A QGIS framework for physically-based probabilistic modelling of landslide susceptibility: QGIS-FORM - Jian Ji; Bin Tong; Hong-Zhi Cui; Xin-Tao Tang; Marcel Hürlimann; Shigui Du (Environmental Modelling & Software, 2025)

The tandem cracking-oxidation of phthalate esters with high CO2 selectivity and reduced energy cost - Tao Wei; Dezhen Zhang; Zicheng Wang; Zihan Zhou; Tapiwanashe Shumba; Yangqi Jiang; Shangpu Zhuang; Mifen Cui; Patrick G. Ndungu; Jihai Tang; Zhuxiu Zhang; Xu Qiao (Chemical Engineering Journal, 2025)

Corrigendum to “Chitosan/rutin multifunctional hydrogel with tunable adhesion, anti-inflammatory and antibacterial properties for skin wound healing” [Carbohydr. Polym. 343 (2024) 122492 - Ran An; Chenyu Shi; Yan Tang; Zan Cui; Yinping Li; Zhiyong Chen; Min Xiao; Li Xu (Carbohydrate Polymers, 2025)

Response of ammonium transformation in bioanodes to potential regulation: Performance, electromicrobiome and implications - Xin Tang; Qianjing Yao; Xiaodun Jiang; Chunlin Wang; Yang Liu; Cui Li; Yanlong Chen; Wenzong Liu; Fan Chen; Yuheng Wang (Bioresource Technology, 2025)

Selective Activation of G Protein–Coupled Estrogen Receptor 1 (GPER1) Reduces ER Stress and Pyroptosis via AMPK Signaling Pathway in Experimental Subarachnoid Hemorrhage - Yidan Liang; Wenqiao Fu; Yin Tang; Hongjiang Ye; Yanglingxi Wang; Chao Sun; Yi Xiang; Weiming Xiong; Min Cui; Yuanlin Chen; Ting Wang; Yongbing Deng (Molecular Neurobiology, 2025)

Incentivizing emission controls toward clean air and carbon neutrality in China: Perspectives from a risk-based approach for air quality management - Kimberly Tasha Jiayi Tang; Changqing Lin; Zhe Wang; Tianshu Zhang; Lu Li; Tze Wai Wong; Cui Guo (Science of The Total Environment, 2024)

NIR spectroscopy for quality assessment and shelf-life prediction of kiwifruit - Hongbo Li; Linlin Zhu; Na Li; Zhenbin Liu; Liheng Wang; Bimal Chitrakar; Dan Xu; Zhenkun Cui; Yanhua Tang; Liangbin Hu; Haizhen Mo (Postharvest Biology and Technology, 2024)

Total water level prediction at continental scale: Coastal ocean - Linlin Cui; Fei Ye; Y. Joseph Zhang; Haocheng Yu; Zhengui Wang; Saeed Moghimi; Gregory Seroka; Jack Riley; Shachak Pe'eri; Soroosh Mani; Edward Myers; Kyungmin Park; et al. (Ocean Modelling, 2024)

Applicability analysis of comprehensive drought index based on GRACE data in ten major river basins in China - Rong Wu; Zijun Wang; Chenfeng Cui; Yongxiang Li; Miao Tang; Jiangdong Chu; Renjie Xv; Chenrui Zhu; Shuo Wang; Yuli Li; Chengyuan Zhang; Zhannan Huang (Journal of Hydrology, 2024)

Relationship between root characteristics and saturated hydraulic conductivity in a grassed clayey soil - Ling-Xin Cui; Qing Cheng; Pui San So; Chao-Sheng Tang; Ben-Gang Tian; Cong-Ying Li (Journal of Hydrology, 2024)

Study on the multi-type drought propagation process and driving factors on the Tibetan Plateau - Heng Wang; Heng Zhao; Fuqiang Wang; Bing Yan; Lei Tang; Yutian Du; Lanbo Cui (Journal of Hydrology, 2024)

Construction mechanisms, synthesis strategies, and photocatalytic applications of homojunction catalysts: A review - Hao-wen Zhu; Rui-tang Guo; Qing-shan Wang; Cong Liu; Heng-fei Cui; Ming-yang Liu; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

Co-pyrolyzed biochar derived from microplastics and microalgae as peroxymonosulfate activator: Influence of microplastic types and analysis of systemic causes - Lei Qin; Shixian Qian; Xuerong Zhou; Naif Abdullah Al-Dhabi; Cui Lai; Dengsheng Ma; Xiuqin Huo; Lei Wu; Wangwang Tang (Journal of Environmental Chemical Engineering, 2024)

Breakthrough in soil remediation advancement: Nonthermal plasma powers polyvalent Ce-Mn (Hydro)oxide-enhanced nanographene to securely stabilize thallium-laden soils - Tao Huang; Dongping Song; Zhengfeng Hu; Yuxuan Feng; Jialin Cui; Mengyue Wu; Di Wu; Yinglan Luo; Yue Li; Yirong Jiang; Chaojun Tang; DanDan Wang (Journal of Environmental Chemical Engineering, 2024)

Sources, metabolism, health benefits and future development of saponins from plants - Jiang Wang; Xin Tang; Fei Liu; Bingyong Mao; Qiuxiang Zhang; Jianxin Zhao; Wei Chen; Shumao Cui (Food Research International, 2024)

The insights into sour flavor and organic acids in alcoholic beverages - Yan Yan; Mingxin Zou; Cui Tang; Hongyan Ao; Laping He; Shuyi Qiu; Cen Li (Food Chemistry, 2024)

Icariin promotes skeletal muscle mitochondrial biogenesis by the AMPK-PPARδ-PGC-1α signaling pathway: A potential mechanism for beneficial muscle function homeostasis - Yunlong Dong; Cuiru Ren; Hongyuan Tang; Jiabao Yan; Ying Zhang; Linchao Fan; Guangning Kou; Zhenwei Cui (Food Bioscience, 2024)

Enhancing the anti-fatigue effect of ginsenoside extract by Bifidobacterium animalis subsp. lactis CCFM1274 fermentation through biotransformation of Rb1, Rb2 and Rc to Rd - Xin Tang; Cencen Liu; Bulei Wang; Mingjun Zhang; Bingyong Mao; Qiuxiang Zhang; Jianxin Zhao; Shumao Cui (Food Bioscience, 2024)

Dynamic mechanisms of the collapse of wet granular columns: Insights from experiments and DEM simulations - Yu Wang; Jinbo Tang; Peng Cui (Computers and Geotechnics, 2024)

A flexible and superhydrophobic PVDF-HFP@PVA bilayer enables high-performance radiative cooling and thermal management - Jun-Heng Fu; Qigong Zhang; Minglei Yan; Wei Tang; Yun Zeng; Yuntao Cui; Mingkuan Zhang; Hongwei Deng; Hao Kang; Xinlong Sun; Liang Qiao; Hongzhang Wang; et al. (Chemical Engineering Journal, 2024)

Cytological mapping of a powdery mildew resistance locus PmRc1 based on wheat-Roegneria ciliaris structural rearrangement library - Menghao Cheng; Huajian Zhang; Yao Zhang; Xiong Tang; Zongkuan Wang; Xu Zhang; Xinying Song; Xingyue Li; Huimin Cui; Tong Wang; Rongrong Song; Jin Xiao; et al. (Theoretical and Applied Genetics, 2024)

A loss-of-function mutation in OsTZF5 confers sensitivity to low temperature and effects the growth and development in rice - Limin Wang; Ru Wang; Xin Cai; Huiqi Zheng; Yuxing Huang; Yuechen Li; Mingyue Cui; Mingli Lin; Huiwu Tang (Plant Molecular Biology, 2024)

Description and genomic characterization of Cohnella caldifontis sp. nov., isolated from hot springs in Yunnan province, south-west China - Ming-Xian Xiang; Cui-Ping Miao; Dian-Yan Zhang; Juan Wang; Yi-Qing Li; Min Yin; ShuKun Tang (Antonie van Leeuwenhoek, 2024)

Recent updates in anti-glycation strategies: selection of natural products and lactic acid bacteria as potential inhibitors based on the multi-pathway anti-glycation targets - Kaiyan Yue; Bingyong Mao; Xin Tang; Qiuxiang Zhang; Jianxin Zhao; Shumao Cui; Wei Chen (Critical Reviews in Food Science and Nutrition, 2024)

Transmission of carbapenem-resistant enterobacterales producing NDM-5 during the broiler breeding process in China - Ke Wu; Yuanyuan Zhang; Wei Xu; Xiaolong Lin; Cui Li; Juan Wang; Ruichao Li; Yizhi Tang; Changwei Lei; Hongning Wang (Veterinary Microbiology, 2024)

Effect of urban morphology on microclimate and building cluster energy consumption in cold regions of China - Peng Cui; Jiaqi Lu; Yutong Wu; Jingnan Tang; Jinjian Jiang (Sustainable Cities and Society, 2024)

Exploring the association between multi-mode transport and the built environment: A comparative study of metro, bus, taxi, and shared bike use - Zhitao Li; Jinjun Tang; Wenkang Zhang; Yifeng Ji; Lida Cui; Cheng Hu; Chuyun Zhao (Sustainable Cities and Society, 2024)

Bacterial membrane vesicles from swine farm microbial communities harboring and safeguarding diverse functional genes promoting horizontal gene transfer - Jinpeng Li; Chao Li; Yun Han; Jian Yang; Yulian Hu; Heting Xu; Yi Zhou; Jing Zuo; Yizhi Tang; Changwei Lei; Cui Li; Hongning Wang (Science of The Total Environment, 2024)

Distribution characteristics and risk assessment of fluoride in surface water of urban typical rivers - Ruixue Mu; Kangping Cui; Yihan Chen; Yuchao Tang; Kun Wang; Shijie Sun (Science of The Total Environment, 2024)

Overexpression of the receptor-like cytoplasmic kinase SZE1 positively regulates the PTI signaling pathway in Arabidopsis - Junhao Li; Jinya Guo; Yang Hu; Junmei Cui; Yan Huang; Yizu Wang; Yao Tang; Qiqi Wu; Zhihong Diao; Jinbo Shen; Yi Cai (Physiological and Molecular Plant Pathology, 2024)

A comparative study on stability and flavor of additive-free oat milk obtained by different heat pretreatments (blanching and microwave) of oat kernels - Lulu Cui; Jiani Zhao; Qiuju Jia; Jian Tang; Fang Zhong; Jing Lu; Sumei Zhou (Journal of Cereal Science, 2024)

Spatiotemporal variability of leaf critical senescence age across northern lands and its key drivers - Xingli Xia; Cuihai You; Ruiling Lu; Ning Wei; Chenyu Bian; Ying Du; Erqian Cui; Songbo Tang; Zhiqin Tu; Jiaye Ping; Kun Huang; Jianyang Xia (Global and Planetary Change, 2024)

Characteristic volatile compounds contributed to aroma of braised pork and their precursor sources - Yishun Yao; Meigui Huang; Xiaomin Wang; Jingyang Yu; Heping Cui; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Chemistry, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

Kirkendall effect enhanced sustained-release Fe-C composites for long-term reductive dechlorination of trichloroethylene: Interfacial reactions and slow-release degradation - Daibing Hou; Xuedan Cui; Yiming Tang; Meng Liu; Hantong Qie; Pengjie Zhao; Wenpeng Leng; Nan Luo; Huilong Luo; Wenxia Wei; Aijun Lin; Tianwen Zheng (Chemical Engineering Journal, 2024)

Microsphere LiMn0.6Fe0.4PO4/C cathode with unique rod-like secondary architecture for high energy lithium ion batteries - Liang Xie; Jiawu Cui; Yongliang Ma; Weibo Hua; Zhen Wang; Hao Wu; Taifan Yang; Zexun Tang; Xiangwen Gao; Xiaowei Wang; Wei Tang; Yuping Wu (Chemical Engineering Journal, 2024)

Advanced design of metal single-atom (Pt, Mn, Fe or Cu) loaded S-Ni(OH)2 nanosheets array catalysts to achieve high-performance overall water splitting - Wenhui Fang; Tingting Tang; Min Li; Shixian Xin; Ying Wu; Yutao Cao; Zhize Yu; Wei Cui; Zengxi Li; Hong Zhao (Chemical Engineering Journal, 2024)

Chitosan/rutin multifunctional hydrogel with tunable adhesion, anti-inflammatory and antibacterial properties for skin wound healing - Ran An; Chenyu Shi; Yan Tang; Zan Cui; Yinping Li; Zhiyong Chen; Min Xiao; Li Xu (Carbohydrate Polymers, 2024)

Autophagy activation ameliorates the fibrosis of trabecular meshwork cells induced by TGFβ2 through the promotion of fibrotic proteins degradation - Gang Wang; Rumeng Zhao; Zhenyang Guo; Huiling Cui; Di Wang; Jing Ren; Shichao Zhu; Ke Zhang; Bo Tang; Jingyi Zhang; Peng Li; Shichao Duan; et al. (Human Cell, 2024)

High-similarity sheep face recognition method based on a Siamese network with fewer training samples - Xiwen Zhang; Chuanzhong Xuan; Yanhua Ma; Zhaohui Tang; Jiahe Cui; Haoyu Zhang (Computers and Electronics in Agriculture, 2024)

Assessing the effects of urban green spaces metrics and spatial structure on LST and carbon sinks in Harbin, a cold region city in China - Peng Cui; Dawei Xv; Jingnan Tang; Jiaqi Lu; Yutong Wu (Sustainable Cities and Society, 2024)

Roof greening in major Chinese cities possibly afford a large potential carbon sink - Chao Yang; Yinghui Zhang; Min Chen; Song Zhu; Yuzhi Tang; Zhixin Zhang; Wei Ma; Huizeng Liu; Junyi Chen; Bohui Tang; Dejin Zhang; Zhengdong Huang; et al. (Science Bulletin, 2024)

Anti-inflammatory and cytotoxicity nitrogenous merosesquiterpenoids from the sponge Pseudoceratina purpurea - Xiaoli Yu; Xiao Han; Yue Mi; Yongpeng Cui; Anran Fu; Kun Liu; Xiaobin Li; Xuli Tang; Guoqiang Li (Phytochemistry, 2024)

Excellent performance of Ce doped CoMn2O4/TiO2 catalyst in NH3-SCR of NO under H2O&SO2 conditions - Fengyu Gao; Yaxin Niu; Yue Cui; Yuanyuan Liu; Ning Luo; Jiajun Wen; Erhong Duan; Chengzhi Wang; Honghong Yi; Yuansong Zhou; Xiaolong Tang (Journal of Environmental Chemical Engineering, 2024)

Potentially toxic element source apportionment and risk assessment in agricultural soils around a large-scale Pb-Zn mine in Southwest China - Heng Wei; Xuekui Niu; Minmin Li; Canwen Cui; Zhonghua Wei; Wei Long; Man Tang; Hong Yu; Peng Zhang; Liping He; Bo Pan (Journal of Environmental Chemical Engineering, 2024)

Source apportionment and specific-source-site risk of quinolone antibiotics for effluent-receiving urban rivers and groundwater in a city, China - Yu Zhao; Yuanmeng Song; Lulu Zhang; Bo Zhao; Mengqi Lu; Jiansheng Cui; Wenzhong Tang (Journal of Environmental Sciences, 2024)

Improving the texture of braised pork by gradient-temperature heating and its molecular mechanism - Yishun Yao; Meigui Huang; Xiaomin Wang; Jingyang Yu; Heping Cui; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Research International, 2024)

Differentiated texture and lipid-lowering effect of cooked pork belly by different cooking regimes: Insights from myofibrillar protein aggregation and dissociation, micromorphology - Yishun Yao; Meigui Huang; Xiaomin Wang; Jingyang Yu; Heping Cui; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Bioscience, 2024)

Vitamin C as a functional enhancer in the non-specific immune defense, antioxidant capacity and resistance to low-temperature stress of juvenile mud crab, Scylla paramamosain - Zheng Tang; Shichao Xie; Yuhui Cui; Wenhao Zhan; Yao Deng; Hongyu Peng; Haiqing Cao; Yinqiu Tian; Min Jin; Peng Sun; Yingzhao Zhang; Feng Tang; et al. (Fish & Shellfish Immunology, 2024)

Deficit irrigation combined with a high planting density optimizes root and soil water–nitrogen distribution to enhance cotton productivity in arid regions - Fengquan Wu; Qiuxiang Tang; Jianping Cui; Liwen Tian; Rensong Guo; Liang Wang; Zipiao Zheng; Na Zhang; Yanjun Zhang; Tao Lin (Field Crops Research, 2024)

Spatial distribution and enrichment characteristics of selenium in paddy soil and rice around the Dongting Lake - Rui Liu; Weijun Zhou; De Yu; Guiduo Shang; Yuzhou Zhou; Zhangqian Xu; Dou Tang; Haojie Cui; Chaolin Liao (Environmental Pollution, 2024)

Synergistic effects of biochar and laccase on nitrogen conversation and degradations of two artificial sweeteners during the sewage sludge composting - Jishao Jiang; Huilin Cui; Zhuyu Tang; Shipeng Wang; Ke Cheng; Chunyan Zhang; Tonghuan Yu; Jinghua Lv; Fuqiang Yu; Dong Liu (Chemical Engineering Journal, 2024)

Reactive complexes mediated singlet oxygen production by MnO2 catalyzed peracetic acid: Characterization and DFT study - Xiuqin Huo; Huan Yi; Dengsheng Ma; Fuhang Xu; Huchuan Yan; Lin Tang; Guangming Zeng; Cui Lai (Chemical Engineering Journal, 2024)

Phenotypic and genetic effect of carotid intima-media thickness on the risk of stroke - Wenqiang Zhang; Jingwei Zhu; Xuan Wu; Tianle Feng; Wei Liao; Xuan Li; Jianci Chen; Li Zhang; Chenghan Xiao; Huijie Cui; Chao Yang; Peijing Yan; et al. (Human Genetics, 2024)

Warming decouples associations between microbial network complexity and ecosystem multifunctionality in alpine grasslands - Kui Wang; Kai Xue; Wenjing Liu; Biao Zhang; Wenchao Wu; Runchen Zhao; Lizhen Cui; Zongsong Wang; Shutong Zhou; Li Tang; Junfu Dong; Jianqing Du; et al. (Agriculture, Ecosystems & Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Immunosuppressive alkaloids from Narcissus tazetta subsp. Chinensis and the mechanism of (+)-narciclasine in vitro and in vivo - Wen-Ling Wang; Xiu-Yin Wu; Xing-Yan Luo; Yu-Qin Tang; Jia Cui; Xin-Yue Huang; Yu-Chen Jiang; Yang Liu; Li-Mei Li (Phytochemistry, 2024)

The nonlinear rainfall–quick flow relationships in a humid mountainous area: Roles of soil thickness and forest type - Fei Wang; Genxu Wang; Junfang Cui; Li Guo; Xiangyu Tang; Ruxin Yang; Jianqing Du; Mohammad Sadegh Askari (Journal of Hydrology, 2024)

Electron cycling mechanism in Fe/Mn DSAzyme accelerates BPA degradation and nanoenzyme regeneration - Xinxin Lv; Aolan Shu; Lei Shu; Huilai Liu; Yao Liu; Kangping Cui; Yuchao Tang; Xing Chen (Journal of Hazardous Materials, 2024)

Beyond grassland degradation: Pathways to resilience for pastoralist households in alpine grassland ecosystems - Tong Li; Ranjay K. Singh; Lizhen Cui; Rajiv Pandey; Hongdou Liu; Zhihong Xu; Li Tang; Jianqing Du; Xiaoyong Cui; Yanfen Wang (Journal of Environmental Management, 2024)

Environmental endocrine disrupting chemical 4-tert-butylphenol induced calcium overload and subsequent autophagy impairment via miRNA-363/CACNA1D Axis in epithelioma papulosum cyprini cells - Jiawen Cui; Zhenda Liang; Yuhao Liu; Zhiyu Hao; You Tang; Li Zhou; Xiaohua Teng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Revealing the mechanism behind the highly selective separation of 1,4-butyrolactone from n-methylpyrrolidone using nonporous adaptive crystals of perethylated pillar[5]arene - Minlei Yin; Chen Yang; Duanlian Tang; Shiyin Huang; Xiaoyu Lou; Rongkai Cui; Changshen Ye; Jie Chen; Ting Qiu (Chemical Engineering Journal, 2024)

Manganese (III) phthalocyanine complex nanoassembly: Oxygen-Independent generation of superoxide radicals and singlet oxygen for ultrasound-augmented chemodynamic therapy - Yun Sun; Chao Li; Zhaoyang Liu; Chaojie Tang; Zhankun Cui; Zhiguo Zhou; Qian Liu; Wu Wang; Shiping Yang; Hong Yang (Chemical Engineering Journal, 2024)

Effects of exogenous thermophilic bacteria and ripening agent on greenhouse gas emissions, enzyme activity and microbial community during straw composting - Yuewei He; Yuedong He; Naif Abdullah Al-Dhabi; Peng Gao; Hongli Huang; Binghua Yan; Xinwei Cui; Wangwang Tang; Jiachao Zhang; Yaoxiong Lu; Fuyuan Peng (Bioresource Technology, 2024)

Recent advance in quality preservation of non-thermal preservation technology of fresh mushroom: a review - Weiling Guo; Xin Tang; Shumao Cui; Qiuxiang Zhang; Jianxin Zhao; Bingyong Mao; Hao Zhang (Critical Reviews in Food Science and Nutrition, 2024)

A Study on the Impact of Environmental Factors on Chub Mackerel Scomber japonicus Fishing Grounds Based on a Linear Mixed Model - Jiasheng Li; Fenghua Tang; Yumei Wu; Shengmao Zhang; Weifeng Zhou; Xuesen Cui (Fishes, 2024)
Chub mackerel (Scomber japonicus) is a commercially important fish species which are widely distributed in the North Pacific. Based on the fishery data from China’s high-sea light-purse seine fishing from 2014 to 2020 and the marine environment factors, a mixed linear model considering the actual spatiotemporal stratification of the catch per unit effort (CPUE) was established to analyze the fixed and random effects of marine environmental factors on the CPUE of chub mackerel and to investigate the relationship between the abundance of chub mackerel resources in the Northwest Pacific and two marine environmental factors: sea surface temperature (SST) and chlorophyll-a concentration (CHL). The results showed that SST had a significant fixed effect on the CPUE. In contrast, the natural logarithm of chlorophyll (logCHL) had no fixed effect on the CPUE. Based on the monthly analysis, random fluctuations were observed in the impact of logCHL on the CPUE. LogCHL and CPUE show a positive correlation during spawning and wintering periods and a negative correlation during the feeding period. The study showed that when fishery sampling data exhibit spatiotemporal stratification, linear mixed models can effectively incorporate both the fixed and random effects of environmental factors on the CPUE of chub mackerel. Linear mixed models can play an important role in analyzing the fluctuations in resource abundance and the mechanisms governing the formation of fishing grounds for chub mackerel in the Northwest Pacific.

MARCH1 and MARCH2 inhibit pseudorabies virus replication by trapping the viral cell-to-cell fusion complex in trans-Golgi network - Rui Huang; Cui-Hong Rao; Yuan-Zhe Bai; Changqing Yu; Meng Chen; Jin-Mei Peng; Shi-Jia Xu; Yue Sun; Meng Fandan; Chuang Lyu; Mirwaise Khan; Tong-Qing An; et al. (Veterinary Microbiology, 2024)

Field investigation of unsaturated hydraulic conductivity using actively heated fiber-optic technology - Jie Liu; Yu-Jun Cui; Meng-Ya Sun; Kai Gu; Jun-Cheng Yao; Chao-Sheng Tang; Bin Shi (Journal of Hydrology, 2024)

Exploration of carbonyl compounds in red-fleshed kiwifruit wine and perceptual interactions among non-volatile organic acids - Cen Li; Cui Tang; Xiangyong Zeng; Yi Zhang; Laping He; Yan Yan (Food Chemistry, 2024)

Directed preparation of N-(1-deoxy-d-ribulos-1-yl)-glutathione during short-term high temperature dehydration: Suppressing the side reactions of glutathione - Linhui Feng; Heping Cui; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Bioscience, 2024)

Dietary lauric acid promoted antioxidant and immune capacity by improving intestinal structure and microbial population of swimming crab (Portunus trituberculatus) - Wenhao Zhan; Hongyu Peng; Shichao Xie; Yao Deng; Tingting Zhu; Yuhui Cui; Haiqing Cao; Zheng Tang; Min Jin; Qicun Zhou (Fish & Shellfish Immunology, 2024)

Elastic, Janus 3D evaporator with arch-shaped design for low-footprint and high-performance solar-driven zero-liquid discharge - Ying Chen; Ruien Hou; Longjuan Yang; Chen Chen; Jianguo Cui; Tong Zhou; Yan Zhao; Jiaxin Song; Zimeng Fan; Yu Tang; Fengjuan Chen (Desalination, 2024)

Lowering the burning rate temperature coefficient of composite propellant by compensating its burning surface through thermal expansion and contraction in microstructure - Suhang Chen; Zhenhua Tang; Kui Tang; Lianpeng Cui; Zhao Qin; Kangzhen Xu (Chemical Engineering Journal, 2024)

Important role of carbon doping in photocatalytic peroxymonosulfate activation of carbon nitride for efficient 4-Chlorophenol degradation - Yuan Zhang; Kangping Cui; Xueyan Liu; Minshu Cui; Xing Chen; Yuchao Tang; Haiyang Li; Kun Wang (Chemical Engineering Journal, 2024)

Removal of artificial sweeteners in wastewater treatment plants and their degradation during sewage sludge composting with micro- and nano-sized kaolin - Jishao Jiang; Rui Hou; Huilin Cui; Zhuyu Tang; Yousif Abdelrahman Yousif Abdellah; Caspar C.C. Chater; Ke Cheng; Fuqiang Yu; Dong Liu (Bioresource Technology, 2024)

The Role of KDM2A and H3K36me2 Demethylation in Modulating MAPK Signaling During Neurodevelopment - Zongyao Ren; Haiyan Tang; Wendiao Zhang; Minghui Guo; Jingjie Cui; Hua Wang; Bin Xie; Jing Yu; Yonghao Chen; Ming Zhang; Cong Han; Tianyao Chu; et al. (Neuroscience Bulletin, 2024)

Absorption, metabolism, bioactivity, and biotransformation of epigallocatechin gallate - Shuling Zhang; Bingyong Mao; Shumao Cui; Qiuxiang Zhang; Jianxin Zhao; Xin Tang; Wei Chen (Critical Reviews in Food Science and Nutrition, 2024)

Biochar reduces antibiotic transport by altering soil hydrology and enhancing antibiotic sorption - Xiang-Yu Tang; Wen-Min Yin; Guang Yang; Jun-Fang Cui; Jian-Hua Cheng; Fei Yang; Xiao-Yu Li; Chun-Yan Wu; Sen-Gen Zhu (Journal of Hazardous Materials, 2024)

Difference comparison of characteristic aroma compounds between braised pork cooked by traditional open-fire and induction cooker and the potential formation cause under electromagnetic cooking - Xiaomin Wang; Meigui Huang; Yishun Yao; Jingyang Yu; Heping Cui; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Research International, 2024)

Multi-omics association study of hexadecane degradation in haloarchaeal strain Halogranum rubrum RO2-11 - HeLang Huang; CaiYun Xie; ZiYuan Xia; ZhaoYong Sun; YaTing Chen; Min Gou; YueQin Tang; HengLin Cui; XiaoLei Wu (Environmental Research, 2024)

Predicting the deformation of compacted loess used for land creation based on the field monitoring with fiber-optic technology - Jie Liu; Bin Shi; Yu-Jun Cui; Meng-Ya Sun; Kai Gu; Jun-Cheng Yao; Chao-Sheng Tang (Engineering Geology, 2024)

Quick and automatic detection of co-seismic landslides with multi-feature deep learning model - Wenchao Huangfu; Haijun Qiu; Peng Cui; Dongdong Yang; Ya Liu; Bingzhe Tang; Zijing Liu; Mohib Ullah (Science China Earth Sciences, 2024)

Dominant role of the non‐forest woody vegetation in the post 2015/16 El Niño tropical carbon recovery - Lei Fan; Tianxiang Cui; Jean‐Pierre Wigneron; Philippe Ciais; Stephen Sitch; Martin Brandt; Xin Li; Shuli Niu; Xiangming Xiao; Jérome Chave; Chaoyang Wu; Wei Li; et al. (Global Change Biology, 2024)
The extreme dry and hot 2015/16 El Niño episode caused large losses in tropical live aboveground carbon (AGC) stocks. Followed by climatic conditions conducive to high vegetation productivity since 2016, tropical AGC are expected to recover from large losses during the El Niño episode; however, the recovery rate and its spatial distribution remain unknown. Here, we used low‐frequency microwave satellite data to track AGC changes, and showed that tropical AGC stocks returned to pre‐El Niño levels by the end of 2020, resulting in an AGC sink of Pg C year −1 during 2014–2020. This sink was dominated by strong AGC increases ( Pg C year −1 ) in non‐forest woody vegetation during 2016–2020, compensating the forest AGC losses attributed to the El Niño event, forest loss, and degradation. Our findings highlight that non‐forest woody vegetation is an increasingly important contributor to interannual to decadal variability in the global carbon cycle.

Diagnosis of the accuracy of land cover classification using bootstrap resampling - Tong Yang; Binghong Han; Xiaofei He; Ziqi Ye; Yongli Tang; Jiexin Lin; Xia Cui; Jian Bi (International Journal of Remote Sensing, 2024)

Synergistic analysis of lignin degrading bacterial consortium and its application in rice straw fiber film - Jinghong Wang; Wei Zhang; Chenying Wu; Yanhua Hong; Guinan Shen; Weiwei Wang; Hongzhi Tang; Kazuhiro Mochidzuki; Zongjun Cui; Aman Khan; Weidong Wang (Science of The Total Environment, 2024)

Celastrol induced the autophagy of spermatogonia cells contributed to tripterygium glycosides-related testicular injury - Dong-Xiao Cui; Ze-Chen Niu; Xi Tang; Chun-Zhou Cai; Ding-Qiao Xu; Rui-Jia Fu; Wen-Juan Liu; Yu-Wei Wang; Yu-Ping Tang (Reproductive Toxicology, 2024)

A Pueraria lobata root extract alleviates high-fat diet-induced non-alcoholic fatty liver disease by modulating the gut microbiota and associated metabolites - Xin Tang; Yongkang Zhou; Fei Liu; Botao Wang; Bingyong Mao; Qiuxiang Zhang; Jianxin Zhao; Wei Chen; Shumao Cui (Food Bioscience, 2024)

Natural magnetite as an efficient green catalyst boosting peroxydisulfate activation for pollutants degradation - Xuedan Cui; Daibing Hou; Yiming Tang; Hantong Qie; Ruiqing Xu; Pengjie Zhao; Aijun Lin; Meng Liu (Chemical Engineering Journal, 2024)

The Cambrian microfossil Qingjiangonema reveals the co-evolution of sulfate-reducing bacteria and the oxygenation of Earth’s surface - Linhao Cui; Kelei Zhu; Ruiyun Li; Chao Chang; Laiyuan Wu; Wei Liu; Dongjing Fu; Peiyu Liu; Hao Qiu; Guoqiang Tang; Qiuli Li; Robert R. Gaines; et al. (Science Bulletin, 2024)

Trophic transfer of antibiotics in the benthic-pelagic coupling foodweb in a macrophyte-dominated shallow lake: The importance of pelagic-benthic coupling strength and baseline organism - Lulu Zhang; Sai Gao; Yuanmeng Song; Haoda Chen; Linjing Wang; Yu Zhao; Jiansheng Cui; Wenzhong Tang (Journal of Hazardous Materials, 2024)

Laccase immobilization and its degradation of emerging pollutants: A comprehensive review - Hao Wang; Lu-Xin Tang; Yi-Fan Ye; Jin-Xin Ma; Xin Li; Jing Si; Bao-Kai Cui (Journal of Environmental Management, 2024)

Rock and ice avalanche-generated catastrophic debris flow at Chamoli, 7 February 2021: New insights from the geomorphic perspective - Hao Wang; Peng Cui; Yao Li; Jinbo Tang; Ruilong Wei; Anna Yang; Liqin Zhou; Nazir Ahmed Bazai; Guotao Zhang (Geomorphology, 2024)

Efficiency and power enhancement strategies for methane direct injection argon power cycle engines - Chenxu Wang; Jun Deng; Weiqi Ding; Yongjian Tang; Wenyi Cui; Xiang Su; Liguang Li (Fuel, 2024)

The same species, different nutrients: Lipidomics analysis of muscle in mud crabs (Scylla paramamosain) fed with lard oil and fish oil - Xuexi Wang; Shihui Cui; Jinjin Liu; Zihao Ye; Yifang Xu; Ziyi Wang; Mengyao Tang; Ziping Zhang; Yi Zhang; Weiqing Huang (Food Chemistry, 2024)

Highly efficient molybdenum nanostructures for solar thermophotovoltaic systems: One-step fabrication of absorber and design of selective emitter - Tao Cui; Yan Shen; Ao Cheng; Zhe Liu; Shi Jia; Shuai Tang; Lei Shao; Huanjun Chen; Shaozhi Deng (Chemical Engineering Journal, 2024)

Electroacupuncture Exerts Analgesic Effects by Restoring Hyperactivity via Cannabinoid Type 1 Receptors in the Anterior Cingulate Cortex in Chronic Inflammatory Pain - Junshang Wu; Libo Hua; Wenhao Liu; Xiaoyun Yang; Xiaorong Tang; Si Yuan; Sheng Zhou; Qiuping Ye; Shuai Cui; Zhennan Wu; Lanfeng Lai; Chunzhi Tang; et al. (Molecular Neurobiology, 2024)
As one of the commonly used therapies for pain-related diseases in clinical practice, electroacupuncture (EA) has been proven to be effective. In chronic pain, neurons in the anterior cingulate cortex (ACC) have been reported to be hyperactive, while the mechanism by which cannabinoid type 1 receptors (CB1Rs) in the ACC are involved in EA-mediated analgesic mechanisms remains to be elucidated. In this study, we investigated the potential central mechanism of EA analgesia. A combination of techniques was used to detect the expression and function of CB1R, including quantitative real-time PCR (q-PCR), western blot (WB), immunofluorescence (IF), enzyme-linked immunosorbent assay (ELISA), and in vivo multichannel optical fibre recording, and neuronal activity was examined by in vivo two-photon imaging and in vivo electrophysiological recording. We found that the hyperactivity of pyramidal neurons in the ACC during chronic inflammatory pain is associated with impairment of the endocannabinoid system. EA at the Zusanli acupoint (ST36) can reduce the hyperactivity of pyramidal neurons and exert analgesic effects by increasing the endocannabinoid ligands anandamide (AEA), 2-arachidonoylglycerol (2-AG) and CB1R. More importantly, CB1R in the ACC is one of the necessary conditions for the EA-mediated analgesia effect, which may be related to the negative regulation of the N-methyl-D-aspartate receptor (NMDAR) by the activation of CB1R downregulating NR1 subunits of NMDAR (NR1) via histidine triad nucleotide-binding protein 1 (HINT1). Our study suggested that the endocannabinoid system in the ACC plays an important role in acupuncture analgesia and provides evidence for a central mechanism of EA-mediated analgesia.

Power law in species–area relationship overestimates bacterial diversity in grassland soils at larger scales - Biao Zhang; Kai Xue; Wenjing Liu; Shutong Zhou; Shipeng Nie; Yichao Rui; Li Tang; Zhe Pang; Linfeng Li; Junfu Dong; Cong Xu; Lili Jiang; et al. (Global Ecology and Biogeography, 2024)
Aim Species–area relationships (SAR) are widely utilized for estimating the species richness and its spatial turnover across various scales. Despite the prevalent characterization of SAR using the power law in many microbial community studies, its efficacy remains unvalidated. This study aims to characterize the microbial SAR and its mechanisms in alpine grassland soils on the Qinghai‐Tibet Plateau (QTP). Location Qinghai‐Tibet Plateau, China. Time Period August 2014. Major Taxa Studied Soil bacteria. Methods Soil samples were collected from five alpine grassland sites on the QTP. Employing a nested sampling strategy at each site, soil samples were collected in plot sizes ranging from 0.5 × 0.5 m 2 to 2048 × 2048 m 2 . Soil bacterial communities were analysed by sequencing 16S ribosomal RNA gene amplicons using an Illumina MiSeq. Results The bacterial SAR exhibited a logarithmic power law ( R 2 : 0.952–0.999), outperforming the power law ( R 2 : 0.701–0.852). Consequently, the most widely adopted power law led to an overestimation of species richness by up to 15.07% in areas >256 × 256 m 2 , and the regional maximum theoretical richness based on Chao1 by up to 9.88%. Mechanistically, the passive sampling hypothesis was refuted through the rarefied species richness analysis, and the disproportionate effect hypothesis was rejected based on analyses of the effective numbers of species number conversions for the probability of interspecific encounters ( S PIE ). Notably, Pearson and multiple linear regression analyses indicated that the spatial turnover of bacterial richness was determined by the environmental heterogeneity ( R 2 : 0.855–0.999), rather or better than environmental variables themselves, supporting the ‘environment heterogeneity hypothesis’. Main Conclusions Soil bacterial SAR in alpine grasslands exhibited a logarithmic power relationship. Spatial turnover was primarily governed by the environmental heterogeneity. In contrast, the traditional power law leads to an overestimation of soil bacterial diversity at the regional scale.

Drought shortens subtropical understory growing season by advancing leaf senescence - Huanfa Sun; Liming Yan; Zhao Li; Wanying Cheng; Ruiling Lu; Xingli Xia; Jiaye Ping; Chenyu Bian; Ning Wei; Cuihai You; Songbo Tang; Ying Du; et al. (Global Change Biology, 2024)
Subtropical forests, recognized for their intricate vertical canopy stratification, exhibit high resistance to extreme drought. However, the response of leaf phenology to drought in the species‐rich understory remains poorly understood. In this study, we constructed a digital camera system, amassing over 360,000 images through a 70% throughfall exclusion experiment, to explore the drought response of understory leaf phenology. The results revealed a significant advancement in understory leaf senescence phenology under drought, with 11.75 and 15.76 days for the start and end of the leaf‐falling event, respectively. Pre‐season temperature primarily regulated leaf development phenology, whereas soil water dominated the variability in leaf senescence phenology. Under drought conditions, temperature sensitivities for the end of leaf emergence decreased from −13.72 to −11.06 days °C −1 , with insignificance observed for the start of leaf emergence. Consequently, drought treatment shortened both the length of the growing season (15.69 days) and the peak growth season (9.80 days) for understory plants. Moreover, this study identified diverse responses among intraspecies and interspecies to drought, particularly during the leaf development phase. These findings underscore the pivotal role of water availability in shaping understory phenology patterns, especially in subtropical forests.

New butanolide derivatives from the marine derived fungus Aspergillus terreus GZU-31-1 by chemical epigenetic manipulation - Yuwei Zhou; Xiaocong Chen; Yuqian Tang; Yena Liu; Zhongxiang Zhao; Hui Cui (Natural Product Research, 2024)

Study on the Adsorption Performance of a Vortex Suction Cup under Varying Diameters of Underwater Structure Tubes - Qinyun Tang; Ying Du; Zhaojin Liu; Shuo Zhang; Qiang Zhao; Yingxuan Li; Liquan Wang; Tong Cui; Gang Wang (Journal of Marine Science and Engineering, 2024)
In certain precision work scenarios, underwater robots require the ability to adhere to surfaces in order to perform tasks effectively. An efficient and stable suction device plays a pivotal role in the functionality of such underwater robots. The vortex suction cup, distinguished by its uncomplicated design, high suction efficiency, and capability for non-contact adhesion, holds significant promise for integration into underwater robotic systems. This paper presents a novel design for a vortex suction cup and investigates its suction force and torque when encountering surfaces with varying curvature radii using Computational Fluid Dynamics (CFD) simulations and experimental testing. These findings offer valuable insights for the development of robots capable of adapting to underwater structures of different dimensions. Results from both experiments and simulations indicate that reducing the curvature radius of the adhered surface results in a decrease in suction force and an increase in torque exerted on the suction cup. As the adhered surface transitions from flat to a curvature radius of 150 mm, the adhesion force of our proposed vortex suction cup decreases by approximately 10%, while the torque increases by approximately 20% to 30%. Consequently, the adhesion efficiency of the suction cup decreases by about 25% to 30%.

Mitochondrial uptake of aristolactam I plays a critical role in its toxicity - Yan Zhou; Ruirui Cui; Mingkang Zhang; Fabing Tang; Xiaohua Ma; Xin’an Wu (Toxicology Letters, 2024)

Interactions of ferrate(VI) and aquatic humic substances in water treatment - Junkui Cui; Zepei Tang; Qiufeng Lin; Lisitai Yang; Yang Deng (Science of The Total Environment, 2024)

Antibiotic resistance genes and mobile genetic elements in different rivers: The link with antibiotics, microbial communities, and human activities - Lulu Zhang; Haoda Chen; Sai Gao; Yuanmeng Song; Yu Zhao; Wenzhong Tang; Jiansheng Cui (Science of The Total Environment, 2024)

ZIF-67 based CoS2 self-assembled on graphitic carbon nitride microtubular for sensitive electrochemical detection of paraquat in fruits - Chenghu Yuan; Cui Tang; Xuejia Zhan; Menglin Zhou; Lei Zhang; Wen-Tong Chen; Abdukader Abdukayum; Guangzhi Hu (Journal of Hazardous Materials, 2024)

Selective flotation separation mechanism of LFPs and graphite electrode materials using CMC as inhibitor - Cui Wang; Erfa Ding; Xiongxing Zhang; Yong Zeng; Wei Sun; Zhao Wei; Yue Yang; Honghu Tang (Journal of Environmental Chemical Engineering, 2024)

Rapid preparation of the Amadori rearrangement product of glutamic acid - xylose through intermittent microwave heating and its browning formation potential in microwave thermal processing - Xingwei Wang; Heping Cui; Xiaoming Zhang; Jingyang Yu; Shuqin Xia; Chi-Tang Ho (Food Research International, 2024)

Numerical investigations of translocation characteristics of nano-silica lunar dust across pulmonary surfactant monolayer - Kailiang Tang; Wen Gao; Dongxing Tao; Bin Wu; Yuan Xue; Haiwen Ge; Xinguang Cui (Environmental Pollution, 2024)

Partially oxidized mackinawite/biochar for photo-Fenton organic contaminant removal: Synergistically improve interfacial electron transfer and H2O2 activation - Binrong Li; Chen Wang; Na Li; Chunyang Chen; Zhi Zhu; Xu Tang; Yanhua Cui; Tingting Liu; Collins Kwashie Attatsi; Xuedong Wang (Environmental Pollution, 2024)

Two-dimensional interfacial enhanced CO2 adsorption performance of porous organic amine solids: Structure-activity relationships and DFT calculations - Pengchao Zang; Jiyun Tang; Hao Zhang; Xiaozhe Wang; Lin Cui; Juan Chen; Pei Zhao; Yong Dong (Chemical Engineering Journal, 2024)

Anti-aging effects and mechanisms of anthocyanins and their intestinal microflora metabolites - Bulei Wang; Xin Tang; Bingyong Mao; Qiuxiang Zhang; Fengwei Tian; Jianxin Zhao; Shumao Cui; Wei Chen (Critical Reviews in Food Science and Nutrition, 2024)

Meroterpenoids from the marine-derived fungus Aspergillus terreus GZU-31-1 exerts anti-liver fibrosis effects by targeting the Nrf2 signaling in vitro - Hui Cui; Yuqian Tang; Chunfang Yang; Huimei Deng; Lei Chen; Xueying Fan; Liping Zhu; Yena Liu; Zhongxiang Zhao; Tao Su (Phytochemistry, 2024)

Provenance and tectonic settings of the lower Permian siliciclastic rocks in central Inner Mongolia: Implications for the evolution of the Paleo-Asian Ocean - Xinyu Cui; Lizhi Shi; Xianchun Tang; Zhuozhuo Wang; Jinxi Wang; Lijun Cheng; Longming Li; Biao Wang; Xiaomeng Han; Kaijun Zhang (Marine and Petroleum Geology, 2024)

Plasticity of cold and heat stress tolerance induced by hardening and acclimation in the melon thrips - Hua-Qian Cao; Jin-Cui Chen; Meng-Qing Tang; Min Chen; Ary A. Hoffmann; Shu-Jun Wei (Journal of Insect Physiology, 2024)

Long-term exposure to reduced specific-size ambient particulate matter and progression of arterial stiffness among Chinese adults - Dankang Li; Shouling Wu; Linxi Tang; Shuohua Chen; Feipeng Cui; Yudiyang Ma; Run Liu; Jianing Wang; Yaohua Tian (Journal of Hazardous Materials, 2024)

Efficient photocatalytic NO removal with inhibited NO2 formation and catalyst loss over sponge-supported and functionalized g-C3N4 - Yin Tang; Wen Cui; Songxia Wang; Fan Dong (Journal of Hazardous Materials, 2024)

Unveiling the toxic effects, physiological responses and molecular mechanisms of tobacco (Nicotiana tabacum) in exposure to organic ultraviolet filters - Dong Jiang; Guoqun Yang; Li-Jun Huang; Kebin Chen; Yangcan Tang; Xin Pi; Runke Yang; Xia Peng; Chuantong Cui; Ning Li (Journal of Hazardous Materials, 2024)

Role of keystone drives polycyclic aromatic hydrocarbons degradation and humification especially combined with aged contaminated soil in co-composting - Jiayue Huang; Ziwei Jiang; Anyang Li; Fangzhi Jiang; Pengfei Tang; Jizhe Cui; Wenxuan Feng; Chang Fu; Qian Lu (Journal of Environmental Management, 2024)

The effects of iron-based nanomaterials (Fe NMs) on plants under stressful environments: Machine learning-assisted meta-analysis - Daibing Hou; Xuedan Cui; Meng Liu; Hantong Qie; Yiming Tang; Ruiqing Xu; Pengjie Zhao; Wenpeng Leng; Nan Luo; Huilong Luo; Aijun Lin; Wenxia Wei; et al. (Journal of Environmental Management, 2024)

Orbital-paced silicate weathering intensity and climate evolution across the Eocene-Oligocene transition in the southeastern margin of the Tibetan Plateau - He Tang; Hao Cui; Shu-Feng Li; Robert A. Spicer; Shi-Hu Li; Tao Su; Zhe-Kun Zhou; Caitlyn R. Witkowski; Vittoria Lauretano; Gang-Jian Wei (Global and Planetary Change, 2024)

Residential greenness and incident idiopathic pulmonary fibrosis: A prospective study - Linxi Tang; Feipeng Cui; Yudiyang Ma; Dankang Li; Jianing Wang; Run Liu; Yaohua Tian (Environmental Research, 2024)

Composition and release rates of chemicals in inkjet fabrics determined by non-targeted screening and targeted analysis - Xi Chen; Wenjing Han; Jingwen Chen; Huaijun Xie; Qing Xie; Minghua Zhu; Zhongyu Wang; Yunhan Cui; Weihao Tang (Environmental Pollution, 2024)

OsGEX3 affects anther development and improves osmotic stress tolerance in rice - Han Bao; Yuchao Cui; Li Ge; Yan Li; Xiaorong Xu; Ming Tang; Yin Yi; Liang Chen (Planta, 2024)

Moso bamboo (Phyllostachys edulis) expansion enhances soil pH and alters soil nutrients and microbial communities - Yaoxing Wu; Jiahuan Guo; Zhiying Tang; Tianxiang Wang; Wenting Li; Xiaorong Wang; Hongxia Cui; Xingyi Hu; Lianghua Qi (Science of The Total Environment, 2024)

A novel tool for tracing water sources of streamflow in a mixed land-use catchment - Zhi-Xiang Sun; Jun-Fang Cui; Jian-Hua Cheng; Xiang-Yu Tang (Science of The Total Environment, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Effect of inlet gas volume fraction on shafting vibration of multiphase pumps under low discharge conditions - Guojun Zhu; Zhenbo Tang; Jianjun Feng; Sina Yan; Yunzhe Li; Wenhao Cui (Ocean Engineering, 2024)

Gas tube effect: A transport mode of deeply buried volatile DNAPLs to shallow strata - Lifan Chen; Guantao Ding; Jie Lu; Yuxiang Liu; Shanming Wei; Xiujun Guo; Cui Tang; Hao Sun; Hanyue Zuo (Journal of Hydrology, 2024)

Comparative analysis and selection criteria for residence time distribution models in free water surface constructed wetlands - Bochao Zhang; Yuanlai Cui; Yonghong Shu; Bin Liao; Mengwei Yang; Chi Tang (Journal of Hydrology, 2024)

Gaussian meta-feature balanced aggregation for few-shot synthetic aperture radar target detection - Zheng Zhou; Zongyong Cui; Kailing Tang; Yu Tian; Yiming Pi; Zongjie Cao (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Mechanism analysis of methionine inhibiting growth of Bifidobacterium bifidum - Zheming Gu; Xin Tang; Bingyong Mao; Qiuxiang Zhang; Jianxin Zhao; Wei Chen; Shumao Cui (Food Bioscience, 2024)

Biomass-related PM2.5 induced inflammatory microenvironment via IL-17F/IL-17RC axis - Fang He; Xiaoyuan Yu; Jiahuan Zhang; Jieda Cui; Lei Tang; Siqi Zou; Jinding Pu; Pixin Ran (Environmental Pollution, 2024)

Pendulum-swing coordination boosting “liquid-like” Li-ion conduction within asymmetric lamellar fillers for solid polymer electrolytes - Fei Tang; Liu Wang; Xinqi Huang; Xuesong Yin; Yapeng Tian; Zhuosen Wang; Xinwei Cui; Qun Xu (Chemical Engineering Journal, 2024)

Piperlongumine inhibits esophageal squamous cell carcinoma in vitro and in vivo by triggering NRF2/ROS/TXNIP/NLRP3-dependent pyroptosis - Yue Cui; Xiao-bo Chen; Ying Liu; Qian Wang; Jie Tang; Man-jun Chen (Chemico-Biological Interactions, 2024)

Simultaneous decontamination of phosphorus and bisphenol A from livestock wastewater with boehmite-modified carbon composite - Yaru Peng; Xiu Zhang; Yuan Luo; Azeem Muhammad; Guoping Yang; Kuok Ho Daniel Tang; Zengqiang Zhang; Yuan Xu; Menghao Li; Jintong Cui; Ronghua Li (Bioresource Technology, 2024)

OsNAC103, an NAC transcription factor negatively regulates plant height in rice - Yan Li; Liming Zhao; Chiming Guo; Ming Tang; Wenli Lian; Siyu Chen; Yuehan Pan; Xiaorong Xu; Chengke Luo; Yin Yi; Yuchao Cui; Liang Chen (Planta, 2024)
Main conclusion OsNAC103 negatively regulates rice plant height by influencing the cell cycle and crosstalk of phytohormones. Abstract Plant height is an important characteristic of rice farming and is directly related to agricultural yield. Although there has been great progress in research on plant growth regulation, numerous genes remain to be elucidated. NAC transcription factors are widespread in plants and have a vital function in plant growth. Here, we observed that the overexpression of OsNAC103 resulted in a dwarf phenotype, whereas RNA interference (RNAi) plants and osnac103 mutants showed no significant difference. Further investigation revealed that the cell length did not change, indicating that the dwarfing of plants was caused by a decrease in cell number due to cell cycle arrest. The content of the bioactive cytokinin N 6 -Δ 2 -isopentenyladenine (iP) decreased as a result of the cytokinin synthesis gene being downregulated and the enhanced degradation of cytokinin oxidase. OsNAC103 overexpression also inhibited cell cycle progression and regulated the activity of the cell cyclin OsCYCP2;1 to arrest the cell cycle. We propose that OsNAC103 may further influence rice development and gibberellin–cytokinin crosstalk by regulating the Oryza sativa homeobox 71 ( OSH71 ). Collectively, these results offer novel perspectives on the role of OsNAC103 in controlling plant architecture.

Circulating Lipoproteins Mediate the Association Between Cardiovascular Risk Factors and Cognitive Decline: A Community-Based Cohort Study - Jialin Li; Qingxia Huang; Yingzhe Wang; Mei Cui; Kelin Xu; Chen Suo; Zhenqiu Liu; Yanpeng An; Li Jin; Huiru Tang; Xingdong Chen; Yanfeng Jiang (Phenomics, 2024)

Distribution characteristics of soil organic carbon fractions in paddy profiles with 40 years of fertilization under two groundwater levels - Kaizhao Tang; Cong Wu; Shuai Wang; Wenjuan Liao; Lichu Yin; Weijun Zhou; Hao-Jie Cui (Journal of Soils and Sediments, 2024)

Leveraging CRISPR/Cas12 signal amplifier to sensitive detection of apurinic/apyrimidinic endonuclease 1 and high-throughput inhibitor screening - Sheng Ding; Yi Yuan; Juan Dong; Feng Du; Xin Cui; Zheng Shi; Zhuo Tang (Analytica Chimica Acta, 2024)

Cross-Domain Contrastive Learning-Based Few-Shot Underwater Acoustic Target Recognition - Xiaodong Cui; Zhuofan He; Yangtao Xue; Keke Tang; Peican Zhu; Jing Han (Journal of Marine Science and Engineering, 2024)
Underwater Acoustic Target Recognition (UATR) plays a crucial role in underwater detection devices. However, due to the difficulty and high cost of collecting data in the underwater environment, UATR still faces the problem of small datasets. Few-shot learning (FSL) addresses this challenge through techniques such as Siamese networks and prototypical networks. However, it also suffers from the issue of overfitting, which leads to catastrophic forgetting and performance degradation. Current underwater FSL methods primarily focus on mining similar information within sample pairs, ignoring the unique features of ship radiation noise. This study proposes a novel cross-domain contrastive learning-based few-shot (CDCF) method for UATR to alleviate overfitting issues. This approach leverages self-supervised training on both source and target domains to facilitate rapid adaptation to the target domain. Additionally, a base contrastive module is introduced. Positive and negative sample pairs are generated through data augmentation, and the similarity in the corresponding frequency bands of feature embedding is utilized to learn fine-grained features of ship radiation noise, thereby expanding the scope of knowledge in the source domain. We evaluate the performance of CDCF in diverse scenarios on ShipsEar and DeepShip datasets. The experimental results indicate that in cross-domain environments, the model achieves accuracy rates of 56.71%, 73.02%, and 76.93% for 1-shot, 3-shot, and 5-shot scenarios, respectively, outperforming other FSL methods. Moreover, the model demonstrates outstanding performance in noisy environments.

7-Methoxy-13-dehydroxypaxilline: New indole diterpenoid from an endophytic fungus Penicillium sp. Nb 19 - Jing Yu; Jia-Peng Wang; Shi-Fang Liu; Cui-Yun Yin; De-Ying Tang; Yi-Hang Li; Li-Xia Zhang (Natural Product Research, 2024)

Degradation of trichloroethylene by biochar supported nano zero-valent iron (BC-nZVI): The role of specific surface area and electrochemical properties - Daibing Hou; Xuedan Cui; Meng Liu; Hantong Qie; Yiming Tang; Wenpeng Leng; Nan Luo; Huilong Luo; Aijun Lin; Wenjie Yang; Wenxia Wei; Tianwen Zheng (Science of The Total Environment, 2024)

Recent progresses, challenges and proposals on SF6 emission reduction approaches - Zhaolun Cui; Yi Li; Song Xiao; Shuanngshuang Tian; Ju Tang; Yanpeng Hao; Xiaoxing Zhang (Science of The Total Environment, 2024)

Differences in background environment and fertilization method mediate plant response to nitrogen fertilization in alpine grasslands on the Qinghai-Tibetan Plateau - Shun He; Jianqing Du; Yanfen Wang; Lizhen Cui; Wenjing Liu; Yifan Xiao; Qinwei Ran; Linfeng Li; Zuopei Zhang; Li Tang; Ronghai Hu; Yanbin Hao; et al. (Science of The Total Environment, 2024)

Overexpression of PtoMYB99 diminishes poplar tolerance to osmotic stress by suppressing ABA and JA biosynthesis - Tao Long; Fengming Yang; Zihao Chen; Yuhang Xing; Xia Tang; Banglan Chen; Wenli Cui; Lucas Gutierrez Rodriguez; Lijun Wang; Yongfeng Gao; Yinan Yao (Journal of Plant Physiology, 2024)

Influence of covalent conjugates of zein peptide-phenolic acids with different hydrophobicity on performance of resultant lutein-loaded emulsion gels - Wenting Tang; Mengyao Liu; Yongxue Luo; Hanwen Cui; Zeyue Fu; Jie Zhang; Qingjie Sun; Chuanfen Pu (Journal of Food Engineering, 2024)

Prediction model on hydrolysis kinetics of phthalate monoester: A density functional theory study - Tong Xu; Jingwen Chen; Deming Xia; Weihao Tang; Jiansheng Cui; Chun Liu; Shuangjiang Li (Journal of Environmental Sciences, 2024)

Knowledge evolution learning: A cost-free weakly supervised semantic segmentation framework for high-resolution land cover classification - Hao Cui; Guo Zhang; Yujia Chen; Xue Li; Shasha Hou; Haifeng Li; Xiaolong Ma; Na Guan; Xuemin Tang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Effects of in vitro fecal fermentation on the metabolism and antioxidant properties of cyanidin-3-O-glucoside - Bulei Wang; Xin Tang; Bingyong Mao; Qiuxiang Zhang; Fengwei Tian; Jianxin Zhao; Wei Chen; Shumao Cui (Food Chemistry, 2024)

Tannic acid-coated cellulose nanocrystal-reinforced transparent multifunctional hydrogels with UV-filtering for wearable flexible sensors - Shuyuan Cui; Sufeng Zhang; Fengjiao Zhang; Rui Lin; Chengfang Tang; Xiaokai Jing (Carbohydrate Polymers, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Electrochemical biosensing for E.coli detection based on triple helix DNA inhibition of CRISPR/Cas12a cleavage activity - Jiuying Cui; Qisheng Luo; Cheng Wei; Xiandong Deng; Hongqu Liang; Jihua Wei; Yuanxun Gong; Qianli Tang; Kai Zhang; Xianjiu Liao (Analytica Chimica Acta, 2024)

A remote sensing method for mapping alpine grasslines based on graph‐cut - Licong Liu; Jin Chen; Miaogen Shen; Xuehong Chen; Ruyin Cao; Xin Cao; Xihong Cui; Wei Yang; Xiaolin Zhu; Le Li; Yanhong Tang (Global Change Biology, 2024)
Climate change has induced substantial shifts in vegetation boundaries such as alpine treelines and shrublines, with widespread ecological and climatic influences. However, spatial and temporal changes in the upper elevational limit of alpine grasslands (“alpine grasslines”) are still poorly understood due to lack of field observations and remote sensing estimates. In this study, taking the Tibetan Plateau as an example, we propose a novel method for automatically identifying alpine grasslines from multi‐source remote sensing data and determining their positions at 30‐m spatial resolution. We first identified 2895 mountains potentially having alpine grasslines. On each mountain, we identified a narrow area around the upper elevational limit of alpine grasslands where the alpine grassline was potentially located. Then, we used linear discriminant analysis to adaptively generate from Landsat reflectance features a synthetic feature that maximized the difference between vegetated and unvegetated pixels in each of these areas. After that, we designed a graph‐cut algorithm to integrate the advantages of the Otsu and Canny approaches, which was used to determine the precise position of the alpine grassline from the synthetic feature image. Validation against alpine grasslines visually interpreted from a large number of high‐spatial‐resolution images showed a high level of accuracy ( R 2 , .99 and .98; mean absolute error, 22.6 and 36.2 m, vs. drone and PlanetScope images, respectively). Across the Tibetan Plateau, the alpine grassline elevation ranged from 4038 to 5380 m (5th–95th percentile), lower in the northeast and southeast and higher in the southwest. This study provides a method for remotely sensing alpine grasslines for the first‐time at large scale and lays a foundation for investigating their responses to climate change.

Plant colorants for natural hair coloration: Dyeing optimization and photostability assessment - Hongyan Cui; Rui Cai; Zhongjie Hua; Ying Tang (Sustainable Chemistry and Pharmacy, 2023)

Author correction to “nirS and nosZII bacterial denitrifiers as well as fungal denitrifiers are coupled with N2O emissions in long-term fertilized soils” [Sci. Total Environ. 897-165426] - Ziwei Wan; Ling Wang; Guoqin Huang; Fahd Rasul; Masood Iqbal Awan; Huanming Cui; Kailou Liu; Xichu Yu; Haiying Tang; Shubin Wang; Huifang Xu (Science of The Total Environment, 2023)

Global, regional, and national burden of asbestosis from 1990 to 2019 and the implications for prevention and control - Zejin Ou; Xin Li; Jiaxin Cui; Shaofang Zhu; Kexin Feng; Jialao Ma; Kangyong Wu; Yuquan Chen; Yiwei Su; Shihao Tang; Danping Duan; Yixian Ren; et al. (Science of The Total Environment, 2023)

Does environmental regulation improve firms' export product quality? Empirical evidence based on China's key regional air pollution and control policy - Yan Jiang; Long Tang; Cui Huang (Journal of Cleaner Production, 2023)

A novel plant-based milk alternative made from red kidney bean (Phaseolus vulgaris L.): Effects of cultivars on its stability and sensory properties - Jian Tang; Lulu Cui; Siqi Zhang; Li Wang; Dianzhi Hou; Sumei Zhou (Food Bioscience, 2023)

Cyclopropane fatty acid and accumulation of glutamate contributed to higher freeze-drying resistance for Bifidobacterium animalis than Bifidobacterium adolescentis - Wenrui Zhou; Bingyong Mao; Xin Tang; Qiuxiang Zhang; Jianxin Zhao; Wei Chen; Shumao Cui (Food Bioscience, 2023)

Formation of fluorescent substances and correlation with process flavor changes of dehydrated Maillard reaction intermediates of peanut protein hydrolysates - Wenyu Zhou; Cheng Huang; Yishun Yao; Tong Zhou; Heping Cui; Yunwei Niu; Foxin Zhang; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Bioscience, 2023)

l-Cysteine involved Maillard peptides of distillers’ grain hydrolysates: Browning, formation of characteristic flavor and improvement on fracturability of sugared garlic - Yunqi Feng; Shibin Deng; Xue Xia; Yishun Yao; Heping Cui; Jingyang Yu; Shiqing Song; Foxin Zhang; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Bioscience, 2023)

Characterization of physicochemical properties and flavor profiles of fermented Chinese bamboo shoots (suansun) from Liuzhou and Guilin - Dingyuan Wang; Mengyu Hu; Xin Tang; Qiuxiang Zhang; Jianxin Zhao; Bingyong Mao; Hao Zhang; Shumao Cui (Food Bioscience, 2023)

MiR-7-5p targeted Rb regulating cell cycle is involved in hydroquinone-induced malignant progression in human lymphoblastoid TK6 cells - Lu Zhai; Yuting Gao; Zheming Cui; Lin Chen; Lingxue Yu; Pu Guo; Delong Zhu; Huanwen Tang; Xin Liu; Hao Luo (Food and Chemical Toxicology, 2023)

High-performance inkjet-printed inverted QD-LEDs based on cross-linkable electron regulation layers - Liming Xie; Qing Li; Yuan-Qiu-Qiang Yi; Gengrui Qiu; Omolola Esther Fayemi; Xinju Mu; Zhongsheng Ma; Pengyu Tang; Yang Liu; Wenming Su; Wei Lei; Zheng Cui (Chemical Engineering Journal, 2023)

New evidence of high-magnitude Holocene floods in the Purlung Tsangpo River, southeastern Tibetan Plateau - Hao Wang; Peng Cui; Anna Yang; Jinbo Tang; Shusong Wen; Zewen Yang; Liqin Zhou; Weiming Liu; Nazir Ahmed Bazai (CATENA, 2023)

PPAR-γ promotes the polarization of rat retinal microglia to M2 phenotype by regulating the expression of CD200-CD200R1 under hypoxia - Yiyi Hong; Li Jiang; Fen Tang; Mingyuan Zhang; Ling Cui; Haibin Zhong; Fan Xu; Min Li; Changzheng Chen; Lifei Chen (Molecular Biology Reports, 2023)

Comparative Analysis of Transposable Elements Reveals the Diversity of Transposable Elements in Decapoda and Their Effects on Genomic Evolution - Yuanfeng Xu; Yongkai Tang; Wenrong Feng; Yanan Yang; Zhaoxia Cui (Marine Biotechnology, 2023)

Relationships between nitrogen-specific genes and soil potentials are more complex than single linear ones - Yanfen Wang; Shutong Zhou; Biao Zhang; Jianqing Du; Anquan Xia; Lin Chen; Li Tang; Kui Wang; Wenjing Liu; Zongsong Wang; Lizhen Cui; Kai Xue (Applied Soil Ecology, 2023)

Poly-adenine-mediated tetrahedral DNA nanostructure with multiple target-recognition sites for ultrasensitive and rapid electrochemical detection of Aflatoxin B1 - Kaixuan Wang; Nuanfei Zhu; Yumo Li; Hu Zhang; Beibei Wu; Jian Cui; Jun Tang; Zhugen Yang; Fang Zhu; Zhen Zhang (Analytica Chimica Acta, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Depth Spatial Characterization of Marine Environmental Noise in the Zengmu Basin - Xiaoming Cui; Siyuan Cang; Chao Li; Danling Tang; Qing Hu; Huayong Yang (Journal of Marine Science and Engineering, 2023)
Based on the measured data obtained from an array of optical fiber hydrophones, this paper analyzes and interprets the depth spatial spectrum characteristics, correlation characteristics, and vertical directionality of marine environmental noise in the Zengmu Basin. The analysis is conducted within the frequency range of 20 Hz to 2500 Hz. Additionally, the statistical characteristics of the probability density distribution of environmental noise in the Zengmu Basin were studied and analyzed. The findings indicate that the predominant ambient noise in the low-frequency range (less than 400 Hz) in the Zengmu Basin is primarily attributed to distant sources, commonly identified as ship radiation noise. In the high-frequency band (greater than 400 Hz), the marine ambient noise is primarily derived from the sea surface, predominantly in the form of wind-generated noise. In the frequency range of 25–1600 Hz, examined in this study, the power spectral density exhibits an average decrease of over 3 dB and a maximum decrease of over 5 dB with each doubling of frequency. When the frequency is below 400 Hz, there is a higher vertical spatial correlation to ambient noise. The vertical directivity of the noise energy is horizontal, meaning that it is perpendicular to the vertical array direction. Additionally, the probability distribution of the noise level approximately follows the Burr distribution. When the frequency exceeds 400 Hz, there is a low vertical spatial correlation to noise. The vertical directivity of environmental noise exhibits distinct grooves in the horizontal direction, and the probability distribution of the noise spectrum level generally follows a normal distribution.

Curcumin strengthens a spontaneous self-protective mechanism-SP1/PRDX6 pathway, against di-n-butyl phthalate-induced testicular ferroptosis damage - Hengtao Bu; Bao Wang; Yulin Wu; Pu Li; Yankang Cui; Xuping Jiang; Xiaowen Yu; Bianjiang Liu; Min Tang (Environmental Science and Pollution Research, 2023)

First report of Serratia marcescens causing seed necrosis on Nelumbo nucifera in China - Weigang Kuang; Xin Gong; Yachun Lin; Lanlan Chen; Xinwen Zheng; Jiping Tang; Xugen Shi; Xiaotang Sun; Lianhu Zhang; Ruqiang Cui (Crop Protection, 2023)

Evidence of vertical transmission of fowl adenovirus 8b in ducks - Bingrong Wu; Qimin Xu; Zhenchuan Li; Qianqian Wang; Dalin He; Xiaoning Jiang; Yitong Cui; Qiang Feng; Yi Tang; Youxiang Diao (Veterinary Microbiology, 2023)

Effects of the application of nanoscale zero-valent iron on plants: Meta analysis, mechanism, and prospects - Xuedan Cui; Daibing Hou; Yiming Tang; Meng Liu; Hantong Qie; Tuzheng Qian; Ruiqing Xu; Aijun Lin; Xin Xu (Science of The Total Environment, 2023)

nirS and nosZII bacterial denitrifiers as well as fungal denitrifiers are coupled with N2O emissions in long-term fertilized soils - Ziwei Wan; Ling Wang; Guoqin Huang; Fahd Rasul; Masood Iqbal Awan; Huanming Cui; Kailou Liu; Xichu Yu; Haiying Tang; Shubin Wang; Huifang Xu (Science of The Total Environment, 2023)

Long-term stability and toxicity effects of three-dimensional electrokinetic remediation on chromium-contaminated soils - Zheng Wang; Xiao He; Xin Li; Liuzhou Chen; Tian Tang; Guodong Cui; Qiming Zhang; Yangsheng Liu (Environmental Pollution, 2023)

Clinical characteristics and prognostic risk factors of candidemia in non-neutropenic patients: a retrospective cohort study - Fengqi Liu; Xueping Shao; Zhaohui Dong; Kankai Tang; Li Zhong; Wei Xu; Zhidong Chen; Cheng Zheng; Kai Zhang; Jiachang Cai; Hongwei Zhou; Wei Cui; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Technical Design and Data Analysis of Autonomous Underwater Vehicle-Based Side-Scan Sonar Operations - Xinyang Zhao; Shaohua Jin; Gang Bian; Yang Cui; Junsen Wang; Yulin Tang; Chao Jiang (Journal of Marine Science and Engineering, 2023)
In response to the absence of standardized work practices, work safety measures, efficient work procedures, and suitable line planning methods for exploring seabed topography using autonomous underwater vehicles (AUVs) equipped with side-scan sonar systems, this paper proposes a design framework for side-scan sonar measurement technology based on AUVs. Detailed research has been conducted on line planning methods that differ significantly from those used in shipborne operations. The new line planning method was developed based on the performance characteristics of AUV equipment, the principles of motion modes, and shipborne side-scan sonar operations. The validity of the line planning method was verified through actual sea experiments using different types of AUVs in various terrains. The experimental results demonstrate that the new survey line planning method is distinct from existing AUV path planning methods and is highly applicable for conducting seabed topography exploration operations. Furthermore, the technical design scheme studied in this article is applicable in different sea areas and ensures the safety, operational efficiency, and data quality of AUVs. It holds significant importance for marine science engineering and practical applications. The article also features an analysis of successful data collected from AUVs equipped with side-scan sonar for conducting seabed topography exploration operations.

Inhibiting mechanisms of metal ion complexation on photogenerated reactive intermediates derived from dissolved black carbon - Yi-na Tu; Wei Tang; Weilin Wu; Huaying Liu; Xiangfen Cui; Senlin Tian; Yingjie Li; Weidong Jiao (Chemosphere, 2023)

Single particle tracking reveals SARS-CoV-2 regulating and utilizing dynamic filopodia for viral invasion - Yue Zhang; Xiaowei Zhang; Zhongyi Li; Weisong Zhao; Hui Yang; Shuangshuang Zhao; Daijiao Tang; Qian Zhang; Zonghong Li; Huisheng Liu; Haoyu Li; Bo Li; et al. (Science Bulletin, 2023)

Photocatalytic degradation of bisphenol A by temperature-sensitive magnetic hydrogel with enhanced service life - Wenhui Chen; Wei Mao; Zhiqiang Liu; Weilin Hou; Naresh Kumar; Jun Sun; Xingwei Cai; Cheng Huang; Wei Shen; Fu Yang; Yanjuan Cui; Hian Kee Lee; et al. (Journal of Hazardous Materials, 2023)

Strategies to improve CaO absorption cycle stability and progress of catalysts in Ca-based DFMs for integrated CO2 capture-conversion: A critical review - Pengchao Zang; Jiyun Tang; Xiaoyang Zhang; Lin Cui; Juan Chen; Pei Zhao; Yong Dong (Journal of Environmental Chemical Engineering, 2023)

Multiple path-dominated activation of peroxymonosulfate by MOF-derived Fe2O3/Mn3O4 for catalytic degradation of tetracycline - Chensi Tang; Min Cheng; Cui Lai; Ling Li; Zhen Wei; Dengsheng Ma; Li Du; Guangfu Wang; Lu Yang; Lin Tang (Journal of Environmental Chemical Engineering, 2023)

Comparative characterization of flavor precursors and volatiles of Taihe black-boned silky fowl and Hy-line Brown yolks using multiomics and GC-O-MS-based volatilomics - Weifang Yang; Youyou Yang; Liang Wang; Xueze Lv; Jing Li; Huanxian Cui; Chaohua Tang; Qingyu Zhao; Yaxiong Jia; Yuchang Qin; Junmin Zhang (Food Research International, 2023)

Changes of lipid oxidation, volatile and taste-active compounds during pan-heating of pork belly - Xingwei Wang; Xinshuo Wang; Xiaoming Zhang; Shaoquan Liu; Jingyang Yu; Heping Cui; Shuqin Xia; Chi-Tang Ho (Food Research International, 2023)

Night warming from tillering to jointing increases post-anthesis flag leaf photosynthetic capacity and wheat yield - Yonghui Fan; Liangliang Ma; Jinhao Yang; Wenjin Ding; Wei He; Yu Tang; Guoji Cui; Wenjing Zhang; Shangyu Ma; Chuanxi Ma; Zhenglai Huang (European Journal of Agronomy, 2023)

Protective effect of Huanglianjiedu Decoction on microcystin-LR induced nerve injury - Zhengqiang Hu; Guanmin Meng; Lejun Zhang; Meng Zhang; Huashun Cui; Huifang Tang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Insight into the selective oxidation behavior of organic pollutants via Ni-N4-C mediated electron transfer pathway - Huchuan Yan; Cui Lai; Shiyu Liu; Dongbo Wang; Xuerong Zhou; Mingming Zhang; Ling Li; Dengsheng Ma; Fuhang Xu; Xiuqin Huo; Lin Tang; Ming Yan; et al. (Chemical Engineering Journal, 2023)

Response Surface Methodology and Artificial Neural Network Modeling for the Removal of Volatile Organic Compounds in Biotrickling Filters - Tianqiu Hong; Lin Wei; Kangping Cui; Yugang Dong; Lei Luo; Tingting Zhang; Ruolan Li; Ziyue Li; Yiming Tang (Water, Air, & Soil Pollution, 2023)

Intestinal Microbiomics and Metabolomics Insights into the Hepatoprotective Effects of Lactobacillus paracasei CCFM1222 Against the Acute Liver Injury in Mice - Weiling Guo; Shumao Cui; Xin Tang; Qiuxiang Zhang; Jianxin Zhao; Bingyong Mao; Hao Zhang (Probiotics and Antimicrobial Proteins, 2023)

Zinc and selenium status in coronavirus disease 2019 - Liding Fan; Yanshuo Cui; Zonghao Liu; Jiayue Guo; Xiaohui Gong; Yunfei Zhang; Weihao Tang; Jiahe Zhao; Qingjie Xue (BioMetals, 2023)

Multi-GNSS precise point positioning with predicted orbits and clocks - Longjiang Tang; Jungang Wang; Bobin Cui; Huizhong Zhu; Maorong Ge; Harald Schuh (GPS Solutions, 2023)
Global Navigation Satellite Systems (GNSS) Real-time Precise Point Positioning (RT-PPP) strongly relies on the precise satellite orbits and clocks, especially the latter requires high update rate, e.g., five seconds, due to its limited prediction accuracy. Such a high-rate update frequency is a burden to both the data analysis and communicating, and interruption in communicating is almost unavoidable. For the new constellations such as Galileo and BDS-3 with high-stability hydrogen clocks onboard, it is possible to predict satellite clocks to a longer arc. Moreover, recent developments in multi-GNSS ultra-rapid precise orbit determination enables the half-hourly update, ensuring the availability with a prediction arc of 30–60 min. We investigate multi-GNSS RT-PPP using half-hourly predicted products and demonstrate that a 3-D accuracy of 2.9 and 11.3 cm can be achieved for static and simulated kinematic solutions, respectively. We present the different clock prediction accuracies of different types of satellites and propose a satellite-specific weighting strategy in PPP, which exploits the benefits of the satellites of good performance. The method is based on the prediction accuracy of both, satellites and clocks, and shows an improvement of 15 to 60% compared to those without satellite-specific weighting or with simplified weighting strategies. We also demonstrate that Galileo satellites contribute the most in the quad-constellation solution, thanks to the highly stable satellite clocks.

Metal-organic framework composite Mn/Fe-MOF@Pd with peroxidase-like activities for sensitive colorimetric detection of hydroquinone - Die Deng; Ya Wang; Shaohua Wen; Yujie Kang; Xiaoyan Cui; Rong Tang; Xiupei Yang (Analytica Chimica Acta, 2023)

Inverting the DNA tetrahedron: A novel strategy for sensitive and stable detection of aging-related enzyme MMP2 - Jihua Wei; Zichun Song; Jiuying Cui; Yuanxun Gong; Qianli Tang; Kai Zhang; Xinlei Song; Xianjiu Liao (Analytica Chimica Acta, 2023)

Ellagic acid and intestinal microflora metabolite urolithin A: A review on its sources, metabolic distribution, health benefits, and biotransformation - Mengwei Zhang; Shumao Cui; Bingyong Mao; Qiuxiang Zhang; Jianxin Zhao; Hao Zhang; Xin Tang; Wei Chen (Critical Reviews in Food Science and Nutrition, 2023)

Relationship between Resource Distribution and Vertical Structure of Water Temperature of Purpleback Flying Squid (Sthenoteuthis oualaniensis) in the Northwest Indian Ocean Based on GAM and GBT Models - Chen Shang; Haibin Han; Junlin Chen; Fenghua Tang; Wei Fan; Heng Zhang; Xuesen Cui (Journal of Marine Science and Engineering, 2023)
The Northwest Indian Ocean is a key fishing ground for China’s pelagic fisheries, with the purpleback flying squid being a significant target. This study uses commercial fishing logs of the Indian Ocean between 2015 and 2021, alongside pelagic seawater temperature and its vertical temperature difference within the 0–200 m depth range, to construct generalized additive models (GAMs) and gradient boosting tree models (GBTs). These two models are evaluated using cross-validation to assess their ability to predict the distribution of purpleback flying squid. The findings show that factors like year, latitude, longitude, and month significantly influence the distribution of purpleback flying squid, while surface water temperature, 200 m water temperature, and the 150–200 m water layer temperature difference also play a role in the GBT model. Similar factors also take effects in the GAM. Comparing the two models, both GAM and GBT align with reality in predicting purpleback flying squid resource distribution, but the precision indices of GBT model outperform those of the GAM. The predicted distribution for 2021 by GBT also has a higher overlap with the actual fishing ground than that by GAM, indicating GBT’s superior forecasting ability for the purpleback flying squid fishing ground in the Northwest Indian Ocean.

Navigating the landscape of global sustainable livelihood research: past insights and future trajectory - Tong Li; Ranjay K. Singh; Lizhen Cui; Zhihong Xu; Hongdou Liu; Francesco Fava; Shalander Kumar; Xiufang Song; Li Tang; Yanfen Wang; Yanbin Hao; Xiaoyong Cui (Environmental Science and Pollution Research, 2023)

Electrooxidation degradation of hydroxychloroquine in wastewater using a long-acting Ti-based PbO2 anode with an arc-sprayed (Ti,Zr)N interlayer - Changbin Tang; Duanduan Cui; Zhigang Li; Lihua Yu; Juanqin Xue; Xiangyang Yin (Chemosphere, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Study of the adsorption behavior of tetracycline onto suspended sediments in the Yellow River, China: Insights into the transportation and mechanism - Quantao Cui; Jiawei Liu; Yifan Tang; Yao Ma; Gong Lin; Ruonan Wang; Wei Zhang; Qiting Zuo; Xiaoli Zhao; Fengchang Wu (Science of The Total Environment, 2023)

Chronic intermittent hypobaric hypoxia improves iron metabolism disorders via the IL-6/JAK2/STAT3 and Epo/STAT5/ERFE signaling pathways in metabolic syndrome rats - Fang Cui; Jie Sun; Haichao Mi; Bo Li; Longmei Tang; Ruotong Wang; Yutao Du; Bingyan Guo; Yongjun Li; Min Shi (Journal of Trace Elements in Medicine and Biology, 2023)

Exploration of potential driving mechanisms of Comamonas testosteroni in polycyclic aromatic hydrocarbons degradation and remodelled bacterial community during co-composting - Fangzhi Jiang; Ziwei Jiang; Jiayue Huang; Pengfei Tang; Jizhe Cui; Wenxuan Feng; Chunjing Yu; Chang Fu; Qian Lu (Journal of Hazardous Materials, 2023)

Tuning the intrinsic catalytic sites of magnetite to concurrently enhance the reduction of H2O2 and O2: Mechanism analysis and application potential evaluation - Ling Li; Min Cheng; Eydhah Almatrafi; Lei Qin; Shiyu Liu; Huan Yi; Lu Yang; Zhexin Chen; Dengsheng Ma; Mingming Zhang; Xuerong Zhou; Fuhang Xu; et al. (Journal of Hazardous Materials, 2023)

Optimizing environmental flow based on a new optimization model in balancing objectives among river ecology, water supply and power generation in a high-latitude river - Peng Qi; Xiaoyu Tang; Y. Jun Xu; Zhen Cui; Jiaxin Sun; Guangxin Zhang; Yao Wu; Ming Jiang (Journal of Environmental Management, 2023)

Evolution of lean meat tenderness stimulated by coordinated variation of water status, protein structure and tissue histology during cooking of braised pork - Xiaomin Wang; Yishun Yao; Jingyang Yu; Heping Cui; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Research International, 2023)

Improved tenderness and water retention of pork pieces and its underlying molecular mechanism through the combination of low-temperature preheating and traditional cooking - Yishun Yao; Xiaomin Wang; Heping Cui; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Chemistry, 2023)

Near-infrared-IIb fluorescent nanozymes for imaging-guided treatment of traumatic brain injury - Feng Liu; Biao Huang; Tao Tang; Fanjie Wang; Ran Cui; Mingxi Zhang; Taolei Sun (Chemical Engineering Journal, 2023)

Recent advances in the pharmacological applications and liver toxicity of triptolide - Dongxiao Cui; Dingqiao Xu; Shijun Yue; Chaoqun Yan; Wenjuan Liu; Ruijia Fu; Wenfu Ma; Yuping Tang (Chemico-Biological Interactions, 2023)

Effects of biochar and inorganic amendments on soil fertility, tea yield, and quality in both Pb–Cd-contaminated and acidified tea plantations - Wenbin Liu; Yanxin Tang; Jiawei Ma; Weiling Zhang; Shiyan Liao; Shiyu Cui; Zhengqian Ye; Dan Liu (Journal of Soils and Sediments, 2023)

The recent advances of glucosinolates and their metabolites: Metabolism, physiological functions and potential application strategies - Jiaying Wu; Shumao Cui; Junsheng Liu; Xin Tang; Jianxin Zhao; Hao Zhang; Bingyong Mao; Wei Chen (Critical Reviews in Food Science and Nutrition, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Dioxin emission modeling using feature selection and simplified DFR with residual error fitting for the grate-based MSWI process - Heng Xia; Jian Tang; Loai Aljerf; Canlin Cui; Bingyin Gao; Prince Onyedinma Ukaogo (Waste Management, 2023)

Recent advances in degradation of the most potent industrial greenhouse gas sulfur hexafluoride - Shengyao Shi; Yi Li; Zhaolun Cui; Yongxu Yan; Xiaoxing Zhang; Ju Tang; Song Xiao (Chemical Engineering Journal, 2023)

Cadmium induced time-dependent kidney injury in common carp via mitochondrial pathway: Impaired mitochondrial energy metabolism and mitochondrion-dependent apoptosis - Jiawen Cui; Yuhao Liu; Zhiyu Hao; Yuhang Liu; Minna Qiu; Lu Kang; Xiaohua Teng; You Tang (Aquatic Toxicology, 2023)

Lactobacillus reuteri CCFM1175 and Lactobacillus paracasei CCFM1176 Could Prevent Capsaicin-Induced Ileal and Colonic Injuries - Bingyong Mao; Qunran Xiang; Xin Tang; Qiuxiang Zhang; Xiaoming Liu; Jianxin Zhao; Shumao Cui; Hao Zhang (Probiotics and Antimicrobial Proteins, 2023)

Correction to: Lack of Rab27a attenuates foam cell formation and macrophage inflammation in uremic apolipoprotein E knockout mice - Yan Shen; Yajuan Gao; Jiani Fu; Cui Wang; Yali Tang; Shengnan Chen; Yan Zhao (Journal of Molecular Histology, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Gene-specific silencing of SlPL16, a pectate lyase coding gene, extends the shelf life of tomato fruit - Haozhan Ren; Qing Zhao; Youwei Feng; Peipei Tang; Yong Wang; Jun Jiang; Chunhua Hu; Yunxing Wang; Baolu Cui; Xiaodong Xie; Yan Li; Xuejie Zhao; et al. (Postharvest Biology and Technology, 2023)

Sponge-like, semi-interpenetrating self-sensory hydrogel for smart photothermal-responsive soft actuator with biomimetic self-diagnostic intelligence - Xingchen Cui; Zhezhi Liu; Bing Zhang; Xiaoduo Tang; Fuqiang Fan; Yu Fu; Junhu Zhang; Tieqiang Wang; Fanbao Meng (Chemical Engineering Journal, 2023)

Activation of cellulose with CO2 and/or H2O: Evolution of functionalities of the biochar and environmental impacts - Cong Ming; Yuchen Jiang; Chao Li; Qifeng Chen; Shu Zhang; Shuang Wang; Bin Li; Zhenhua Cui; Yonggui Tang; Xun Hu (Biomass and Bioenergy, 2023)

hUMSCs Transplantation Regulates AMPK/NR4A1 Signaling Axis to Inhibit Ovarian Fibrosis in POI Rats - Linlu Cui; Hongchu Bao; Wenqian Zhu; Yu Tang; Qianqian Luo; Yaru Si; Qiang Fu; Zhonglin Jiang (Stem Cell Reviews and Reports, 2023)

Channel aggradation triggered by dam failure amplifies the damage of outburst flood - Dingzhu Liu; Yifei Cui; Wen Jin; Hao Wang; Hui Tang (Landslides, 2023)

Children with autism spectrum disorder perform comparably to their peers in a parent–child cooperation task - Yun Tang; Chenbo Wang; Xin Liu; Fēi Li; Yuan Dai; Lijuan Cui; Fĕi Li (Experimental Brain Research, 2023)

Inspired by game theory: Multi-signal output photoelectrochemical point-of-care immunoassay based on target-triggered organic electronic barriers - Xianlin Han; Shujin Lin; Cui Cheng; Xiao Han; Dianping Tang (Analytica Chimica Acta, 2023)

The effect of PM2.5 exposure on the mortality of patients with hepatocellular carcinoma in Tianjin, China - Hao Cui; Ye Qi; Chunyue Guo; Naijun Tang (Environmental Science and Pollution Research, 2023)

A review of seismic resilience of shield tunnels - Xiangsheng Chen; Jun Shen; Xiaohua Bao; Xianlong Wu; Waiching Tang; Hongzhi Cui (Tunnelling and Underground Space Technology, 2023)

Estimation of reduced greenhouse gas emission from municipal solid waste incineration with electricity recovery in prefecture- and county-level cities of China - Qing Zhao; Weihao Tang; Mengjie Han; Wenjing Cui; Lei Zhu; Huaijun Xie; Wei Li; Fengchang Wu (Science of The Total Environment, 2023)

Downregulation of BRD4 attenuates high glucose-induced damage of trophoblast cells by inhibiting activation of AKT/mTOR pathway - Ou Chai; Na Tang; Ruimeng Guo; Dongqing Cui; Zhimin Hou (Reproductive Biology, 2023)

Toward a unified and refined Ordovician stratigraphy for the western Yangtze region, South China - Guang-Xu Wang; Yu-Nong Cui; Yan Liang; Rong-Chang Wu; Xin Wei; Fang-Yi Gong; Bing Huang; Xiao-Cong Luan; Peng Tang; Li-Xia Li; Xiao-Le Zhang; Yi-Chi Zhang; et al. (Palaeoworld, 2023)

Intraperitoneal injection of β-glucan during the suckling period improved the intestinal health of newly weaned rabbits by enhancing immune responses - X. Wang; S.S. Wang; F. Yan; W.Q. Yang; G.F. Tang; M.H. Cui; X.R. Xu (Livestock Science, 2023)

Entropy-driven assisted T7 RNA polymerase amplification-activated CRISPR/Cas13a activity for SARS-CoV-2 detection in human pharyngeal swabs and environment by an electrochemiluminescence biosensor - Jihua Wei; Zichun Song; Jiuying Cui; Yuanxun Gong; Qianli Tang; Kai Zhang; Xinlei Song; Xianjiu Liao (Journal of Hazardous Materials, 2023)

Uncertainty quantification of CO2 emissions from China's civil aviation industry to 2050 - Lishan Yang; Yu-Jie Hu; Honglei Wang; Chengjiang Li; Bao-Jun Tang; Binli Wang; Hefu Cui (Journal of Environmental Management, 2023)

Effects of Lacticaseibacillus casei fermentation on the bioactive compounds, volatile and non-volatile compounds, and physiological properties of barley beverage - Weiling Guo; Minxuan Chen; Shumao Cui; Xin Tang; Qiuxiang Zhang; Jianxin Zhao; Bingyong Mao; Hao Zhang (Food Bioscience, 2023)

Enzyme-responsive microneedle patch for bacterial infection and accelerated healing of diabetic wounds - Shizhou Wu; Boquan Qin; Xiaofang Tang; Ting Cui; Shijiu Yin; Hongxian Dong; Yunjie Liu; Shu Deng; Hui Zhang; Guoying Feng; Huiqi Xie; Lei Lei (Chemical Engineering Journal, 2023)

An experimental study on the resuspension characteristics of evaporation residues of human exhaled droplets on medical clothing - Han Yu; Chunying Li; Haida Tang; Pengjie Cui; Wenzheng Deng; QianQian Zhang (Building and Environment, 2023)

Potential Probiotic Properties of Blautia producta Against Lipopolysaccharide-Induced Acute Liver Injury - Bingyong Mao; Weiling Guo; Xuemei Liu; Shumao Cui; Qiuxiang Zhang; Jianxin Zhao; Xin Tang; Hao Zhang (Probiotics and Antimicrobial Proteins, 2023)

Lack of Rab27a attenuates foam cell formation and macrophage inflammation in uremic apolipoprotein E knockout mice - Yan Shen; Yajuan Gao; Jiani Fu; Cui Wang; Yali Tang; Shengnan Chen; Yan Zhao (Journal of Molecular Histology, 2023)

Behavior of large yellow croaker (Larimichthys crocea) in pen aquaculture as measured by meter-scale telemetry - Dehua Gong; Xiaojie Cui; Mingyuan Song; Binbin Xing; Pengxiang Xu; Yong Tang; Leiming Yin (Frontiers in Marine Science, 2023)
To understand the behavior of the large yellow croaker ( Larimichthys crocea ) in a pen aquaculture setting, three individuals in each of two experimental groups were telemetered in meter scale by four cable-synchronized hydrophones. The ultrasound pinger system was applied to track the motion of six L. crocea for 24 h using two fixation methods, i.e., implanting tags in the abdomen (the in vivo implantation group) and hanging tags on the dorsal fin (the dorsal fin suspension group). Pingers repeated unique 62.5 kHz coded signals at 5 s intervals along with a pressure signal. The results showed that fish tagged with internal pingers took approximately 3 h longer than externally tagged fish to stabilize in their behavior, as measured by depth utilization; the horizontal movements of the test fish were mostly found outside of the fence, where the test fish performed round-trip swimming, with the least probability of appearing near the production platform and more frequent activities in the feeding areas.

Evaluation and improvement of residence time distribution analysis methods - Bochao Zhang; Yuanlai Cui; Junzhe Luo; Jiaer Wang; Bin Liao; Chi Tang (Journal of Hydrology, 2023)

Projected seasonal changes in future rainfall erosivity over the Lancang-Mekong River basin under the CMIP6 scenarios - Ximeng Xu; Xiaobo Yun; Qiuhong Tang; Huijuan Cui; Jie Wang; Lu Zhang; Deliang Chen (Journal of Hydrology, 2023)

Tailoring porosity and acidity of Sn-modified ZSM-5 for co-aromatization of methanol with 2-methylfuran - Yanfeng Xue; Xiaojing Cui; Jianfeng Shan; Songping Gao; Shusheng Wang; Hongyan Zheng; Jianke Tang; Yulan Niu; Kai Wang; Xun Wang (Fuel, 2023)

Dynamics changes in physicochemical properties, volatile metabolites, non-volatile metabolites, and physiological functions of barley juice during Bifidobacterium infantis fermentation - Weiling Guo; Minxuan Chen; Shumao Cui; Xin Tang; Qiuxiang Zhang; Jianxin Zhao; Bingyong Mao; Hao Zhang (Food Chemistry, 2023)

Determination of dry soil layer and its soil heat flux distribution using actively heated distributed temperature sensing - Meng-Ya Sun; Bin Shi; Yu-Jun Cui; Chao-Sheng Tang; Xing Zheng; Jin Liu; Zi Ying; Yi-Jie Sun; Yun-Qiang Wang; Jing-Xiong Zhou (Engineering Geology, 2023)

Design of a highly efficient Cu-based catalyst with two functional areas: The role of Cu0 and oxygen vacancies in Fenton-like system - Cui Lai; Lu Yang; Ling Li; Dengsheng Ma; Min Cheng; Shiyu Liu; Mingming Zhang; Huchuan Yan; Chensi Tang; Zhexin Chen; Lin Tang (Chemical Engineering Journal, 2023)

Revealing the dynamic temperature of the cathode catalyst layer inside proton exchange membrane fuel cell by experimental measurements and numerical analysis - Qianqian Wang; Fumin Tang; Xiang Li; Jim P. Zheng; Liang Hao; Guomin Cui; Pingwen Ming (Chemical Engineering Journal, 2023)

Effects of Kuroshio and Mesoscale Eddy on Fishing Ground Gravity of Neon Flying Squid Ommastrephes bartramii in Northwest Pacific Ocean - Jiasheng Li; Xuesen Cui; Fenghua Tang; Wei Fan; Zhen Han; Zuli Wu (Journal of Marine Science and Engineering, 2023)
Understanding the spatial patterns of neon flying squid is important for the monitoring and management of fishery resources. Mesoscale eddies and the Kuroshio Extension play important roles in the variation of the fishing ground of Ommastrephes bartramii. However, the way in which eddies and the Kuroshio influence the distribution of Ommastrephes bartramii requires further understanding. In this study, the spatial variation in the distribution of fishing activity and the change of fishing ground gravity of squid were analyzed using automatic identification system (AIS) data. There is a positive correlation between the fishing ground gravity in latitudinal direction and Kuroshio Extension indicators based on the high-frequency eddy kinetic energy (EKE), which describes the Kuroshio variations. Furthermore, the Kuroshio Extension indicators show a positive relationship with the number of the eddies generated in the fishing ground. The results suggest that the changes in the dynamics of SST anomalies could be influenced by eddy-shedding processes in the upstream KE and then alter the distribution of the fishing ground for Ommastrephes bartramii. The Kuroshio index (mean high-frequency eddy kinetic energy between 32° and 37° N, 142° and 149° E) can be used as a good indicator of Kuroshio extension variations to investigate the squid fishing ground in the Kuroshio–Oyashio transition area.

Mitigating soil salinity stress with titanium gypsum and biochar composite materials: Improvement effects and mechanism - Xin Xu; Jiahui Wang; Yiming Tang; Xuedan Cui; Daibing Hou; Hongjun Jia; Shaobo Wang; Lin Guo; Jinhang Wang; Aijun Lin (Chemosphere, 2023)

Debris flow characteristics of the compound channels with vegetated floodplains - Wen-rong Cui; Jian-gang Chen; Xiao-qing Chen; Jin-bo Tang; Ke Jin (Science of The Total Environment, 2023)

Flavonoid accumulation modulates the responses of cassava tuberous roots to postharvest physiological deterioration - Feifei An; Mengjia Cui; Ting Chen; Cheng Cheng; Zhu Liu; Xiuqin Luo; Jingjing Xue; Yanqiong Tang; Jie Cai; Songbi Chen (Postharvest Biology and Technology, 2023)

Experimental checking and modeling of the influence of operation conditions on the first order kinetic constants in free water surface wetlands - Bochao Zhang; Yuanlai Cui; Bin Liao; Chi Tang; Yonghong Shu (Journal of Environmental Management, 2023)

Sequential pyrolysis of spirulina and sawdust: Interactions of volatiles from upper-bed feedstock to lower-bed biochar - Jingyi Liang; Chao Li; Lijun Zhang; Shu Zhang; Kuan Ding; Shuang Wang; Bin Li; Zhenhua Cui; Yonggui Tang; Xun Hu (Journal of Environmental Chemical Engineering, 2023)

The interaction mechanism and the functionality of yeast protein with hydrophilic and hydrophobic bioactive molecules - Haili Sun; Yifei Sun; Xin Tang; Yuanmeng Cui; Demei Meng; Yuyu Zhang; Ku Li; Hui Guo; Hai Chen; Rui Yang (Food Bioscience, 2023)

Taste characteristic and the mechanism of light-colored Maillard reaction products derived from gluten hydrolysate - Jingwen Zhu; Xue Xia; Foxin Zhang; Shiqing Song; Heping Cui; Khizar Hayat; Qiang Zhang; Xiaoming Zhang; Chi-Tang Ho (Food Bioscience, 2023)

Nano-selenium protects grass carp hepatocytes against 4-tert-butylphenol-induced mitochondrial apoptosis and necroptosis via suppressing ROS-PARP1 axis - Jiawen Cui; Minna Qiu; Yuhang Liu; Yuhao Liu; You Tang; Xiaohua Teng; Shu Li (Fish & Shellfish Immunology, 2023)

A comparative study of self-centering precast concrete walls with replaceable buckling-restrained yielding plates or friction dissipation components - Xinghua Li; Yahya C. Kurama; Gang Wu; Haoran Cui; Yuchuan Tang; Yihua Zeng (Engineering Structures, 2023)

Cooling performance and optimization of a tubular indirect evaporative cooler based on response surface methodology - Tiezhu Sun; Tingzheng Tang; Chuanjun Yang; Weichao Yan; Xin Cui; Junjie Chu (Energy and Buildings, 2023)

Interfacial modification of in-situ polymerized AMPS/NiFe2O4 quantum dots for efficient and air-stable CsPbBr3 perovskite solar cells - Jingwei Mao; Benlin He; Haojie Sui; Lifang Cui; Haiyan Chen; Yanyan Duan; Peizhi Yang; Qunwei Tang (Chemical Engineering Journal, 2023)

A numerical model of debris flows with the Voellmy model over a real terrain - Jinbo Tang; Peng Cui; Hao Wang; Yao Li (Landslides, 2023)

Correction to: Geographical, Sex, Age, and Seasonal Differences in Serum Manganese Status Among Chinese Adults with Hypertension - Hong Chen; Zhixin Cui; Wenhai Lu; Ping Wang; Jia Wang; Ziyi Zhou; Nan Zhang; Zhuo Wang; Tengfei Lin; Yun Song; Lishun Liu; Xiao Huang; et al. (Biological Trace Element Research, 2023)

Design of confined catalysts and applications in environmental catalysis: Original perspectives and further prospects - Tian Zhao; Xiaosheng Huang; Rongji Cui; Weiliang Han; Guodong Zhang; Zhicheng Tang (Journal of Cleaner Production, 2023)

Investigation on the influence of inherent AAEMs on gasification reactivity of solid digestate char - Cui Quan; Jin Zhang; Zimou Tang; Aneta Magdziarz; Chunfei Wu; Ningbo Gao (Fuel, 2023)

Reduced asynchronism between regenerative cysteine and fragments of deoxyosones promoting formation of sulfur-containing compounds through extra-added xylose and elevated temperature during thermal processing of 2‑threityl-thiazolidine-4-carboxylic acid - Yun Zhai; Xue Xia; Shibin Deng; Heping Cui; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Chemistry, 2023)

EGCG alleviated Mn exposure-caused carp kidney damage via trpm2-NLRP3-TNF-α-JNK pathway: Oxidative stress, inflammation, and tight junction dysfunction - Qin Zhou; Jiawen Cui; Yuhang Liu; Lepeng Gu; Xiaohua Teng; You Tang (Fish & Shellfish Immunology, 2023)

Arsenic metabolism, N6AMT1 and AS3MT single nucleotide polymorphisms, and their interaction on gestational diabetes mellitus in Chinese pregnant women - Xiaoshan Liang; Guanshuai Guo; Yiyun Wang; Meng Wang; Xi Chen; Jingran Zhang; Shuying Li; Liangpo Liu; Qingyu Huang; Bo Cui; Ming Zhang; Guifan Sun; et al. (Environmental Research, 2023)

Trends in elemental Pb concentrations within atmospheric PM2.5 and associated risk to human health in major cities of China - Qian Cui; Liangzhong Li; Yaqiang Cao; Bo Yang; Lindou Liu; Xiaoyan Dong; Yu'e Cha; Hongjie Ruan; Song Tang; Qiong Wang (Environmental Pollution, 2023)

Association between dental fluorosis prevalence and inflammation levels in school-aged children with low-to-moderate fluoride exposure - Huayang Tang; Mengru Wang; Gaochun Li; Mengwei Wang; Chen Luo; Guoyu Zhou; Qian Zhao; Lixin Dong; Hongliang Liu; Yushan Cui; Li Liu; Shun Zhang; et al. (Environmental Pollution, 2023)

Microtopography mediates the community assembly of soil prokaryotes on the local-site scale - Wencong Lv; Yali Liu; Jianqing Du; Li Tang; Biao Zhang; Qiang Liu; Xiaoyong Cui; Kai Xue; Yanfen Wang (CATENA, 2023)

Spatial interpolation of regional PM2.5 concentrations in China during COVID-19 incorporating multivariate data - Pengzhi Wei; Shaofeng Xie; Liangke Huang; Lilong Liu; Lilu Cui; Youbing Tang; Yabo Zhang; Chunyang Meng; Linxin Zhang (Atmospheric Pollution Research, 2023)

A preliminary study on the acoustic properties of seafloor sediment in the southern U-boundary of the South China Sea - Zhengyu Hou; Danling Tang; Yao Xiao; Jingqiang Wang; Bo Zhang; Xiaoming Cui; Peng Hao (Journal of Oceanology and Limnology, 2023)

DNAzyme-driven bipedal DNA walker triggered to hybridize silver nanoparticle probes for electrochemical detection of amyloid-β oligomer - Chenyi Zhuo; Zheng Li; Jiuying Cui; Zichun Song; Qianli Tang; Yiming Yin; Guanqun Zhang; Xianjiu Liao; Zhao Liu; Fenglei Gao (Analytica Chimica Acta, 2023)

Ecological restoration exacerbates the agriculture-induced water crisis in North China Region - Yan Zhou; Jinwei Dong; Yaoping Cui; Meng Zhao; Xinxin Wang; Qiuhong Tang; Yongqiang Zhang; Sha Zhou; Graciela Metternicht; Zhenhua Zou; Geli Zhang; Xiangming Xiao (Agricultural and Forest Meteorology, 2023)

Late Eocene—early Miocene provenance evolution of the Crocker Fan in the southern South China Sea - Yuchi Cui; Lei Shao; Wu Tang; Peijun Qiao; Goh Thian Lai; Yongjian Yao (Acta Oceanologica Sinica, 2023)

Simultaneous mitigation of arsenic and cadmium accumulation in rice grains by foliar inhibitor with ZIF-8@Ge-132 - Hao Cui; Shuting Tang; Shiqi Huang; Lidan Lei; Zhenmao Jiang; Lei Li; Shiqiang Wei (Science of The Total Environment, 2023)

Hillslope-scale variability of soil water potential over humid alpine forests: Unexpected high contribution of time-invariant component - Fei Wang; Genxu Wang; Junfang Cui; Li Guo; Xiangyu Tang; Ruxing Yang; Kewei Huang (Journal of Hydrology, 2023)

A high-efficient anisotropic continuum model for the optimization of heat transfer and chemical reaction in a packed-bed water gas shift reactor - Bo Jiang; Haonan Wang; Kewei Yu; Jing Ma; Wang Si-ma; Yuming Gao; Lin Li; Xinwei Zhang; Huiru Cui; Dawei Tang (Fuel, 2023)

Interface engineering of Fe3Se4/FeSe heterostructures encapsulated in MXene for boosting LiPS conversion and inhibiting shuttle effect - Xiaoya Zhou; Yuchen Cui; Xin Huang; Qingyuan Zhang; Biao Wang; Shaochun Tang (Chemical Engineering Journal, 2023)

3D macro/mesoporous highly reproducible amino-functionalized covalent organic framework nanospheres for fat-rich foodstuffs pretreatment in nontargeted analysis - Yan Qi; Jing Zhang; Li Zhang; Xiangyu Zhou; Wei Li; Jialin Cui; Mengdie Fan; Yushen Jin; Junwang Tang; Jianzhong Shen; Bing Shao (Chemical Engineering Journal, 2023)

Vertical distribution of PbI2 nanosheets for robust air-processed perovskite solar cells - Zhenkun Zhu; Jitao Shang; Guanqi Tang; Zhen Wang; Xiaxia Cui; Junjun Jin; Yuan Zhou; Xiang Zhang; Dan Zhang; Xiaowei Liu; Qidong Tai (Chemical Engineering Journal, 2023)

Analysis and research on the difference of design codes for vertical bearing capacity of pile foundation in cold regions - Liyun Tang; Yupeng Cui; Jianbing Chen; Gengshe Yang; Shiyuan Sun; Guoyu Li; Qiang Sun; Hailiang Jia (Cold Regions Science and Technology, 2023)

Fe-Al bimetallic oxides functionalized-biochar via ball milling for enhanced adsorption of tetracycline in water - Jiayi Tang; Yongfei Ma; Chenyu Zeng; Lie Yang; Song Cui; Suli Zhi; Fengxia Yang; Yongzhen Ding; Keqiang Zhang; Zulin Zhang (Bioresource Technology, 2023)

Effect of a Terminated PVCap on Methane Gas Hydrate Formation - Zhiguang Song; Shiyuan Cui; Cuiping Tang; Yong Chen; Deqing Liang; Sibo Wang (Journal of Marine Science and Engineering, 2023)
Polyvinylcaprolactam (PVCap) is an economic kinetic inhibitor for hydrate formation in pipelines during oil and gas transportation. However, its application is limited because of the low inhibition performance under certain conditions. In this work, a modified PVCap on its chain end is proposed. 2-amino-3-propionic acid mercapto-terminated polyvinyl caprolactam (PVCap-NH2-COOH) was synthesized and its performance as a KHI for methane hydrate formation was evaluated under different conditions. Results showed that the performance of PVCap-NH2-COOH as a KHI was better than that of PVCap at the same concentrations. Gas hydrate samples with 1 wt.% PVCap-NH2-COOH were measured using Raman spectroscopy, XRD, and cryo-SEM. PVCap-NH2-COOH had a selective action on a specific crystal surface of the hydrates and could prevent methane molecules from entering large cages. Its inhibition ability increased with the decrease in the occupancy rate of large cages. The morphology of the gas hydrate crystal changed from porous in a pure water system to a chaotic but compact structure state in the system with PVCap-NH2-COOH.

Drug repurposing of ilepcimide that ameliorates experimental autoimmune encephalomyelitis via restricting inflammatory response and oxidative stress - Zhaomin Xu; Sisi Lu; Xi Liu; Lu Tang; Zehui Liu; Jiayan Cui; Wanyan Wang; Weiqiang Lu; Jin Huang (Toxicology and Applied Pharmacology, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

The landscape of micron-scale particles including microplastics in human enclosed body fluids - Quanquan Guan; Jin Jiang; Yan Huang; Qing Wang; Zhaofeng Liu; Xuan Ma; Xiaona Yang; Yong Li; Shangqian Wang; Weiding Cui; Junwei Tang; Hua Wan; et al. (Journal of Hazardous Materials, 2023)

Distribution of per- and poly-fluoroalkyl substances and their precursors in human blood - Daxi Liu; Bo Tang; Saisai Nie; Nan Zhao; Li He; Jiansheng Cui; Weili Mao; Hangbiao Jin (Journal of Hazardous Materials, 2023)

Theoretical prediction on stability, electronic and activity properties of single-atom catalysts anchored graphene and boron phosphide heterostructures - Yanan Tang; Weiguang Chen; Mingyu Zhao; Jinlei Shi; Yingqi Cui; Zhaohan Li; Zhiwen Wang; Zhen Feng; Xianqi Dai (Fuel, 2023)

Ag doping Fe-Ti spinel sorbent for Hg0 removal from syngas and the mechanism investigation - Xiaoyang Zhang; Xiangwen Xing; Lin Cui; Pengxiang Sun; Jiyun Tang; Juan Chen; Yong Dong (Fuel, 2023)

Pore-expanded UiO-66 pellets for efficient bisphenol A adsorption - Wanyong Yang; Tao Yu; Liuxin Sun; Qing Liu; Zhaoyang Fei; Xian Chen; Zhuxiu Zhang; Jihai Tang; Mifen Cui; Xu Qiao (Chemical Engineering Journal, 2023)

An S-scheme CdS/K2Ta2O6 heterojunction photocatalyst for production of H2O2 from water and air - Cui Lai; Mengyi Xu; Fuhang Xu; Bisheng Li; Dengsheng Ma; Yixia Li; Ling Li; Mingming Zhang; Danlian Huang; Lin Tang; Shiyu Liu; Huchuan Yan; et al. (Chemical Engineering Journal, 2023)

One-step synthesis of Cu(OH)2-Cu/Ni foam cathode for electrochemical reduction of nitrate - Yuntao Liang; Yuxi Zeng; Xiaofeng Tang; Wu Xia; Biao Song; Fubing Yao; Yang Yang; Yashi Chen; Chuangxin Peng; Chengyun Zhou; Cui Lai (Chemical Engineering Journal, 2023)

Absorption, metabolism, and functions of hyaluronic acid and its therapeutic prospects in combination with microorganisms: A review - Xueli Zheng; Botao Wang; Xin Tang; Bingyong Mao; Qiuxiang Zhang; Tianmeng Zhang; Jianxin Zhao; Shumao Cui; Wei Chen (Carbohydrate Polymers, 2023)

Amygdalin alleviated TGF-β-induced epithelial-mesenchymal transition in bronchial epithelial cells - An-nan Zhang; Nan Li; Zhuo-chang Chen; Ya-li Guo; Cui-jie Tian; Dong-jun Cheng; Xue-yi Tang; Xiao-yu Zhang (Chemico-Biological Interactions, 2023)

Geographical, Sex, Age, and Seasonal Differences in Serum Manganese Status Among Chinese Adults with Hypertension - Hong Chen; Zhixin Cui; Wenhai Lu; Ping Wang; Jia Wang; Ziyi Zhou; Nan Zhang; Zhuo Wang; Tengfei Lin; Yun Song; Lishun Liu; Xiao Huang; et al. (Biological Trace Element Research, 2023)

Light-enhanced transparent hydrogel for uric acid and glucose detection by four different analytical platforms - Wei Mao; Xingwei Cai; Ruirong Pan; Sheng Tang; Fu Yang; Yanjuan Cui; Jun Sun; Wei Shen (Analytica Chimica Acta, 2023)

Pollution characteristics of groundwater in an agricultural hormone-contaminated site and implementation of Fenton oxidation process - Fang Tang; Yaru Wang; Jing Li; Shuo Sun; Yuhua Su; Hongxu Chen; Wu Cui; Chaocheng Zhao; Qiyou Liu (Environmental Science and Pollution Research, 2022)

Using short-interval landslide inventories to build short-term and overall spatial prediction models for earthquake-triggered landslides based on machine learning for the 2018 Lombok earthquake sequence - Changhu Xue; Kejie Chen; Hui Tang; Chaoqi Lin; Wenfeng Cui (Natural Hazards, 2022)

Correction to: Genome sequencing of Colletotrichum gloeosporioides ES026 reveals plausible pathway of HupA - Haiyang Xia; Hamza Armghan Noushahi; Aamir Hamid Khan; Ying Liu; Andreea Cosoveanu; Lingli Cui; Jing Tang; Shehzad Iqbal; Shaohua Shu (Molecular Biology Reports, 2022)

Genome sequencing of Colletotrichum gloeosporioides ES026 reveals plausible pathway of HupA - Haiyang Xia; Hamza Armghan Noushahi; Aamir Hamid Khan; Ying Liu; Andreea Cosoveanu; Lingli Cui; Jing Tang; Shehzad Iqbal; Shaohua Shu (Molecular Biology Reports, 2022)

Saline-alkali stress reduces soil bacterial community diversity and soil enzyme activities - Dihe Yang; Lu Tang; Ying Cui; Jiaxin Chen; Lei Liu; Changhong Guo (Ecotoxicology, 2022)

Bi-LSTM-GPR algorithms based on a high-density electrical method for inversing the moisture content of landslide - Lu Xiaochun; Cui Xue; Xiong Bobo; Tian Bin; Tu Xiaolong; Tang Zhigang (Bulletin of Engineering Geology and the Environment, 2022)

Paenibacillus hamazuiensis sp. nov., a bacterium isolated from Hamazui hot spring in Yunnan province, south-west China - Juan Wang; Ming Deng; En-Min Zhou; Lei Ran; Cui-Ping Miao; Yi-Qing Li; Jun-Mei Ding; Shu-Kun Tang (Archives of Microbiology, 2022)

No Association Was Found Between Mild Iodine Deficiency During Pregnancy and Pregnancy Outcomes: a Follow-up Study Based on a Birth Registry - Xueying Cui; Huiting Yu; Zhengyuan Wang; Hai Wang; Zehuan Shi; Wei Jin; Qi Song; Changyi Guo; Hongmei Tang; Jiajie Zang (Biological Trace Element Research, 2022)
Background Severe iodine deficiency during gestation is associated with adverse pregnancy outcomes; however, the impact of mild-to-moderate iodine deficiency, though prevalent in pregnancy, remains unclear. Methods We extracted follow-up data for 7435 pregnant women from a national iodine deficiency disorders monitoring program from 2016 to 2018 and a mother–child cohort study in 2017 based on a birth registry in Shanghai. Birth outcomes were collected from the registry. Spot urine and household salt samples were collected for iodine testing. Single-factor analysis and logistic regression were used to evaluate the association between maternal iodine status and pregnancy outcomes. Results The median urine iodine level in pregnant women was 137.5 μg/L (interquartile range 82.4–211.5), suggesting mild deficiency according to WHO standards. The incidence of pregnancy termination, preterm birth, congenital malformations, low birth weight, and cesarean section was 3.2%, 4.3%, 1.4%, 2.7%, and 45.2% in the mildly iodine-deficient group and 3.4%, 4.5%, 1.4%, 2.7%, and 44.5% in the normal group, respectively. After adjusting for maternal age and education, trimesters, and preterm birth rate in the general population, the odds ratios for any outcome did not differ significantly between the two groups. Conclusion The present study suggests that mild maternal iodine deficiency is not associated with adverse pregnancy outcomes.

Reconstruction of ocean temperature and salinity profiles in the Northern South China Sea using satellite observations - Bo Tang; Dandan Zhao; Chaoran Cui; Xinhua Zhao (Frontiers in Marine Science, 2022)
Based on historical temperature and salinity (T–S) profiles, the correlation between the sea surface temperature (SST) anomaly, sea surface dynamic height (SSH) anomaly, and temperature profile anomaly is constructed by regression analysis. A three-dimensional temperature field is reconstructed in the northern South China Sea by satellite SST and SSH, with daily temporal and 0.25°×0.25° spatial resolutions. The three-dimensional salinity field is also reconstructed based on the correlation between salinity and temperature. Compared with the observational T–S profiles, the reconstructed T–S field reflects the characteristics and structure and accurately describes the mesoscale variability of the ocean temperature field. The new expanded T–S field can be used as the initial field in numerical models and be assimilated into numerical reanalysis and prediction systems, improving their output.

Genome-wide identification of chicken bursae of Fabricius miRNAs in response to very virulent infectious bursal disease virus - Xuewei Huang; Yue Li; Xiaona Wang; Junyan Zhang; Li Wang; Han Zhou; Yanping Jiang; Wen Cui; Xinyuan Qiao; Yijing Li; Lijie Tang (Archives of Virology, 2022)

Dyadobacter diqingensis sp. nov., isolated from Baima snow mountain of Diqing Tibetan Autonomous Prefecture in Yunnan province, south-west China - Lei Ran; Man Peng; Wei-Qun Wang; Yu-Zhou Feng; Juan Wang; Yu Wang; Cui-Ying Li; Xin-Xing Liu; Wei-Xun Chunyu; Shu-Kun Tang (Archives of Microbiology, 2022)

Integrating life cycle assessment and a farmer survey of management practices to study environmental impacts of peach production in Beijing, China - Ziyue Li; Yongliang Chen; Fanlei Meng; Qi Shao; Mathew R. Heal; Fengling Ren; Aohan Tang; Jiechen Wu; Xuejun Liu; Zhenling Cui; Wen Xu (Environmental Science and Pollution Research, 2022)

Characteristics and trends of grassland degradation research - Tong Li; Lizhen Cui; Michele Scotton; Junfu Dong; Zhihong Xu; Rongxiao Che; Li Tang; Shuohao Cai; Wenchao Wu; Davide Andreatta; Yanfen Wang; Xiufang Song; et al. (Journal of Soils and Sediments, 2022)

Prediction of drought/flood intensities based on a 500-year time series in three different climate provinces of China - Yu Peng; Zhaohua Wang; Yixin Cui; Yali Su; Yiyun Tang; Shiqian Luo; Lianlin Liu; Yanqiu Zhou; Jihui Dong; Wentao Wang; Xiang Li; Jiaxin Shang; et al. (Regional Environmental Change, 2022)

Potential of phytomedicine in the treatment of inflammatory bowel disease - Jie Tang; Dong Xu; Xin-Ran Dong; Yi-Lun Wang; Kun-Tang Wang; Yue Wang; Tao Qiao; Yuan-Lu Cui (Phytochemistry Reviews, 2022)

Wood decay fungi: an analysis of worldwide research - Tong Li; Lizhen Cui; Xiufang Song; Xiaoyong Cui; Yulian Wei; Li Tang; Yanhong Mu; Zhihong Xu (Journal of Soils and Sediments, 2022)
Purpose Wood decay fungi are the only forms of life capable of degrading wood to its initial constituents, greatly contributing to the soil ecosystem. This study summarizes the current research status and development characteristics of global wood decay fungi research, in order to better understand their role in soils. Methods A bibliometric analysis was applied to the literature from 1913 to 2020, based on data from the Web of Science (WOS) Core Collection. For this, various bibliometric analysis methods, R (Biblioshiny package), and VOSviewer were applied. Results A total of 8089 documents in this field were identified in the WOS Core Collection. The annual number of publications tended to increase, with exponential growth after 2008. Researchers in this field were mainly concentrated in North Europe, the USA, and China. Biotechnology, applied microbiology, environmental sciences, and microbiology were the most popular WOS categories. Bioresource Technology and Applied Environmental Microbiology were the top two journals with the most citations. The top three authors with the most published papers were Dai YC, Martinez AT, and Cui BK. Co-occurrence analysis of author keywords identified six clusters, mainly divided into three categories: the classification and diversity, the degradation mechanisms, and the ecological functions of wood decay fungi. Clustering results further showed that the lignin degradation process and the application of wood decay fungi in industrial production and soil contamination remediation are current research hotspots. Conclusions We present a comprehensive and systematic overview of research related to wood decay fungi and provide a deep perspective to understand the associated research progress. This is important for facilitating the development of a profound understanding of the contribution of wood decay fungi to soil systems and the degradation of soil contaminants.

The seed primer and biofertilizer performances of living Chlorella pyrenoidosa on Chenopodium quinoa under saline-alkali condition - Chen Ma; Hongli Cui; Chenggang Ren; Jianchao Yang; Zhengyi Liu; Tao Tang; Chunli Ji; Chunhui Zhang; Jinai Xue; Runzhi Li (Journal of Applied Phycology, 2022)

Periplaneta americana extract ameliorates dextran sulfate sodium-induced ulcerative colitis via immunoregulatory and PI3K/AKT/NF-κB signaling pathways - Lianli Ni; Qian Lu; Miao Tang; Lu Tao; Hairong Zhao; Chenggui Zhang; Yun Yu; Xiumei Wu; Heng Liu; Ri Cui (Inflammopharmacology, 2022)

Numerical simulation of the pore-fracture propagation law of single-hole shale during hydraulic fracturing with fluid–solid coupling - Nuo Ren; Zhonghu Wu; Huailei Song; Yili Lou; Hengtao Cui; Motian Tang (Arabian Journal of Geosciences, 2022)

CmPMRl and CmPMrs are responsible for resistance to powdery mildew caused by Podosphaera xanthii race 1 in Melon - Haonan Cui; Chao Fan; Zhuo Ding; Xuezheng Wang; Lili Tang; Yingdong Bi; Feishi Luan; Peng Gao (Theoretical and Applied Genetics, 2022)

The solar wind plasma upstream of Mars observed by Tianwen-1: Comparison with Mars Express and MAVEN - Kai Fan; Limei Yan; Yong Wei; Aibing Zhang; Linggao Kong; Markus Fränz; Fei He; Lihui Chai; Chongjing Yuan; Yuqi Wang; Jun Zhong; Zhaojin Rong; et al. (Science China Earth Sciences, 2022)

Cavin-1 promotes M2 macrophages/microglia polarization via SOCS3 - Wei Huang; Yiyi Hong; Wenjing He; Li Jiang; Wen Deng; Biyan Peng; Fen Tang; Chaolan Shen; Qianqian Lan; Hui Huang; Haibin Zhong; Jian Lv; et al. (Inflammation Research, 2022)

Depth-resolved numerical model of dam break mud flows with Herschel-Bulkley rheology - Jin-bo Tang; Peng-zhi Lin; Peng Cui (Journal of Mountain Science, 2022)

A Review of Parallel Implementations for the Smith–Waterman Algorithm - Zeyu Xia; Yingbo Cui; Ang Zhang; Tao Tang; Lin Peng; Chun Huang; Canqun Yang; Xiangke Liao (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Electrokinetic stabilization of marine clayey soil using magnesium chloride solution: A green soil stabilizer - Yongqiang Tang; Ningwei Wang; Feng Xu; Da Teng; Xiaoming Cui (Marine Georesources & Geotechnology, 2022)

PHD2 attenuates high-glucose-induced blood retinal barrier breakdown in human retinal microvascular endothelial cells by regulating the Hif-1α/VEGF pathway - Jia Li; Xi Lu; Liqing Wei; Dan Ye; Jianqiang Lin; Xiaoyu Tang; Kaixuan Cui; Shanshan Yu; Yue Xu; Xiaoling Liang (Inflammation Research, 2022)

Identification of QTLs for cold tolerance at the booting and flowering stages in rice (Oryza sativa L.) - Lina Zhang; Jianghong Tang; Di Cui; Cuifeng Tang; Xiaoding Ma; Xinxiang A; Bing Han; Guilan Cao; Zhengwu Zhao; Hee-Jong Koh; Longzhi Han (Euphytica, 2021)

Overexpression of SMC4 predicts a poor prognosis in cervical cancer and facilitates cancer cell malignancy phenotype by activating NF-κB pathway - Hui He; Cui Zheng; Yunxian Tang (Human Cell, 2021)

Porcine deltacoronavirus and its prevalence in China: a review of epidemiology, evolution, and vaccine development - Pan Tang; Enhui Cui; Yihong Song; Ruoqian Yan; Jingyu Wang (Archives of Virology, 2021)

Stimulation of N 2 O emission via bacterial denitrification driven by acidification in estuarine sediments - Xiaoxuan Su; Teng Wen; Yingmu Wang; Junshi Xu; Li Cui; Jinbo Zhang; Ximei Xue; Kai Ding; Yijia Tang; Yong‐guan Zhu (Global Change Biology, 2021)
Ocean acidification in nitrogen‐enriched estuaries has raised global concerns. For decades, biotic and abiotic denitrification in estuarine sediments has been regarded as the major ways to remove reactive nitrogen, but they occur at the expense of releasing greenhouse gas nitrous oxide (N 2 O). However, how these pathways respond to acidification remains poorly understood. Here we performed a N 2 O isotopocules analysis coupled with respiration inhibition and molecular approaches to investigate the impacts of acidification on bacterial, fungal, and chemo‐denitrification, as well as N 2 O emission, in estuarine sediments through a series of anoxic incubations. Results showed that acidification stimulated N 2 O release from sediments, which was mainly mediated by the activity of bacterial denitrifiers, whereas in neutral environments, N 2 O production was dominated by fungi. We also found that the contribution of chemo‐denitrification to N 2 O production cannot be ignored, but was not significantly affected by acidification. The mechanistic investigation further demonstrated that acidification changed the keystone taxa of sedimentary denitrifiers from N 2 O‐reducing to N 2 O‐producing ones and reduced microbial electron‐transfer efficiency during denitrification. These findings provide novel insights into how acidification stimulates N 2 O emission and modulates its pathways in estuarine sediments, and how it may contribute to the acceleration of global climate change in the Anthropocene.

A combined semi-analytical algorithm for retrieving total suspended sediment concentration from multiple missions: a case study of the China Eastern Coastal Zone - Zhongli Liu; Jun Chen; Tingwei Cui; Junwu Tang; Lin Wang (International Journal of Remote Sensing, 2021)

Structural and Functional Changes in the Cerebellum and Brainstem in Patients with Benign Paroxysmal Positional Vertigo - Qian Zhu; Wei Chen; Yangyang Cui; Jing Wu; Liang Shu; Xuhong Sun; Zhaoxia Qin; Wei Tang; Tingting Gao; Qian Xu; Chun-Yan Jiang; Jianren Liu; et al. (The Cerebellum, 2021)

Regional brain network and behavioral alterations in EGR3 gene transfected rat model of schizophrenia - Wenwen Gao; Guangfei Li; Xiaowei Han; Zeyu Song; Shuai Zhao; Feiyi Sun; Hong Ma; Ailing Cui; Yige Wang; Xiuxiu Liu; Yue Chen; Lu Zhang; et al. (Brain Imaging and Behavior, 2021)

Interaction of magnolia bark extracts with Staphylococcus aureus DNA and evaluation of the stability of their antibacterial activities - Shu-Mei Cui; Hai-yun Liang; Ting Li; Ke-Ke He; Yu-Mei Zheng; Meng Tang; Chong-rong Ke; Li-Ya Song (Archives of Microbiology, 2021)

Diverse transcriptional patterns of homoeologous recombinant transcripts in triploid fish (Cyprinidae) - Li Ren; Xueyin Zhang; Jiaming Li; Xiaojing Yan; Xin Gao; Jialin Cui; Chenchen Tang; Shaojun Liu (Science China Life Sciences, 2021)

Visualization of GNSS multipath effects and its potential application in IGS data processing - Weiming Tang; Yawei Wang; Xuan Zou; Yangyang Li; Chenlong Deng; Jianhui Cui (Journal of Geodesy, 2021)

Insights from comparative proteomic analysis into degradation of phenanthrene and salt tolerance by the halophilic Martelella strain AD-3 - Xin Chen; Weiwei Wang; Haiyang Hu; Hongzhi Tang; Yongdi Liu; Ping Xu; Kuangfei Lin; Changzheng Cui (Ecotoxicology, 2021)

Effect of DAOA genetic variation on white matter alteration in corpus callosum in patients with first-episode schizophrenia - Wenjun Su; Tianyuan Zhu; Lihua Xu; Yanyan Wei; Botao Zeng; Tianhong Zhang; Huiru Cui; Junjie Wang; Yuping Jia; Jinhong Wang; Donald C. Goff; Yingying Tang; et al. (Brain Imaging and Behavior, 2021)

Genetic mapping of highly versatile and solvent‐tolerant Pseudomonas putida B6 ‐2 ( ATCC BAA ‐2545) as a ‘superstar’ for mineralization of PAHs and dioxin‐like compounds - Weiwei Wang; Qinggang Li; Lige Zhang; Jie Cui; Hao Yu; Xiaoyu Wang; Xingyu Ouyang; Fei Tao; Ping Xu; Hongzhi Tang (Environmental Microbiology, 2021)
Summary Polycyclic aromatic hydrocarbons (PAHs) and dioxin‐like compounds, including sulfur, nitrogen and oxygen heterocycles, are widespread and toxic environmental pollutants. A wide variety of microorganisms capable of growing with aromatic polycyclic compounds are essential for bioremediation of the contaminated sites and the Earth's carbon cycle. Here, cells of Pseudomonas putida B6‐2 (ATCC BAA‐2545) grown in the presence of biphenyl (BP) are able to simultaneously degrade PAHs and their derivatives, even when they are present as mixtures, and tolerate high concentrations of extremely toxic solvents. Genetic analysis of the 6.37 Mb genome of strain B6‐2 reveals coexistence of gene clusters responsible for central catabolic systems of aromatic compounds and for solvent tolerance. We used functional transcriptomics and proteomics to identify the candidate genes associated with catabolism of BP and a mixture of BP, dibenzofuran, dibenzothiophene and carbazole. Moreover, we observed dynamic changes in transcriptional levels with BP, including in metabolic pathways of aromatic compounds, chemotaxis, efflux pumps and transporters potentially involved in adaptation to PAHs. This study on the highly versatile activities of strain B6‐2 suggests it to be a potentially useful model for bioremediation of polluted sites and for investigation of biochemical, genetic and evolutionary aspects of Pseudomonas .

Development of organelle single nucleotide polymorphism (SNP) markers and their application for the identification of cytoplasmic inheritance patterns in Pyropia yezoensis (Bangiales, Rhodophyta) - Lu Wang; Junhao Wang; Yunke Zhu; Zhengcai Cui; Fanna Kong; Xianghai Tang; Yunxiang Mao (Journal of Oceanology and Limnology, 2021)

Fusarium solani G6, a novel vitexin-producing endophytic fungus: characterization, yield improvement and osteoblastic proliferation activity - Pei-jia Tang; Zhi-hui Zhang; Li-li Niu; Cheng-bo Gu; Wen-yi Zheng; Hai-chao Cui; Xiao-han Yuan (Biotechnology Letters, 2021)

Simulated Sensitivity of Ozone Generation to Precursors in Beijing during a High O3 Episode - Meng Cui; Xingqin An; Li Xing; Guohui Li; Guiqian Tang; Jianjun He; Xin Long; Shuman Zhao (Advances in Atmospheric Sciences, 2021)

Ziziphus jujuba Mill., a plant used as medicinal food: a review of its phytochemistry, pharmacology, quality control and future research - Shi-Jun Liu; Yan-Ping Lv; Zhi-Shu Tang; Yu Zhang; Hong-Bo Xu; Dong-Bo Zhang; Chun-Li Cui; Hong-Bo Liu; Huan-Huan Sun; Zhong-Xing Song; Si-Min Wei (Phytochemistry Reviews, 2021)

Seismic signal characteristics and interpretation of the 2020 “6.17” Danba landslide dam failure hazard chain process - Yan Yan; Yifei Cui; Dingzhu Liu; Hui Tang; Yongjian Li; Xin Tian; Lei Zhang; Sheng Hu (Landslides, 2021)

Reservoir operation-induced hydrodynamic disturbances affect the distributions of Cd, Cu, and Pb in the riparian soil of the water-level-fluctuation zone - Wei Zhang; Honglei Sun; Yun Liang; Xiangyu Tang; Yuxiao Fang; Junfang Cui; Xingmin Wang; Qigang Zhou (Journal of Soils and Sediments, 2021)

Comparative analysis of genetic diversity of rice (Oryza sativa L.) varieties cultivated in different periods in China - Ruyu Tang; Di Cui; Jian Zhou; Wenqiu Li; Xiaoding Ma; Bing Han; Xiaohong Guo; Zhengwu Zhao; Longzhi Han (Genetic Resources and Crop Evolution, 2021)

Acoustic Emission Investigation on Crack Propagation Mode of Sandstone During Brazil Splitting Process - Xiaohu Zhang; Xuebin Cui; Qiongqiong Tang; Yanhua Sun (Geotechnical and Geological Engineering, 2021)

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Combined effects of arbuscular mycorrhizae fungus and composted pig manure on the growth of ryegrass and uptake of Cd and Zn in the soil from an e-waste recycling site - Jun Meng; Zhonghua Cui; Henglei Zhang; Jin Zhang; Xianjin Tang; Ming Hung Wong; Shengdao Shan (Environmental Science and Pollution Research, 2021)

Effects of Selenium on Arsenic-Induced Liver Lesions in Broilers - Zhihua Ren; Huidan Deng; Youtian Deng; Wenjiao Tang; Qiang Wu; Zhicai Zuo; Hengmin Cui; Yanchun Hu; Shumin Yu; Sheng-yu Xu; Junliang Deng (Biological Trace Element Research, 2021)

Comparative metabolomics of two saline-alkali tolerant plants Suaeda glauca and Puccinellia tenuiflora based on GC-MS platform - Xueyan Lu; Qi Chen; Xiaoyang Cui; Ann Abozeid; Yang Liu; Jia Liu; Zhonghua Tang (Natural Product Research, 2021)

Warming and grazing interact to affect root dynamics in an alpine meadow - Yibo Wu; Biao Zhu; David M. Eissenstat; Shiping Wang; Yanhong Tang; Xiaoyong Cui (Plant and Soil, 2021)

CmCLCa Plays a Key Role in the Storage of Nitrate in Chrysanthemum Leaf Vacuoles - Cui Chen; Zhen Zhang; Xiaoqi Xu; Qi Tang; Jiaxi Liu; Bowen Liu; Chengshu Zheng (Journal of Plant Growth Regulation, 2021)

The phase changes of M1/M2 phenotype of microglia/macrophage following oxygen-induced retinopathy in mice - Jia Li; Shanshan Yu; Xi Lu; Kaixuan Cui; Xiaoyu Tang; Yue Xu; Xiaoling Liang (Inflammation Research, 2021)

Resazurin as an indicator of reducing capacity for analyzing the physiologic status of deep-sea bacterium Photobacterium phosphoreum ANT-2200 - Jie Dai; Hongzhi Tang; Xuegong Li; Claire-Lise Santini; Wenpeng Cui; Na Liu; Xiaoqing Qi; Xuehua Cui; Alain Grossi; Philippe Notareschi; Wei-Jia Zhang; Long-Fei Wu (Journal of Oceanology and Limnology, 2021)

Effects of Rhein-8-O-β-D-glucopyranoside on the Biofilm Formation of Streptococcus mutans - Yaochao Zhang; Yong Zhu; Yanping Zuo; Chengfang Tang; Fang Zhou; Xiaoming Cui; Lin Wang (Current Microbiology, 2021)

Damage Analysis of Soaking Gypsum and Safety Evaluation of Goaf: Based on Energy Dissipation Theory - Xiaoding Xu; Xuebin Cui; Xue Liu; Qiongqiong Tang; Xiaohu Zhang; Yanhua Sun (Geotechnical and Geological Engineering, 2020)

Groundwater resources survey of tongchuan city using the audio magnetotelluric method - Zhi-min Xu; Jing-tian Tang; Guang Li; Hui-Cui Xin; Zhang-jian Xu; Xin-ping Tan; Jin Li (Applied Geophysics, 2020)

Fasudil attenuates glial cell-mediated neuroinflammation via ERK1/2 and AKT signaling pathways after optic nerve crush - Wei Huang; Qianqian Lan; Li Jiang; Wenya Yan; Fen Tang; Chaolan Shen; Hui Huang; Haibin Zhong; Jian Lv; Siming Zeng; Min Li; Zhongxiang Mo; et al. (Molecular Biology Reports, 2020)

A pair of new neo -clerodane diterpenoid epimers from the roots of Croton crassifolius and their anti-inflammatory - Dong-Bo Zhang; Zhi-Shu Tang; Pei Xie; Yan-Ni Liang; Jin-Gao Yu; Zhen Zhang; Dong-Zhu Duan; Chun-Li Cui; Zhong-Xing Song; Li Ren; Zheng Wang; Dao-Geng Yu (Natural Product Research, 2020)

The transcriptional factor GATA-4 negatively regulates Hsp70 transcription in Crassostrea hongkongensis - Tinglong Hou; Delin Xu; Miao Cui; Huiru Liu; Yaowu Fu; Lingli Zhang; Lei Tang; Yanmeng Liu; Qizhong Zhang (Molecular Biology Reports, 2020)

Association of LHPP genetic variation (rs35936514) with structural and functional connectivity of hippocampal-corticolimbic neural circuitry - Lingling Cui; Xiaohong Gong; Miao Chang; Zhiyang Yin; Haiyang Geng; Yanzhuo Song; Jing Lv; Ruiqi Feng; Fei Wang; Yanqing Tang; Ke Xu (Brain Imaging and Behavior, 2020)

Post deformation characteristics of a large-scale slope on the right bank of the Lancang River, Yunnan, China - Yao Jiang; Zhankui Tang; Qingwen Yang; Shenghua Cui (Arabian Journal of Geosciences, 2020)

High Canonical Wnt/β-Catenin Activity Sensitizes Murine Hematopoietic Stem and Progenitor Cells to DNA Damage - Yiting Wang; Hui Cui; Si Tao; Ting Zeng; Jianying Wu; Zhendong Tao; Liu Zhang; Bing Zou; Zhiyang Chen; George B. Garside; Duozhuang Tang (Stem Cell Reviews and Reports, 2020)
Aging is characterized by the accumulation of DNA damage and a decrease in stem cell functionality, yet molecular mechanisms that limit the maintenance of stem cells in response to DNA damage remain to be delineated. Here we show in mouse models that DNA damage leads to a transient over-activation of Wnt signaling in hematopoietic stem cells (HSCs), and that high activity of canonical Wnt/β-catenin signaling sensitizes HSCs to DNA damage induced by X-irradiation which results in preferential maintenance of HSCs with low levels of Wnt signaling. The study shows that genetic or chemical activation of canonical Wnt signaling enhances radiosensitivity of HSCs while inhibition of Wnt signaling decreases it. Together, these results indicate that levels of Wnt signaling activity mediate heterogeneity in the sensitivity of HSCs to DNA damage induced depletion. These findings could be relevant for molecular alterations and selection of stem cells in the context of DNA damage accumulation during aging and cancer formation.

The expression and role of PIDD in retina after optic nerve crush - Fen Tang; Fan Xu; Ling Cui; Wei Huang; Li Jiang; Lifei Chen; Wenya Yan; Wenjing He; Chaolan Shen; Hui Huang; Jian Lv; Xin Zhao; et al. (Journal of Molecular Histology, 2020)

Study on the association between ambient air pollution and daily cardiovascular death in Hefei, China - Jixiang Xu; Wenfeng Geng; Xiya Geng; LongJiang Cui; Tao Ding; Changchun Xiao; Junqing Zhang; Jing Tang; Jinxia Zhai (Environmental Science and Pollution Research, 2020)

Synthesis and biological evaluation of C-13, C-14 modified taxane analogues from 1-deoxybaccatin VI - Ping Tang; Hai-Xia Lin; Tian-Hai Yuan; Yong-Mei Cui (Natural Product Research, 2019)

QTL analysis of main agronomic traits in rice under low temperature stress - Jianghong Tang; Xiaoding Ma; Di Cui; Bing Han; Leiyue Geng; Zhengwu Zhao; Yafei Li; Longzhi Han (Euphytica, 2019)

Correction to: Short-term dietary restriction in old mice rejuvenates the aging-induced structural imbalance of gut microbiota - Ting Zeng; Hui Cui; Duozhuang Tang; George B. Garside; Yiting Wang; Jianying Wu; Zhendong Tao; Liu Zhang; Si Tao (Biogerontology, 2019)
In the original publication of the article, the alphabets in figures were published in upper case and mismatched with the figure legends. The corrected figures and figure legends are given in this Correction.

Short-term dietary restriction in old mice rejuvenates the aging-induced structural imbalance of gut microbiota - Ting Zeng; Hui Cui; Duozhuang Tang; George B. Garside; Yiting Wang; Jianying Wu; Zhendong Tao; Liu Zhang; Si Tao (Biogerontology, 2019)

HprK Xcc is a serine kinase that regulates virulence in the Gram‐negative phytopathogen Xanthomonas campestris - Rui‐Fang Li; Ping Cui; Ping‐Zhen Wei; Xing‐Yan Liu; Ji‐Liang Tang; Guang‐Tao Lu (Environmental Microbiology, 2019)
Summary The HprK serine kinase is a component of the phosphoenolpyruvate phosphotransferase system (PTS) of bacteria that generally regulates catabolite repression through phosphorylation/dephosphorylation of the PTS protein PtsH at a conserved serine residue. However, many bacteria do not encode a complete PTS or even have an HprK homologue. Xanthomonas campestris pv. campestris ( Xcc ) is a pathogen that cause black rot disease in crucifer plants and one of the few Gram‐negative bacteria that encodes a homologue of HprK protein (herein HprK Xcc ). To gain insight into the role of HprK Xcc and other PTS‐related components in Xcc we individually mutated and phenotypically assessed the resulting strains. Deletion of hprK Xcc demonstrated its requirement for virulence and other diverse cellular processes associated including extracellular enzyme activity, extracellular‐polysaccharide production and cell motility. Global transcriptome analyses revealed the HprK Xcc had a broad regulatory role in Xcc . Additionally, through overexpression, double gene deletion and transcriptome analysis we demonstrated that hprK Xcc shares an epistatic relationship with ptsH . Furthermore, we demonstrate that HprK Xcc is a functional serine kinase, which has the ability to phosphorylate PtsH. Taken together, the data illustrates the previously unappreciated global regulatory role of HprK Xcc and previously uncharacterized PTS components that control virulence in this pathogen.

Characterization on the conservation and diversification of miRNA156 gene family from lower to higher plant species based on phylogenetic analysis at the whole genomic level - Chen Wang; Qinglian Wang; Xudong Zhu; Menjie Cui; Haifeng Jia; Wenying Zhang; Wei Tang; Xiangpeng Leng; Wenbiao Shen (Functional & Integrative Genomics, 2019)

Genetic mapping reveals a candidate gene for egusi seed in watermelon - Feishi Luan; Chao Fan; Lei Sun; Haonan Cui; Sikandar Amanullah; Lili Tang; Peng Gao (Euphytica, 2019)

An integrated strategy to identify genes responsible for sesquiterpene biosynthesis in turmeric - Jingru Sun; Guanghong Cui; Xiaohui Ma; Zhilai Zhan; Ying Ma; Zhongqiu Teng; Wei Gao; Yanan Wang; Tong Chen; Changjiangsheng Lai; Yujun Zhao; Jinfu Tang; et al. (Plant Molecular Biology, 2019)

QTL analysis and candidate gene identification for plant height in cotton based on an interspecific backcross inbred line population of Gossypium hirsutum × Gossypium barbadense - Jianjiang Ma; Wenfeng Pei; Qifeng Ma; Yanhui Geng; Guoyuan Liu; Ji Liu; Yupeng Cui; Xia Zhang; Man Wu; Xingli Li; Dan Li; XinShan Zang; et al. (Theoretical and Applied Genetics, 2019)

A pathogenesis-related protein 10 gene PnPR10–3 was involved in molecular interaction between Panax notoginseng and Fusarium solani - Bifeng Tang; Xin Li; Limei Pu; Qin Zhao; Xiuming Cui; Feng Ge; Diqiu Liu (Australasian Plant Pathology, 2019)

Spontaneous Regional Brain Activity in Healthy Individuals is Nonlinearly Modulated by the Interaction of ZNF804A rs1344706 and COMT rs4680 Polymorphisms - Lingling Cui; Fei Wang; Miao Chang; Zhiyang Yin; Guoguang Fan; Yanzhuo Song; Yange Wei; Yixiao Xu; Yifan Zhang; Yanqing Tang; Xiaohong Gong; Ke Xu (Neuroscience Bulletin, 2019)

Layer regrouping optimization for multilayer heterogeneous reservoirs at a high water cut stage - Wu Zhongwei; Cui Chuanzhi; Japan Trivedi; Li Rongtao; Tang Wenhao; Wei Zijian; Gao Min (Arabian Journal of Geosciences, 2019)

Impact of ambient temperature on hospital admissions for cardiovascular disease in Hefei City, China - Longjiang Cui; Xiya Geng; Tao Ding; Jing Tang; Jixiang Xu; Jinxia Zhai (International Journal of Biometeorology, 2019)

Oxidative effects of lungs in Wistar rats caused by long-term exposure to four kinds of China representative chrysotile - Yan Cui; Yuxin Zha; Tao Li; Jun Bai; Lanlan Tang; Jianjun Deng; Renjiang He; Faqin Dong; Qingbi Zhang (Environmental Science and Pollution Research, 2019)

Cyclosporin A Protected Cardiomyocytes Against Oxidative Stress Injury by Inhibition of NF-κB Signaling Pathway - Meng Ma; Xiaohui Ma; Jie Cui; Yifeng Guo; Xiuqin Tang; Chuanmin Chen; Ying Zhu; Chao Cui; Gang Wang (Cardiovascular Engineering and Technology, 2019)

Pastoralists’ perception of and adaptation strategies for climate change: associations with observed climate variability - Qin Zhang; Fengqi Cui; Luwei Dai; Bing Feng; Yunjing Lu; Haiping Tang (Natural Hazards, 2019)

Selenium Rescues Aflatoxin B1-Inhibited T Cell Subsets and Cytokine Levels in Cecal Tonsil of Chickens - Fengyuan Wang; Zhicai Zuo; Kejie Chen; Xi Peng; Jing Fang; Hengmin Cui; Gang Shu; Min He; Li Tang (Biological Trace Element Research, 2019)

FLA, which encodes a homolog of UBP, is required for chlorophyll accumulation and development of lemma and palea in rice - Xiaoding Ma; Jiani Zhang; Bing Han; Jianghong Tang; Di Cui; Longzhi Han (Plant Cell Reports, 2019)

Chinese society of cardiology expert consensus statement on the diagnosis and treatment of adult fulminant myocarditis - Daowen Wang; Sheng Li; Jiangang Jiang; Jiangtao Yan; Chunxia Zhao; Yan Wang; Yexin Ma; Hesong Zeng; Xiaomei Guo; Hong Wang; Jiarong Tang; Houjuan Zuo; et al. (Science China Life Sciences, 2019)

An increase of estrogen receptor α protein level regulates BDE-209-mediated blood-testis barrier disruption during spermatogenesis in F1 mice - Jinxia Zhai; Xiya Geng; Tao Ding; Jun Li; Jing Tang; Daojun Chen; Longjiang Cui; Qizhi Wang (Environmental Science and Pollution Research, 2019)

Condition dependence of advertisement calls in male African clawed frogs - Xiaocui Wang; Zhi-Jun Zhao; Yan Cao; Jianguo Cui; Yezhong Tang; Jingfeng Chen (Journal of Ethology, 2019)

Three new isoflavones from the Pueraria montana var. lobata (Willd.) and their bioactivities - Tinghui Cui; Shiyun Tang; Chunbo Liu; Zhenjie Li; Qin Zhu; Junheng You; Xiaoxi Si; Fengmei Zhang; Pei He; Zhihua Liu; Mingming Miao; Guangyu Yang; et al. (Natural Product Research, 2018)

Characterization of Vv-miR156: Vv-SPL pairs involved in the modulation of grape berry development and ripening - Mengjie Cui; Chen Wang; Wenying Zhang; Tariq Pervaiz; Muhammad Salman Haider; Wei Tang; Jinggui Fang (Molecular Genetics and Genomics, 2018)

Comparative genomics and systematics of Betaphycus, Eucheuma, and Kappaphycus (Solieriaceae: Rhodophyta) based on mitochondrial genome - Yue Li; Na Liu; Xumin Wang; Xianming Tang; Lei Zhang; Maria Dyah Nur Meinita; Guoliang Wang; Hongxin Yin; Yuemei Jin; Haiyang Wang; Cui Liu; Shan Chi; et al. (Journal of Applied Phycology, 2018)

The impact of GJA8 SNPs on susceptibility to age-related cataract - Xiaoning Yu; Xiyuan Ping; Xin Zhang; Yilei Cui; Hao Yang; Xiajing Tang; Yelei Tang; Xingchao Shentu (Human Genetics, 2018)

Auditory sensitivity exhibits sexual dimorphism and seasonal plasticity in music frogs - Ping Yang; Fei Xue; Jianguo Cui; Steven E. Brauth; Yezhong Tang; Guangzhan Fang (Journal of Comparative Physiology A, 2018)

An improved ionosphere interpolation algorithm for network RTK in low-latitude regions - Jianhui Cui; Weiming Tang; Lei Jin; Chenlong Deng; Xuan Zou; Shengfeng Gu (GPS Solutions, 2018)

White Matter Deficits Underlying the Impaired Consciousness Level in Patients with Disorders of Consciousness - Xuehai Wu; Jiaying Zhang; Zaixu Cui; Weijun Tang; Chunhong Shao; Jin Hu; Jianhong Zhu; Yao Zhao; Lu Lu; Gang Chen; Georg Northoff; Gaolang Gong; et al. (Neuroscience Bulletin, 2018)

Manipulating Aeroponically Grown Potatoes with Gibberellins and Calcium Nitrate - Cui-Cun Wang; Xi-Yao Wang; Ke-Xiu Wang; Jian-Jun Hu; Ming-Xia Tang; Wei He; Peter Vander Zaag (American Journal of Potato Research, 2018)

Network-based triple-frequency carrier phase ambiguity resolution between reference stations using BDS data for long baselines - Weiming Tang; Mingxing Shen; Chenlong Deng; Jianhui Cui; Jia Yang (GPS Solutions, 2018)

Effect of different bulking agents on water variation and thermal balance and their respective contribution to bio-generated heat during long-term storage sludge biodrying process - Tiantian Liu; Chongwei Cui; Junguo He; Jian Tang (Environmental Science and Pollution Research, 2018)

Correction to: Sometimes noise is beneficial: stream noise informs vocal communication in the little torrent frog Amolops torrentis - Longhui Zhao; Bicheng Zhu; Jichao Wang; Steven E. Brauth; Yezhong Tang; Jianguo Cui (Journal of Ethology, 2018)

HpaP, a novel regulatory protein with ATPase and phosphatase activity, contributes to full virulence in Xanthomonas campestris pv. campestris - Ping Cui; Rui‐Fang Li; Da‐Pei Zhang; Ji‐Liang Tang; Guang‐Tao Lu (Environmental Microbiology, 2018)
Summary The ability of the bacterial phytopathogen Xanthomonas campestris pv. campestris ( Xcc ) to cause disease is dependent on the type III secretion system (T3SS). Proteins of the Xcc T3SS are encoded by hrp (hypersensitive response and pathogenicity) genes and whose expression is mainly controlled by the regulators HrpG and HrpX. Here, we describe the identification and characterization of a previously unknown regulatory protein ( named HpaP), which plays important role in hrp gene expression and virulence in Xcc . Clean deletion of hpaP demonstrated reduced virulence and HR (hypersensitive response) induction of Xcc and alterations in cell motility and stress tolerance. Global transcriptome analyses revealed that most hrp genes were down regulated in the hpaP mutant, suggesting HpaP positively regulates hrp genes. GUS activity assays implied that HpaP regulates the expression of hrp genes via controlling the expression of hrpX . Biochemical analyses revealed that HpaP protein had both ATPase and phosphatase activity. While further site‐directed mutagenesis of conserved residues in the PTP loop (a protein tyrosine phosphatase signature) of HpaP resulted in the loss of both phosphatase activity and regulatory activity in virulence and HR. Taken together, the findings identify a new regulatory protein that controls hrp gene expression and virulence in Xcc .

Evaluating environmental equities of urban forest in terms of cooling services using ETM+ and Google data - Ze Tang; Haifeng Zheng; Zhibin Ren; Dan Zhang; Peijiang Wang; Chang Zhai; Mingxing Cui; Xingyuan He (Journal of the Indian Society of Remote Sensing, 2018)

Synthesis and biological evaluation of novel A-seco-taxoids derived from 1-deoxybaccatin VI - Wei-Qing Qiu; Yong-Mei Cui; Ping Tang; Yuan-You Qiu; Hai-Xia Lin (Natural Product Research, 2018)

Precipitation drives the biogeographic distribution of soil fungal community in Inner Mongolian temperate grasslands - Di Wang; Yichao Rui; Kai Ding; Xiaoyong Cui; Yanbin Hao; Li Tang; Zhe Pang; Biao Zhang; Shutong Zhou; Kui Wang; Yanfen Wang (Journal of Soils and Sediments, 2018)

Instantaneous BDS + GPS undifferenced NRTK positioning with dynamic atmospheric constraints - Xuan Zou; Yawei Wang; Chenlong Deng; Weiming Tang; Zongnan Li; Jianhui Cui; Chen Wang; Chuang Shi (GPS Solutions, 2018)

Co-Delivery of Doxorubicin and Survivin shRNA-Expressing Plasmid Via Microenvironment-Responsive Dendritic Mesoporous Silica Nanoparticles for Synergistic Cancer Therapy - Zhengxiong Li; Linlin Zhang; Cui Tang; Chunhua Yin (Pharmaceutical Research, 2017)

Effects of pH, initial Pb2+ concentration, and polyculture on lead remediation by three duckweed species - Jie Tang; Chunxia Chen; Lei Chen; Maurycy Daroch; Yan Cui (Environmental Science and Pollution Research, 2017)

Effects of feeding rates on growth, feed utilization, and body composition of juvenile Pseudobagrus ussuriensis - Xianyong Bu; Xuqiu Lian; Ying Zhang; Chenghui Yang; Cunhe Cui; Jianfang Che; Baibing Tang; Baohui Su; Qicun Zhou; Yuhong Yang (Aquaculture International, 2017)

Recent advances in decomposition of the most potent greenhouse gas SF 6 - Xiaoxing Zhang; Hanyan Xiao; Ju Tang; Zhaolun Cui; Ying Zhang (Critical Reviews in Environmental Science and Technology, 2017)

Kinetics of Antioxidant-Producing Maillard Reaction in the Mixture of Ribose and Sea Cucumber ( Stichopus japonicus ) Gut Hydrolysates - Jia-Run Han; Zhi-Mo Zhu; Hai-Tao Wu; Na Sun; Yue Tang; Cui-Ping Yu; Chen-Chen Zhao; Zheng-Yu Zhang; Ao-Ting Li; Jia-Nan Yan (Journal of Aquatic Food Product Technology, 2017)

Sometimes noise is beneficial: stream noise informs vocal communication in the little torrent frog Amolops torrentis - Longhui Zhao; Bicheng Zhu; Jichao Wang; Steven E. Brauth; Yezhong Tang; Jianguo Cui (Journal of Ethology, 2017)
Many kinds of environmental noise can interfere with acoustic communication and efficient decision making in terrestrial species. Here we identified an exception to this generalization in a streamside species, the little torrent frog ( Amolops torrentis ) which communicates in a stream noise environment. To determine whether stream noise can act as a cue regarding the microhabitat characteristics of senders, we performed phonotaxis experiments using stimulus pairs constructed with synthetic male calls (high or low dominant frequency) and stream noise with varied signal-to-noise ratios. We found that females prefer calls with high amplitude stream noise added compared to those with low amplitude stream noise added for both high and low dominant frequency stimulus pairs; however, stream noise itself was not attractive in the absence of calls. These results show that stream noise can function as a cue that may be used by females for enhancing the attractiveness of calls. Stream noise associates closely with rocks, topographies and vegetation and may thus provide useful microhabitat information for signal receivers, thereby acting on sexual selection. These data therefore contribute to our understanding of how the perception of mate attractiveness in heterogeneous ecological environments can evolve.

Phytochemicals and biological activities of Artemisia sieversiana - Shi-Jun Liu; Zhi-Xin Liao; Zhi-Shu Tang; Chun-Li Cui; Hong-Bo Liu; Yan-Ni Liang; Yu Zhang; Huan-Xian Shi; Yao-Run Liu (Phytochemistry Reviews, 2017)

Involvement of the miR-462/731 cluster in hypoxia response in Megalobrama amblycephala - Cui-Hong Huang; Nan Chen; Chun-Xiao Huang; Bao Zhang; Meng Wu; Lei He; Hong Liu; Rong Tang; Wei-Min Wang; Huan-Ling Wang (Fish Physiology and Biochemistry, 2017)

Effects of Spartina alterniflora Invasion on the Abundance, Diversity, and Community Structure of Sulfate Reducing Bacteria along a Successional Gradient of Coastal Salt Marshes in China - Jun Cui; Xueping Chen; Ming Nie; Shubo Fang; Boping Tang; Zhexue Quan; Bo Li; Changming Fang (Wetlands, 2017)

Incentive effect of bentonite and concrete admixtures on stabilization/solidification for heavy metal-polluted sediments of Xiangjiang River - Ming Yan; Guangming Zeng; Xiaoming Li; Jianmin He; Guiqiu Chen; Danlian Huang; Lin Tang; Cui Lai; Chang Zhang; Xiaodong Li; Lichao Wang; Zhi Guo; et al. (Environmental Science and Pollution Research, 2017)

Human paraoxonase gene cluster overexpression alleviates angiotensin II-induced cardiac hypertrophy in mice - Jian-Fei Pei; Yun-Fei Yan; Xiaoqiang Tang; Yang Zhang; Shen-Shen Cui; Zhu-Qin Zhang; Hou-Zao Chen; De-Pei Liu (Science China Life Sciences, 2016)

Comparison of the immunogenicity of two inactivated recombinant rabies viruses overexpressing the glycoprotein - Muhammad Tariq Navid; Yingying Li; Ming Zhou; Min Cui; Zhen F. Fu; Lijun Tang; Ling Zhao (Archives of Virology, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

A Dual-Channel Sensor for Hg2+ Based on a Diarylethene with a Rhodamine B Unit - Yongjuan Tang; Shiqiang Cui; Shouzhi Pu (Journal of Fluorescence, 2016)

Hydrological monitoring and seasonal forecasting: Progress and perspectives - Qiuhong Tang; Xuejun Zhang; Qingyun Duan; Shifeng Huang; Xing Yuan; Huijuan Cui; Zhe Li; Xingcai Liu (Journal of Geographical Sciences, 2016)

Comparison of a fuzzy control and the data-driven model for flood forecasting - Yixiang Sun; Deshan Tang; Yifei Sun; Qingfeng Cui (Natural Hazards, 2016)

Characterization of the relationship between vascular bundles features and indica-allelic frequency using a seventh filial generations of indica × japonica rice crosses - Tiansheng Liu; Wenjing Bi; Jia Zhang; Yue Cui; Zhiqiang Yan; Yuanzheng Wang; Cheng Fei; Hai Xu; Liang Tang; Wenfu Chen; Jian Sun; Quan Xu (Euphytica, 2016)

Full-length genomic characterization and molecular evolution of canine parvovirus in China - Ling Zhou; Qinghai Tang; Lijun Shi; Miaomiao Kong; Lin Liang; Qianqian Mao; Bin Bu; Lunguang Yao; Kai Zhao; Shangjin Cui; Élcio Leal (Virus Genes, 2016)

Slope spectrum variation in a simulated loess watershed - Fayuan Li; Guoan Tang; Chun Wang; Lingzhou Cui; Rui Zhu (Frontiers of Earth Science, 2016)

Nickel Chloride (NiCl2) Induces Histopathological Lesions via Oxidative Damage in the Broiler’s Bursa of Fabricius - Shuang Yin; Hongrui Guo; Hengmin Cui; Xi Peng; Jing Fang; Zhicai Zuo; Junliang Deng; Xun Wang; Kun Tang; Jian Li (Biological Trace Element Research, 2016)

Sodium Channel Voltage-Gated Beta 2 Plays a Vital Role in Brain Aging Associated with Synaptic Plasticity and Expression of COX5A and FGF-2 - Yan-Bin XiYang; You-Cui Wang; Ya Zhao; Jin Ru; Bing-Tuan Lu; Yue-Ning Zhang; Nai-Chao Wang; Wei-Yan Hu; Jia Liu; Jin-Wei Yang; Zhao-Jun Wang; Chun-Guang Hao; et al. (Molecular Neurobiology, 2016)

Ice thickness, internal layers, and surface and subglacial topography in the vicinity of Chinese Antarctic Taishan station in Princess Elizabeth Land, East Antarctica - Xue-Yuan Tang; Jing-Xue Guo; Bo Sun; Tian-Tian Wang; Xiang-Bin Cui (Applied Geophysics, 2016)

Effects of spillway types on debris flow trajectory and scour behind a sabo dam - Hua-yong Chen; Peng Cui; Jian-gang Chen; Jin-bo Tang (Journal of Mountain Science, 2016)

Diachronic analysis of genetic diversity in rice landraces under on-farm conservation in Yunnan, China - Di Cui; Jinmei Li; Cuifeng Tang; Xinxiang A; Tengqiong Yu; Xiaoding Ma; Enlai Zhang; Guilan Cao; Furong Xu; Yongli Qiao; Luyuan Dai; Longzhi Han (Theoretical and Applied Genetics, 2016)

KPNβ1 promotes palmitate-induced insulin resistance via NF-κB signaling in hepatocytes - Suxin Wang; Yun Zhao; Nana Xia; Wanlu Zhang; Zhuqi Tang; Cuifang Wang; Xiaohui Zhu; Shiwei Cui (Journal of Physiology and Biochemistry, 2015)

Selection of Intracellularly Functional RNA Mimics of Green Fluorescent Protein Using Fluorescence-Activated Cell Sorting - Jiawei Zou; Xin Huang; Lei Wu; Gangyi Chen; Juan Dong; Xin Cui; Zhuo Tang (Journal of Molecular Evolution, 2015)

Isolation and Characterization of a Novel Virulent Phage of Lactobacillus casei ATCC 393 - Xi Zhang; Yu Lan; Wenchao Jiao; Yijing Li; Lijie Tang; Yanping Jiang; Wen Cui; Xinyuan Qiao (Food and Environmental Virology, 2015)

Effects of trawl selectivity and genetic parameters on fish body length under long-term trawling - Yang Yu; Peng Sun; He Cui; Huaxiang Sheng; Fenfang Zhao; Yanli Tang; Zelin Chen (Journal of Ocean University of China, 2015)

Inhibitory role of reactive oxygen species in the differentiation of multipotent vascular stem cells into vascular smooth muscle cells in rats: a novel aspect of traditional culture of rat aortic smooth muscle cells - Haibo Song; Hui Wang; Weiwei Wu; Lei Qi; Lei Shao; Fang Wang; Yimu Lai; Desiree Leach; Bryan Mathis; Joseph S. Janicki; Xing Li Wang; Dongqi Tang; et al. (Cell and Tissue Research, 2015)

Effects of a rhizobacterium on the growth of and chromium remediation by Lemna minor - Jie Tang; Ying Zhang; Yan Cui; Jiong Ma (Environmental Science and Pollution Research, 2015)

Exploring Advantages/Disadvantages and Improvements in Overcoming Gene Delivery Barriers of Amino Acid Modified Trimethylated Chitosan - Hao Zheng; Cui Tang; Chunhua Yin (Pharmaceutical Research, 2015)

Ethylene increases accumulation of compatible solutes and decreases oxidative stress to improve plant tolerance to water stress in Arabidopsis - Mengying Cui; Yingchao Lin; Yuangang Zu; Thomas Efferth; Dewen Li; Zhonghua Tang (Journal of Plant Biology, 2015)

Plastorhodobacter daqingensis gen. nov., sp. nov.: A Non-phototrophic Bacterium Isolated from Daqing Oilfield - Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Yue-Qin Tang; Ya-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2015)

Inhibitive Effects of Nickel Chloride (NiCl2) on Thymocytes - Kun Tang; Hongrui Guo; Jie Deng; Hengmin Cui; Xi Peng; Jing Fang; Zhicai Zuo; Xun Wang; Bangyuan Wu; Jian Li; Shuang Yin (Biological Trace Element Research, 2015)

Activation of NOD1 by DAP contributes to myocardial ischemia/reperfusion injury via multiple signaling pathways - Hui Yang; Nan Li; Li-Na Song; Lei Wang; Cui Tian; Chao-Shu Tang; Jie Du; Hui-Hua Li; Xiao-Hong Yu; Hong-Xia Wang (Apoptosis, 2015)

QTL analysis of three flower-related traits based on an interspecific genetic map of Luffa - Junjie Cui; Jiaowen Cheng; Guoping Wang; Xin Tang; Zhiming Wu; Mingbao Lin; Lianfang Li; Kailin Hu (Euphytica, 2015)

Assessment of conventional French railway sub-structure: a case study - T. V. Duong; Y. J. Cui; A. M. Tang; N. Calon; A. Robinet (Bulletin of Engineering Geology and the Environment, 2015)

Halodurantibacterium flavum gen. nov., sp. nov., a Non-phototrophic Bacterium Isolated from an Oil Production Mixture - Xiang-Lin Lv; Bai-Sheng Xie; Man Cai; Yue-Qin Tang; Ya-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2015)

The Effects of Wubeizi Ointment on the Proliferation of Keloid-Derived Fibroblasts - Ji-cun Ding; Zhi-ming Tang; Xiao-xiang Zhai; Xiang-hui Chen; Jing-guo Li; Cui-xia Zhang (Cell Biochemistry and Biophysics, 2015)
To evaluate the effectiveness of the Wubeizi (WBZ) ointment on keloid-derived fibroblasts. The primary cells of the keloid-derived fibroblasts were cultured and the effectiveness of the WBZ ointment at different concentrations was examined by MTT colorimetric methods on keloid-derived fibroblasts. The WBZ ointment showed inhibitory effects on proliferating the keloid-derived fibroblasts ( P < 0.01)in a time- and dose-dependent manner. The proportion of cells in S stage was significantly higher in each of the WBZ ointment group than in the control group ( P <0.01), and the proportion of G 2 + M stage cells was significantly lower than that of control group, which was statistically significant ( P < 0.01).The inhibitory effects of the S and G 2 + M stage increased with higher drug concentrations ( P < 0.05). Conclusion: The WBZ ointment can inhibit the proliferation of the keloid-derived fibroblasts in a time- and dose- dependent manner.

Seohaeicola nanhaiensis sp. nov., A Moderately Halophilic Bacterium Isolated from the Benthic Sediment of South China Sea - Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Yue-Qin Tang; Yan-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2014)

NiCl2-Down-Regulated Antioxidant Enzyme mRNA Expression Causes Oxidative Damage in the Broiler’s Kidney - Hongrui Guo; Bangyuan Wu; Hengmin Cui; Xi Peng; Jing Fang; Zhicai Zuo; Junliang Deng; Xun Wang; Jie Deng; Shuang Yin; Jian Li; Kun Tang (Biological Trace Element Research, 2014)

Association of interleukin-23 receptor gene polymorphisms with risk of bladder cancer in Chinese - Tielong Tang; Hui Xue; Shu Cui; Zhiyong Gong; Zhonghai Fei; Shulin Cheng; Chunyan Gui (Familial Cancer, 2014)

Asymmetric sensitivity of first flowering date to warming and cooling in alpine plants - S. P. Wang; F. D. Meng; J. C. Duan; Y. F. Wang; X. Y. Cui; S. L. Piao; H. S. Niu; G. P. Xu; C. Y. Luo; Z. H. Zhang; X. X. Zhu; M. G. Shen; et al. (Ecology, 2014)
Understanding how flowering phenology responds to warming and cooling (i.e., symmetric or asymmetric response) is needed to predict the response of flowering phenology to future climate change that will happen with the occurrence of warm and cold years superimposed upon a long‐term trend. A three‐year reciprocal translocation experiment was performed along an elevation gradient from 3200 m to 3800 m in the Tibetan Plateau for six alpine plants. Transplanting to lower elevation (warming) advanced the first flowering date (FFD) and transplanting to higher elevation (cooling) had the opposite effect. The FFD of early spring flowering plants (ESF) was four times less sensitive to warming than to cooling (by −2.1 d/°C and 8.4 d/°C, respectively), while midsummer flowering plants (MSF) were about twice as sensitive to warming than to cooling (−8.0 d/°C and 4.9 d/°C, respectively). Compared with pooled warming and cooling data, warming alone significantly underpredicted 3.1 d/°C for ESF and overestimated 1.7 d/°C for MSF. These results suggest that future empirical and experimental studies should consider nonlinear temperature responses that can cause such warming–cooling asymmetries as well as differing life strategies (ESF vs. MSF) among plant species.

Effects of BMP-2 and FGF2 on the Osteogenesis of Bone Marrow-Derived Mesenchymal Stem Cells in Hindlimb-Unloaded Rats - Xiaodan Qian; Cui Zhang; Guojun Chen; Zihua Tang; Quanwen Liu; Jiarong Chen; Xiangming Tong; Jinfu Wang (Cell Biochemistry and Biophysics, 2014)

Effects of Nickel Chloride on the Erythrocytes and Erythrocyte Immune Adherence Function in Broilers - Jian Li; Bangyuan Wu; Hengmin Cui; Xi Peng; Jing Fang; Zhicai Zuo; Junliang Deng; Xun Wang; Kun Tang; Shuang Yin (Biological Trace Element Research, 2014)

Studies on the isolation and culture of protoplasts from Kappaphycus alvarezii - Si Zhang; Cui Liu; Yuemei Jin; Shan Chi; Xianming Tang; Fuxiao Chen; Xu Fang; Tao Liu (Acta Oceanologica Sinica, 2014)

Effects of warming on root diameter, distribution, and longevity in an alpine meadow - Yibo Wu; Jing Zhang; Yongcui Deng; Jing Wu; Shiping Wang; Yanhong Tang; Xiaoyong Cui (Plant Ecology, 2014)

Effects of Dietary Zinc Oxide Nanoparticles on Growth Performance and Antioxidative Status in Broilers - Cui-Yan Zhao; Shu-Xian Tan; Xi-Yu Xiao; Xian-Shuai Qiu; Jia-Qiang Pan; Zhao-Xin Tang (Biological Trace Element Research, 2014)

Phylogeny of genera Laminaria and Saccharina (Laminariales, Phaeophyceae) based on three molecular markers - Shan Chi; Hao Qian; Tianyong Li; Xumin Wang; Cui Liu; Lei Ren; Xuexi Tang; Tao Liu (Acta Oceanologica Sinica, 2014)

Molecular cloning and characterization of NPR1 gene from Arachis hypogaea - Qi Wu; Xiu Zhen Wang; Yue Yi Tang; Hong Tao Yu; Yu Fei Ding; Chuan De Yang; Feng Gao Cui; Jian Cheng Zhang; Chuan Tang Wang (Molecular Biology Reports, 2014)

Expression of TGF-β1, SNAI1 and MMP-9 is associated with lymph node metastasis in papillary thyroid carcinoma - Ni Wang; Rong Jiang; Jun-Yan Yang; Cui Tang; Lei Yang; Man Xu; Qi-Feng Jiang; Zhi-Min Liu (Journal of Molecular Histology, 2014)

Functional and safety evaluation of transgenic pork rich in omega-3 fatty acids - Maoxue Tang; Lili Qian; Shengwang Jiang; Jian Zhang; Pengkun Song; Yaoxing Chen; Wentao Cui; Kui Li (Transgenic Research, 2014)

Analysis of Methylated Patterns and Quality-Related Genes in Tobacco (Nicotiana tabacum) Cultivars - Junna Jiao; Yanlong Jia; Zhuangwei Lv; Chuanfei Sun; Lijie Gao; Xiaoxiao Yan; Liusu Cui; Zongxiang Tang; Benju Yan (Biochemical Genetics, 2014)

Overexpression of Glycine soja WRKY20 enhances both drought and salt tolerance in transgenic alfalfa (Medicago sativa L.) - Lili Tang; Hua Cai; Hong Zhai; Xiao Luo; Zhenyu Wang; Lin Cui; Xi Bai (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Characterizing the heavy metal-complexing potential of fluorescent water-extractable organic matter from composted municipal solid wastes using fluorescence excitation–emission matrix spectra coupled with parallel factor analysis - Xiao-Song He; Bei-Dou Xi; Hong-Wei Pan; Xiang Li; Dan Li; Dong-Yu Cui; Wen-Bin Tang; Ying Yuan (Environmental Science and Pollution Research, 2014)

Effects of Sodium Selenite on Aflatoxin B1-Induced Decrease of Ileal IgA+ Cell Numbers and Immunoglobulin Contents in Broilers - Yang He; Jing Fang; Xi Peng; Hengmin Cui; Zhicai Zuo; Junliang Deng; Zhengli Chen; Yi Geng; Weimin Lai; Gang Shu; Li Tang (Biological Trace Element Research, 2014)

Genetic structure of duckweed population of Spirodela, Landoltia and Lemna from Lake Tai, China - Jie Tang; Fei Zhang; Weihua Cui; Jiong Ma (Planta, 2014)

Effects of Sodium Selenite on Aflatoxin B1-Induced Decrease of Ileac T cell and the mRNA Contents of IL-2, IL-6, and TNF-α in Broilers - Yang He; Jing Fang; Xi Peng; Hengmin Cui; Zhicai Zuo; Junliang Deng; Zhengli Chen; Weimin Lai; Gang Shu; Li Tang (Biological Trace Element Research, 2014)

Assessment of the distribution and risks of organochlorine pesticides in core sediments from areas of different human activity on Lake Baiyangdian, China - Wei Guo; Huayong Zhang; Songbo Cui; Qigong Xu; Zhenwu Tang; Fan Gao (Stochastic Environmental Research and Risk Assessment, 2014)

Mechanisms of Anti-inflammatory Property of Conserved Dopamine Neurotrophic Factor: Inhibition of JNK Signaling in Lipopolysaccharide-Induced Microglia - Hua Zhao; Lei Cheng; Yi Liu; Wen Zhang; Sailendra Maharjan; Zhaoqiang Cui; Xingli Wang; Dongqi Tang; Lin Nie (Journal of Molecular Neuroscience, 2014)

Electroencephalographic signals synchronize with behaviors and are sexually dimorphic during the light–dark cycle in reproductive frogs - Ping Yang; Guangzhan Fang; Fei Xue; Jianguo Cui; Steven E. Brauth; Yezhong Tang (Journal of Comparative Physiology A, 2014)

Complete genome sequence analysis of two human enterovirus C99 strains isolated in Xinjiang Uighur Autonomous Region, China, in 2011 - Qiang Sun; Yong Zhang; Hui Cui; Shuangli Zhu; Xiaolei Li; Guohong Huang; Haishu Tang; Dongmei Yan; Dongyan Wang; Wenbo Xu (Archives of Virology, 2014)

Effects of PTHrP on chondrocytes of sika deer antler - Bin Guo; Shou-Tang Wang; Cui-Cui Duan; Dang-Dang Li; Xue-Chao Tian; Qu-Yuan Wang; Zhan-Peng Yue (Cell and Tissue Research, 2013)

Structure and dynamics of the bacterial communities in fermentation of the traditional Chinese post-fermented pu-erh tea revealed by 16S rRNA gene clone library - Ming Zhao; Wei Xiao; Yan Ma; Tingting Sun; Wenxia Yuan; Na Tang; Donglian Zhang; Yongxia Wang; Yali Li; Hongjie Zhou; Xiaolong Cui (World Journal of Microbiology and Biotechnology, 2013)

Trimethyl Chitosan-Cysteine Nanoparticles for Systemic Delivery of TNF-α siRNA via Oral and Intraperitoneal Routes - Chunbai He; Lichen Yin; Cui Tang; Chunhua Yin (Pharmaceutical Research, 2013)

Experimental study on cascading landslide dam failures by upstream flows - Gordon G. D. Zhou; P. Cui; H. Y. Chen; X. H. Zhu; J. B. Tang; Q. C. Sun (Landslides, 2013)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

Microarray analysis of differentially expressed transcripts in porcine intestinal epithelial cells (IPEC-J2) infected with porcine sapelovirus as a model to study innate immune responses to enteric viruses - Daoliang Lan; Cheng Tang; Hua Yue; Huan Sun; Li Cui; Xiuguo Hua; Jian Li (Archives of Virology, 2013)

The combined effects of transforming growth factor-β and basic fibroblast growth factor on the human degenerated nucleus pulposus cells in monolayer culture - Erxing He; Ji Hao Cui; Chuang Li; Cheng Tang; In-Sung Kim; Young-Woo Kim; Ho-Guen Chang; Jae-Ryong Cha; Oh-Jong Byung; Yong-Chan Kim (Tissue Engineering and Regenerative Medicine, 2013)

A mutation in a coproporphyrinogen III oxidase gene confers growth inhibition, enhanced powdery mildew resistance and powdery mildew-induced cell death in Arabidopsis - Chuan-yu Guo; Guang-heng Wu; Jin Xing; Wen-qi Li; Ding-zhong Tang; Bai-ming Cui (Plant Cell Reports, 2013)

Ternary Polymeric Nanoparticles for Oral siRNA Delivery - Jing Zhang; Chunbai He; Cui Tang; Chunhua Yin (Pharmaceutical Research, 2013)

Quantitative evaluation of Candia antarctica lipase B displayed on the cell surface of a Pichia pastoris based on an FS anchor system - Xing-xiang Liang; Bei-bei Wang; Yu-fei Sun; Ying Lin; Shuang-yan Han; Sui-ping Zheng; Tang-bing Cui (Biotechnology Letters, 2013)

Effect of targeted silencing of hTERT mRNA by lentivirus-mediated siRNA on A549 lung cancer cells in vitro - Haibo Tang; Linhu Ge; Wenlong Shao; Yuan Qiu; Dong Cui (Molecular Biology Reports, 2013)

Antigenic and genetic characterization of a European avian-like H1N1 swine influenza virus from a boy in China in 2011 - Xian Qi; Lunbiao Cui; Yongjun Jiao; Yuning Pan; Xihan Li; Rongqiang Zu; Xiang Huo; Bin Wu; Fengyang Tang; Yongchun Song; Minghao Zhou; Hua Wang; et al. (Archives of Virology, 2013)

Erratum to: A 90-day safety study of genetically modified rice expressing rhIGF-1 protein in C57BL/6J mice - Maoxue Tang; Tingting Xie; Wenke Cheng; Lili Qian; Shulin Yang; Daichang Yang; Wentao Cui; Kui Li (Transgenic Research, 2012)

Regulation of colon cancer cell migration and invasion by CLIC1-mediated RVD - Pan Wang; Chao Zhang; PeiWu Yu; Bo Tang; Tao Liu; Hao Cui; JianHua Xu (Molecular and Cellular Biochemistry, 2012)

Molecular detection of Torque teno mini virus (TTMV) in China - Caixia Zhu; Rong A; Congli Yuan; Ying Yu; Li Cui; S. D. Tang; Zhiwei Liu; Wei Zhao; Xiuguo Hua (Virus Genes, 2012)

A 90-day safety study of genetically modified rice expressing rhIGF-1 protein in C57BL/6J rats - Maoxue Tang; Tingting Xie; Wenke Cheng; Lili Qian; Shulin Yang; Daichang Yang; Wentao Cui; Kui Li (Transgenic Research, 2012)

Erratum to: hRpn13, a newly identified component of the 19S particle, regulates proliferation, differentiation, and function in the human osteoblast-like cell line MG63 - Xi Zhao; Yonglie Chao; Pixiu Chen; Die Liu; Peng Su; Xuqin Cui; Jian Sun; Yaxiong Tang (Journal of Physiology and Biochemistry, 2012)

hRpn13, a newly identified component of the 19S particle, regulates proliferation, differentiation, and function in the human osteoblast-like cell line MG63 - Xi Zhao; Yonglie Chao; Pixiu Chen; Yaxiong Tang; Die Liu; Peng Su; Xuqin Cui (Journal of Physiology and Biochemistry, 2012)

Electroencephalogram bands modulated by vigilance states in an anuran species: a factor analytic approach - Guangzhan Fang; Qin Chen; Jianguo Cui; Yezhong Tang (Journal of Comparative Physiology A, 2012)

Catastrophic debris flows triggered by a 14 August 2010 rainfall at the epicenter of the Wenchuan earthquake - Chuan Tang; Jing Zhu; Jun Ding; Xiaofei F. Cui; Lei Chen; Jianshi S. Zhang (Landslides, 2011)

Synthesis and evaluation of κ-opioid receptor agonistic activity and antinociceptive effect of novel morphine analogues, 7α-phenyl-6α,14α-endo-etheno-tetrahydrothebaine with substituted o-, m- and p-amino group - Hong Qi; Wei Li; Yu Qiu; Yong-yao Cui; Jian Ma; Xiao-ling Gao; Yi-bin Zeng; Jie Yang; Yun Tang; Xing-hai Wang; Wei Sheng; Qiong Xie; et al. (Medicinal Chemistry Research, 2011)

Discovering the distinct inhibitory effects between C4-epimeric glycosyl amino acids: new insight into the development of protein tyrosine phosphatase inhibitors - Xiao-Peng He; Cui Li; Zhi-Zhou Wang; Li-Xin Gao; Xiao-Xin Shi; Yun Tang; Juan Xie; Jia Li; Guo-Rong Chen; Kaixian Chen (Glycoconjugate Journal, 2011)

Morphological and molecular evidences for a new species of Lignosus (Polyporales, Basidiomycota) from tropical China - Bao-Kai Cui; Li-Ping Tang; Yu-Cheng Dai (Mycological Progress, 2011)

Safety assessment of sFat-1 transgenic pigs by detecting their co-habitant microbe in intestinal tract - Maoxue Tang; Xinmin Zheng; Wenke Cheng; Erhui Jin; Hongxing Chen; Shulin Yang; Wentao Cui; Kui Li (Transgenic Research, 2011)

Expression of Bioactive Thymosin Alpha 1 (Tα1) in Marker-free Transgenic Lettuce (Lactuca sativa) - Lijie Cui; Yuhui Chen; Guoan Shen; Lingxia Zhao; Kexuan Tang (Plant Molecular Biology Reporter, 2011)

Candidate genes involved in tanshinone biosynthesis in hairy roots of Salvia miltiorrhiza revealed by cDNA microarray - Guanghong Cui; Luqi Huang; Xiaojing Tang; Jingxue Zhao (Molecular Biology Reports, 2011)

Structure of the internal isochronous layers at Dome A, East Antarctica - XueYuan Tang; Bo Sun; ZhanHai Zhang; XiangPei Zhang; XiangBin Cui; Xin Li (Science China Earth Sciences, 2011)

Molecular analysis of a homogentisate phytyltransferase gene from Lactuca sativa L. - Weiwei Ren; Lingxia Zhao; Lida Zhang; Yuliang Wang; Lijie Cui; Yueli Tang; Xiaofen Sun; Kexuan Tang (Molecular Biology Reports, 2011)

Phylogeny of Arachis based on internal transcribed spacer sequences - Chuan Tang Wang; Xiu Zhen Wang; Yue Yi Tang; Dian Xu Chen; Feng Gao Cui; Jian Cheng Zhang; Shan Lin Yu (Genetic Resources and Crop Evolution, 2011)

Comprehensive assessments of root biomass and production in a Kobresia humilis meadow on the Qinghai-Tibetan Plateau - Yibo Wu; Jing Wu; Yongcui Deng; Hongchao Tan; Yangong Du; Song Gu; Yanhong Tang; Xiaoyong Cui (Plant and Soil, 2011)

Movement patterns of Bar-headed Geese Anser indicus during breeding and post-breeding periods at Qinghai Lake, China - Peng Cui; Yuansheng Hou; Mingjie Tang; Haiting Zhang; Yuanchun Zhou; Zuohua Yin; Tianxian Li; Shan Guo; Zhi Xing; Yubang He; Diann J. Prosser; Scott H. Newman; et al. (Journal of Ornithology, 2011)

Molecular characterization, polymorphism of bovine ZBTB38 gene and association with body measurement traits in native Chinese cattle breeds - Yongfeng Liu; Linsen Zan; Shuanping Zhao; Yaping Xin; Linqiang Li; Wentao Cui; Zhonglin Tang; Kui Li (Molecular Biology Reports, 2010)

Expression of the housefly acetylcholinesterase in a bioreactor and its potential application in the detection of pesticide residues - Guo-Jun Lang; Jin-Yan Shang; Yan-Xia Chen; Ying-Jun Cui; Qiang Wang; Zhen-Hua Tang; Chuan-Xi Zhang (World Journal of Microbiology and Biotechnology, 2010)

Partitioning pattern of carbon flux in a Kobresia grassland on the Qinghai‐Tibetan Plateau revealed by field 13 C pulse‐labeling - YIBO WU; HONGCHAO TAN; YONGCUI DENG; JING WU; XINGLIANG XU; YANFEN WANG; YANHONG TANG; TERUO HIGASHI; XIAOYONG CUI (Global Change Biology, 2010)
Characterizing the carbon turnover in terrestrial ecosystems is critical for understanding and predicting carbon dynamics in ecosystems. We used in situ 13 C pulse labeling to track photosynthetic carbon fluxes from shoot to roots and to soil in a Kobresia humilis meadow on the Qinghai‐Tibet Plateau. We found that about 36.7% of labeled carbon was translocated out from the shoots within the first 24 h after photosynthetic uptake. This is equivalent to 66.1% of total 13 C moving out from the shoot during the 32‐day chase period, indicating a rapid and large translocation of newly fixed carbon to belowground parts in these alpine plants. 58.7% of the assimilated 13 C was transferred belowground. At the end of the chase phase, 30.9% was retained in living roots, 3.4% in dead roots, 17.2% lost as belowground respiration and 7.3% remained in the soil. In the four carbon pools (i.e., shoots, living roots, dead roots, and soil pools), living roots consistently had the highest proportion of 13 C in the plant–soil system during the 32 days. Based on the 13 C partitioning pattern and biomass production, we estimate a total of 4930 kg C ha −1 was allocated belowground during the vegetation growth season in this alpine meadow. Of this, roots accumulated 2868 kg C ha −1 and soils accumulated 613 kg C ha −1 . This study suggests that carbon storage in belowground carbon pools plays the most important role in carbon cycles in the alpine meadow.

Zhihengliuella salsuginis sp. nov., a moderately halophilic actinobacterium from a subterranean brine - Yi-Guang Chen; Shu-Kun Tang; Yu-Qin Zhang; Zhu-Xiang Liu; Qi-Hui Chen; Jian-Wu He; Xiao-Long Cui; Wen-Jun Li (Extremophiles, 2010)

Molecular characterization and association analysis of porcine PANE1 gene - Honggang Huang; Hong Deng; Yiling Yang; Zhonglin Tang; Shulin Yang; Yulian Mu; Wentao Cui; Jing Yuan; Zhenfang Wu; Kui Li (Molecular Biology Reports, 2010)

The chromosomal localization, expression pattern and polymorphism analysis of porcine FSCN1 gene differently expressed from LongSAGE library - Zh. L. Tang; X. J. Zhang; Sh. L. Yang; Y. L. Mu; W. T. Cui; H. Ao; K. Li (Molecular Biology Reports, 2010)

Quinoline biodegradation and its nitrogen transformation pathway by a Pseudomonas sp. strain - Yaohui Bai; Qinghua Sun; Cui Zhao; Donghui Wen; Xiaoyan Tang (Biodegradation, 2010)

Association Analysis of the RET Proto-Oncogene with Hirschsprung Disease in the Han Chinese Population of Southeastern China - Cui-Ping Liu; Qian-Qian Tang; Jin-Tu Lou; Chun-Fen Luo; Xue-Wu Zhou; Dong-Mei Li; Fei Chen; Xiang Li; Ji-Cheng Li (Biochemical Genetics, 2010)

Isolation, Functional Characterization, and Expression Pattern of a Vacuolar Na+/H+ Antiporter Gene TrNHX1 from Trifolium repens L. - Rui Tang; Cui Li; Kai Xu; Yanhua Du; Tao Xia (Plant Molecular Biology Reporter, 2010)

Partial molecular characterization, expression pattern, polymorphism and association analysis of porcine SKP2 gene - Y. Li; S. L. Yang; Z. L. Tang; W. T. Cui; Y. L. Mu; M. X. Chu; S. H. Zhao; Z. F. Wu; K. M. Peng; K. Li (Molecular Biology Reports, 2010)

Evaluation of the geology-environmental capacity of buildings based on the ANFIS model of the floor area ratio - Zhen-Dong Cui; Yi-Qun Tang; Xue-Xin Yan; Chun-Ling Yan; Han-Mei Wang; Jian-Xiu Wang (Bulletin of Engineering Geology and the Environment, 2010)

Expression and SNP association analysis of porcine FBXL4 gene - Y. Li; S. L. Yang; Z. L. Tang; W. T. Cui; Y. L. Mu; M. X. Chu; S. H. Zhao; Z. F. Wu; K. Li; K. M. Peng (Molecular Biology Reports, 2010)

Distribution of pathogenic Yersinia enterocolitica in China - X. Wang; Z. Cui; D. Jin; L. Tang; S. Xia; H. Wang; Y. Xiao; H. Qiu; Q. Hao; B. Kan; J. Xu; H. Jing (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Virgibacillus litoralis sp. nov., a moderately halophilic bacterium isolated from saline soil - Yi-Guang Chen; Zhu-Xiang Liu; De-Jiao Peng; Yu-Qin Zhang; Yong-Xia Wang; Shu-Kun Tang; Wen-Jun Li; Xiao-Long Cui; Yan-Qi Liu (Antonie van Leeuwenhoek, 2009)

Alteromonas halophila sp. nov., a new moderately halophilic bacterium isolated from a sea anemone - Yi-Guang Chen; Huai-Dong Xiao; Shu-Kun Tang; Yu-Qin Zhang; Entomack Borrathybay; Xiao-Long Cui; Wen-Jun Li; Yan-Qi Liu (Antonie van Leeuwenhoek, 2009)

Marinobacter zhanjiangensis sp. nov., a marine bacterium isolated from sea water of a tidal flat of the South China Sea - Da-Chun Zhuang; Yi-Guang Chen; Yu-Qin Zhang; Shu-Kun Tang; Xiao-Lei Wu; Zhou-Cai Tan; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Transcriptional analysis of the hsp70 gene in a haloarchaeon Natrinema sp. J7 under heat and cold stress - Hao Zhang; Peng Cui; Lu Lin; Ping Shen; Bing Tang; Yu-Ping Huang (Extremophiles, 2009)

Des-γ-carboxy prothrombin stimulates human vascular endothelial cell growth and migration - Su-Bo Wang; Yan-Na Cheng; Shu-Xiang Cui; Julia Li Zhong; S. G. Ward; Li-Rui Sun; Ming-Hui Chen; Norihiro Kokudo; Wei Tang; Xian-Jun Qu (Clinical & Experimental Metastasis, 2009)

Morphology and genome of Euproctis pseudoconspersa nucleopolyhedrovirus - Xu-Dong Tang; Qiang Xiao; Xiu-Cui Ma; Zeng-Rong Zhu; Chuan-Xi Zhang (Virus Genes, 2009)

Halobacillus naozhouensis sp. nov., a moderately halophilic bacterium isolated from a sea anemone - Yi-Guang Chen; Zhi-Xiong Liu; Yu-Qin Zhang; You-Xiang Zhang; Shu-Kun Tang; Entomack Borrathybay; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Arthrobacter halodurans sp. nov., a new halotolerant bacterium isolated from sea water - Yi-Guang Chen; Shu-Kun Tang; Yu-Qin Zhang; Zhao-Yang Li; Lang-Bo Yi; Yong-Xia Wang; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Halomonas sediminis sp. nov., a new halophilic bacterium isolated from salt-lake sediment in China - Heng-Yu Huang; Yi-Guang Chen; Yong-Xia Wang; Ji-Hui Liu; Shu-Kun Tang; Qian Peng; Meng-Liang Wen; Hong Yu; Xiao-Long Cui (Extremophiles, 2008)

Microbial degradation and metabolic pathway of pyridine by a Paracoccus sp. strain BW001 - Yaohui Bai; Qinghua Sun; Cui Zhao; Donghui Wen; Xiaoyan Tang (Biodegradation, 2008)

Mechanosensitive Channels: Insights from Continuum-Based Simulations - Yuye Tang; Jejoong Yoo; Arun Yethiraj; Qiang Cui; Xi Chen (Cell Biochemistry and Biophysics, 2008)

Climatic characteristics of high temperature in East China during 1961–2005 - Jun Shi; Xu Tang; Linli Cui (Journal of Geographical Sciences, 2008)

Model test study of land subsidence caused by high-rise building group in Shanghai - Yi-Qun Tang; Zhen-Dong Cui; Jian-Xiu Wang; Chen Lu; Xue-Xin Yan (Bulletin of Engineering Geology and the Environment, 2008)

Synthesis and Luminescent Properties of Lanthanide Complexes with a Novel Multipodal Ligand - Zhen-Zhong Yan; Yu Tang; Wei-Sheng Liu; Hai-Xia Cui; Min-Yu Tan (Journal of Fluorescence, 2008)

11,12-Epoxyeicosatrienoic acid activates the l-arginine/nitric oxide pathway in human platelets - Like Zhang; Yuying Cui; Bing Geng; Xiangjun Zeng; Chaoshu Tang (Molecular and Cellular Biochemistry, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

MHC-BPS: MHC-binder prediction server for identifying peptides of flexible lengths from sequence-derived physicochemical properties - Juan Cui; Lian Yi Han; Hong Huang Lin; Zhi Qun Tang; Li Jiang; Zhi Wei Cao; Yu Zong Chen (Immunogenetics, 2006)

Role of the JAK-STAT pathway in protection of hydrogen peroxide preconditioning against apoptosis induced by oxidative stress in PC12 cells - H. M. Yu; J. L. Zhi; Y. Cui; E. H. Tang; S. N. Sun; J. Q. Feng; P. X. Chen (Apoptosis, 2006)

Curcumin protects PC12 cells against 1-methyl-4-phenylpyridinium ion-induced apoptosis by bcl-2-mitochondria-ROS-iNOS pathway - J. Chen; X. Q. Tang; J. L. Zhi; Y. Cui; H. M. Yu; E. H. Tang; S. N. Sun; J. Q. Feng; P. X. Chen (Apoptosis, 2006)

Identification and Characterization of the Human SCAN Domain Zinc-Finger Gene ZNF449 - Kuntian Luo; Jie Li; Yanhui Cui; Meng Xu; Jian Yuan; Wenwen Tang; Bo Wan; Long Yu (Molecular Biology Reports, 2006)

Two naturally occurring deletion mutants of 12S seed storage proteins in Arabidopsis thaliana - Anfu Hou; Kede Liu; Niramol Catawatcharakul; Xurong Tang; Vi Nguyen; Wilfred A. Keller; Edward W. T. Tsang; Yuhai Cui (Planta, 2005)

Decadal‐scale variations of ecosystem productivity and control mechanisms in the Bohai Sea - Qisheng Tang; Xianshi Jin; Jun Wang; Zhimeng Zhuang; Yi Cui; Tianxiang Meng (Fisheries Oceanography, 2003)
Decadal‐scale variations of ecosystem productivity in the Bohai Sea are described by using the survey data of 1959–60, 1982–83, 1992–93 and 1998–99. Indices including chlorophyll a concentration, primary production, phytoplankton abundance, zooplankton biomass and fishery biomass were used to describe the ecosystem productivity at different trophic levels. During the past four decades, the productivity and community structure of the Bohai Sea ecosystem has been highly variable. Primary productivity and fish productivity decreased from 1959 to 1998, such that phytoplankton abundance in 1992 and 1998 was about 38% of that in 1959 and 1982, fishery biomass in 1998 was particularly low, which was only about 5% of that in 1959. Zooplankton secondary productivity also showed a decreasing trend from 1959 to 1992, but reached high levels in 1998, about three times as much as 1959 and 1982, and four times as much as 1992. These results indicate that a large variation in ecosystem productivity is one of the important characteristics of coastal ecosystem dynamics. Therefore, it is impossible to apply a single theory to explain the causes of variations in the Bohai Sea ecosystem as the changes in productivity are likely to be forced and/or modulated by multiple mechanisms.

Cloning of human myeloid-associated differentiation marker (MYADM) gene whose expression was up-regulated in NB4 cells induced by all-trans retinoic acid - Wanchang Cui; Long Yu; Hua He; Yaya Chu; Jie Gao; Bo Wan; Lisha Tang; Shouyuan Zhao (Molecular Biology Reports, 2001)